Onboard CO2 capture for the transport sector: A comprehensive review of technologies, system integration, and sector-specific feasibility - Khalid Elserfy; Muhammad Zubair Shahid; Mohamed Hamdy; Mhadi A. Ismael; Alaa M. Khedr; Mohammed El-Adawy; Medhat A. Nemitallah (Fuel, 2027)

Optimization and Evaluation of Aceclofenac Loaded Solid Lipid Nanoparticles via Response Surface Methodology - Khadija Saleem; Nariman Shahid; Badarqa Tul Ayesha; Alia Erum; Amna Wajdan; Kashif Barkat; Ume Ruqia Tulain; Muhammad Umer Ashraf; Sana Hanif (Journal of Pharmaceutical Innovation, 2027)

Multi-omics reveals the microbial succession-driven metabolic regulation during sequential fermentation of fresh Spirulina - Kerui Su; Ayesha Shahid; Bingyu Shi; Anqi Zhao; Farouk Kamel EI-Baz; Sami I. Ali; Mohammad Asraful Alam; Muhammad Aamer Mehmood; Shenglei Bi; Shuai Yang; Jingliang Xu (International Journal of Food Microbiology, 2026)

Changing thunderstorms environments in Saudi Arabia: Frequency, variability and drivers of change - Moutassem El Rafei; Andrew Dowdy; Mazen E. Assiri; Md. Arfan Ali; Muhammad Haroon Siddiqui; Sajjad Saeed; Saeed Ahmad Alghamdi; Shamsuddin Shahid (Atmospheric Research, 2026)

Decoding PARP roles in breast cancer therapy resistance - Mohammad Abohassan; Farag M. Altalbawy; Majid S. Jabir; Thikra F. Hasan; Ashishkumar Kyada; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Munthar Kadhim Abosaoda; Muhammad Shahid Iqbal (Molecular Biology Reports, 2026)

Molecular mechanisms governing exosome biogenesis, engineering strategies, and emerging role as cell-free therapeutics - Muhammad Hassan Raza; Javaria Ilyas; Kashf Shahid; Zania Urooj; Maria Tayyab Baig; Muhammad Shahid (Molecular Biology Reports, 2026)

Deubiquitinases at the crossroads of ferroptosis and cancer therapy: mechanisms and therapeutic potential - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Sumaya Nadhim Mohammed; Haitham L. Abdulhadi; Manoj A. Vora; Tina Saeed Basunduwah; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Wessam T. Muslem (Molecular Biology Reports, 2026)

SUMOylation machinery protein, PIAS4 role in breast cancer cell proliferation and drug sensitivity - Mohammed A. M. Salih; Mohamed M. A. E. L. Salem; Muhammad Ali Shahid; Hussein A. S. Elrewey; Ritchie Williamson; Sriharsha Kantamneni (Molecular Biology Reports, 2026)
Purpose Breast cancer is a significant global health issue, with resistance to doxorubicin (DOX) posing a major challenge to effective treatment. SUMOylation, a post-translational modification process, is linked to cancer progression and therapy resistance. PIAS4, a SUMO E3 ligase involved in maintaining genome stability and stress response, may play a role in these mechanisms. However, its function in breast cancer progression and DOX resistance remains uncertain. This study investigates the potential role of PIAS4 in mediating DOX resistance in breast cancer. Methods and results Naked mole-rats (NMRs) are cancer-resistant rodents with improved genome maintenance, yet the role of SUMOylation in this trait remains unclear. SUMOylation machinery gene expression levels are investigated using qPCR in NMR tissue in comparison with carcinogenic breast cancer (MCF-7) cell line. Functional studies are performed in MCF-7 cells overexpressing PIAS4 to demonstrate effects on proliferation, invasion, drug sensitivity, and protein expression in the presence and absence of DOX treatment. While most SUMOylation genes were expressed at low levels in NMR intestinal tissues, PIAS4 showed higher expression compared to MCF-7 cells. PIAS4 overexpression in MCF-7 cells significantly decreases colony formation, invasiveness, and resistance to DOX. Western blot analysis showed downregulated Bcl-2 protein levels after DOX treatment, indicating a potential role in apoptosis evasion. Conclusion PIAS4 expression level plays a role in breast cancer cell survival, invasiveness, and chemoresistance, partly by altering anti-apoptotic pathways. These findings position PIAS4 as a potential biomarker and therapeutic target for overcoming resistance to anthracycline-based therapies in breast cancer.

Molecular analysis of time-dependent DNA and RNA degradation in bloodstains: differential stability of HBA and ALAS2 gene targets and its forensic implications - Rahat Bukhari; Rahat Abdul Rehman; Midhat Salman; Allah Rakha; Anam Munawar; Shahid Nazir; Muhammad Farhan Khan; Zunaira Batool (Molecular Biology Reports, 2026)

Transgene-free plant genome editing via viral delivery of miniature CRISPR-Cas12f - Muhammad Jawad Akbar Awan; Afzal Akram; Rubab Zahra Naqvi; Mariam Akhtar; Saqib Siddique; Muhammad Ismail Buzdar; Imran Amin; Shahid Mansoor (Functional & Integrative Genomics, 2026)

Association of MUC3A P258S mutation with advanced phase CML structural and in silico insights - Sameen Shahid; Zafar Iqbal; Muhammad Abbas Khokhar; Muhammad Farooq Sabar (Functional & Integrative Genomics, 2026)

Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Multiplexed CRISPR/Cas9 mediated knockdown of BCH gene in potato enhances beta-carotene to combat vitamin A deficiency - Ujala Nasir; Aneela Yasmeen; Muhammad Awais; Ayesha Latif; Allah Bakhsh; Nadeem Ahmad; Naila Shahid; Saira Azam; Abdul Qayyum Rao; Ahmad Ali Shahid (Plant Science, 2026)

Pathogen-induced physiological reprogramming and systemic dysfunction in plants - Mubashir Sharif; Muhammad Annas Shahid; Mahad Ur-Rehman; Ikhlas Shafique; Muhammad Farooq; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2026)

Stable isotopes and larger benthic foraminiferal response to the Paleocene-Eocene Thermal Maximum in the shallow-water carbonates of the Lower Indus Basin (Eastern Tethys, Pakistan) - Hafiz Shahid Hussain; April N. Abbott; Stefan C. Löhr; Muhammad Hanif; Sean T. Murray; Mohibullah Mohibullah; Mukhtiar Ghani (Journal of Asian Earth Sciences, 2026)

Geophysical and remote sensing insights into tectonics and mineralization of Hattian, Azad Jammu and Kashmir - Shahid Ahmed; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Khawaja Umair Majeed; Junaid Yousif (Journal of Applied Geophysics, 2026)

Strait of Hormuz disruption, geopolitical dispute intensity and Brent-based hedging effectiveness in European fuel markets: Empirical evidence from DCC-GARCH approach - Hafiz Muhammad Naveed; Huaping Sun; Muhammad Shahid; Rabia Akram; Zaiba Ali (Energy Policy, 2026)

Bacteriophage therapy for antimicrobial-resistant, biofilm‑associated diabetic foot infection: delivery routes, phage antibiotic synergy, and practical wound‑care integration - Muhammad Irbaz; Zunaira Hamood; Summayah Shahid; Afra Ghufran; Aamir Ajmal; Iqra Rafiq (Archives of Microbiology, 2026)

FruScab-E3Net: A Deep Learning Ensemble Framework for Scab Disease Detection and Classification in Fruits - Tamoor Khan; Sheeraz Akram; Arfan Jaffar; Muhammad Shahid Iqbal; Rashid Abbasi (Applied Fruit Science, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Uncovering the central role of GhSPL13 in vegetative growth, root architecture, and stress responses in cotton - Sahar Sadaqat; Muhammad Awais; Muhammad Saad bin Tahir; Ramsha Ajmal; Aneela Yasmeen; Saira Azam; Naila Shahid; Ayesha Latif; Allah Bakhsh; Ruhangiz Mammadova; Abdul Qayyum Rao (Plant Science, 2026)

Identification and functional verification of resistance genes against Lily bulb virus-1 (LbV-1) in Lilium: Insight from sRNA sequencing and transcriptomic profiling - Nisar Uddin; Xia Li; Noor Muhammad; Muhammad Shahid; Adil Hussain; Lili Zhang; Daochen Zhu (Plant Science, 2026)

Integrated sedimentological and petrographic constraints on early Himalayan foreland basin evolution, Sulaiman ranges, Pakistan - Muhammad Jehangir Khan; Shahid Ghazi; Xiaodong Yang; Syed Ahsan Hussain Gardezi; Mubashir Mehmood; Muhammad Aleem Zahid; Umair Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Mapping 50 Years of rainfall in Greater Kuala Lumpur: Developing a 1-km dataset for tropical urban climates - Nirwani Devi Miniandi; Mohamad Hidayat Jamal; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

A hybrid approach for COVID-19 detection: Combining Wasserstein GAN with transfer learning - Sumera Rounaq; Shahid Munir Shah; Mahmoud Aljawarneh; Ghulam Muhammad (Next Research, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Synergistic regulation of cadmium tolerance by a 2 C protein phosphatase and nano molybdenum by modulating cellular structure, metal transport, and redox homeostasis in polyploid rice - Muhammad Qasim Shahid; Zihang Lin; Lixia Sun; Zhen Li; Muhammad Farooq; Fozia Ghouri (Journal of Hazardous Materials, 2026)

Integrated experimental and computational insights into co-production of pectinase and xylanase from Aspergillus niger: Optimization, purification and molecular characterization - Nayya Waseem Dar; Muhammad Anjum Zia; Muhammad Shahid; Bushra Akhtar (Bioresource Technology Reports, 2026)

New Fossils of Bovids (Bovidae, Mammalia) from the Siwaliks of Pakistan - Muhammad Akbar Khan; Khalid Mahmood; Saba Naz; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mamoona Shahid (Geoheritage, 2026)

Titanium dioxide nanoparticles modulate soil bacterial communities to mitigate arsenic accumulation in contrasting maize varieties - Muhammad Ali Shah; Haseeb Ahmad; Shahid Ali; Kashif Khan; Rayyan Khan; Xi Zheng; Xun Bo Zhou (Applied Soil Ecology, 2026)

Editorial Expression of Concern: Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2026)

Single-ligation approach for construction of agroinfectious clone of single stranded DNA viruses - Muhammad Shafiq Shahid (Indian Phytopathology, 2026)

Chlorophyll fluorescence signatures reveal freezing tolerance differences among new Citrus scions - Carlos Eduardo Aucique-Perez; Nazneen Qureshi; Jhon Chater; Jude Grosser; Fred Gmitter; Zafar Iqbal; Muhammad Adnan Shahid (Theoretical and Experimental Plant Physiology, 2026)

Exploring Carissa spinarum as a therapeutic candidate: metabolite profiling and antimicrobial evaluation - Laiba Ali; Shahid Nawaz; Sikandar Ali; Asad Ur Rehman; Iram Liaqat; Shaukat Ali; Muhammad Nauman Aftab (Natural Product Research, 2026)

An Innovative conceptual framework to identify the potential sites for rainwater harvesting in arid regions - Muhammad Shahid; Muhammad Waseem; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel (Environment, Development and Sustainability, 2026)

Retraction notice to “A critical review of mercury speciation, bioavailability, toxicity and detoxification in soil-plant environment: Ecotoxicology and health risk assessment” [Sci. Total Environ. 711 (2020) 134749] - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Jochen Bundschuh; Nabeel Khan Niazi; Camille Dumat (Science of The Total Environment, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Coming of age for synergising multiple soil remediation strategies - Muhammad SHAHID; Jianxu WANG (Pedosphere, 2026)

Rice 2C protein phosphatase, OsNY1, and magnesium oxide positively regulate arsenic tolerance by root cells reinforcement, metals detoxification, and protein phosphorylation - Zihang Lin; Lixia Sun; Weiwei Xia; Zhen Li; Fozia Ghouri; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2026)

Energy-efficient pulsed photocatalysis with engineered biochar-ferrite nanocomposites for the reductive degradation of chlortoluron in water - Muhammad Imran; Behzad Murtaza; Muhammad Asif Naeem; Zia Ul Haq Khan; Jibran Iqbal; Muhammad Shahid; Long Li; Changseok Han (Journal of Environmental Management, 2026)

A comprehensive study on enhancing the quality attributes of vacuum freeze-dried mango through incorporating dietary fibre - Muhammad Shahid Zafar; Fei Liu; Ruyi Li; Shaodan Peng; Ali Mahmoud El-Badri; Mianhong Chen; Maria Batool; Yangyang Liu; Asif Ahmad; Wangfeng Hu; Jihua Li; Wei Zhou (Food Chemistry, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

A critical review of mercury in the soil–plant-air system: mercury transport and accumulation, plant response mechanisms, and mitigation strategies - Ying Xing; Zhi Yu; Muhammad Shahid; Reni Ustiatik; Jianxu Wang (Plant and Soil, 2026)

Methotrexate Loaded Polymeric Patches with Penetration Enhancers for Transdermal Delivery: in vitro, Ex Vivo, and in Vivo Characterization - Muhammad Shahid Latif; Asif Nawaz; Muhammad Khurshid Alam Shah; Muhammad Fareed; Muhammad Waseem Khan; Muhammad Luqman Nordin; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

Analyzing Household Biological Waste for Energy Efficiency: Advancement Towards Sustainable Energy - Dhaif Allah Ahmed Hadi; Jicheng Liu; Javed Akram; Shahid Ali; Song Yanan; Kathih Ahmed Ali Hadi; Muhammad Sajjad Hussain (Circular Economy and Sustainability, 2026)

Evaluation of Larvicidal Potential of Nepeta cataria and Cymbopogon nardus Essential Oils Against Aedes aegypti - Iqra Shafeeq; Sammina Mahmood; Adeel Sattar; Qamar Niaz; Mian Abdul Hafeez; Muhammad Ilyas; Muhammad Shahid Mahmood (Acta Parasitologica, 2026)

Integrated terrain analysis and SWAT-based modeling for assessing hydrological dynamics of the Upper Jhelum River Basin, Pakistan - Samavia Shahid; Muhammad Nasar-u-Minallah; Muhammad Saad; Muhammad Waqar; Mohamed Hassan Fathima Nuskiya (Acta Geophysica, 2026)

Molecular evidence of two begomoviruses and a novel DNA-B infecting Duranta erecta variegata in Pakistan - Afzal Akram; Mahnoor Jamil; Imran Amin; Jodi A. Scheffler; Brian E. Scheffler; Muhammad Saeed; Shahid Mansoor (Virus Genes, 2026)

Probiotics unveiled: bridging general health benefits to the era of precision medicine - Mati Ullah; Muhammad Rizwan; Muhammad Ihtesham Waheed; Muhammad Shoaib Alam; Sami Ullah Jan; Ali Raza; Muhammad Faisal Shahid; Vivian Andoh; Yong Chen (World Journal of Microbiology and Biotechnology, 2026)

Spatiotemporal dynamics of historical and future drought conditions over the Arabian Peninsula from ERA5 and CMIP6 data - Muhammad Haroon Siddiqui; Mazen E Assiri; Sajjad Saeed; Md Arfan Ali; Moutassem El Rafei; Shahad Bahamdan; Abdullah Masoud Alqahtani; Abdulrahman AlHaidari; Abdulrahman Alsalhi; Ohood Alzahrani; Shamsuddin Shahid (Journal of Earth System Science, 2026)

Entomocidal effect of green synthesized titanium dioxide nanoparticles using Aloe vera Extract against Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2026)

Eco-friendly tick control using Pakistani bee propolis: Behavioral and acaricidal effects against Rhipicephalus microplus and Hyalomma marginatum - Shahid Nazeer; Shahid Ullah Khan; Shamsheer Khan; Malik Muhammad Sohail Elahi; Syed Ishtiaq Anjum; Khalil ur Rehman; Ruoa Saleh Almahallawi; Amal Abdullah Aboras; Nada Ibrahim Alribdi; Umber Zaman (Veterinary Parasitology, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

Oxygen-regulated cascade fermentation to improve the quality of wet Spirulina by off-flavor mitigation, bioactivity enhancement, and coordinated control of biogenic amines - Kerui Su; Bingyu Shi; Anqi Zhao; Beixiao Zhang; Zhihao Fan; Muhammad Usman; Qi Wang; Xuejing Duan; Hanyu Dong; Ayesha Shahid; Jingliang Xu (International Journal of Food Microbiology, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Operational Performance of Packed-Bed Columns Using Mill-Scale Derived Fe3O4 for Efficient Arsenic Removal from Water - San Phearom; Muhammad Kashif Shahid; Minsoo Maeng; Sophal Hai; Huy Hangsak; Mam Sarith; Younggyun Choi (Water, Air, & Soil Pollution, 2026)

Extreme rainfall spatiotemporal trend based on modified Mann-Kendall test under multiple hypothesis testing for Rajang Basin in Sarawak, Malaysia - Zulfaqar Sa’adi; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid; Mohd Ridza Mohd Haniffah; Muhammad Hanifah Mazlan; Siti Aimi Asyarah Zakaria; Hesam Kamyab; Wan Anom Wan Aris; Ricky Anak Kemarau; Md Abdullah Al Mamun Hridoy; Khalid Qaraghuli (Theoretical and Applied Climatology, 2026)

The effects of vitamin D supplementation on inflammatory biomarkers: an umbrella study of meta-analysis on randomized controlled trials - Chou-Yi Hsu; Hassan Youssef Hussein; Karam Akram Al-akkam; Tushar B. Gajjar; Hamad AlMohamadi; Nodir Khonturaev; Sandeep Kumar Shukla; Safa Hussien Radhi; Aseel Smerat; Muhammad Shahid Iqbal (Inflammopharmacology, 2026)

Wheat Farming Dynamics in Pothohar: From Rainfed Practices to Irrigation Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
This study evaluated the dynamics of wheat yield and water productivity under various irrigation methods and farming practices in the rainfed‐to‐irrigated transitioning areas of the Pothohar region, Pakistan. Long‐term yield data (1981–2023) from the Pakistan Bureau of Statistics and farmers' field surveys were used to benchmark existing practices. The comparative performance of conventional flood irrigation (CF) and high‐efficiency irrigation systems (HEISs) was assessed through crop water productivity and simulated root‐zone water balance using the FAO AquaCrop model. The results revealed an average wheat yield of 1.34 ± 0.34 t ha −1 , showing 78% and 69% lower yields than the Punjab provincial and national averages. Irrigated areas (2.55 ± 0.29 t ha −1 ) yielded 96% more than rainfed areas (1.30 ± 0.33 t ha −1 ), underscoring the critical role of irrigation in enhancing productivity. HEIS reduced evaporation (14%) and drainage losses (17%), resulting in 18% higher water productivity (1.66 kg m −3 ) compared with CF (1.41 kg m −3 ). Root‐zone water balance analysis confirmed that HEIS improved soil moisture conservation and transpiration efficiency, making it a sustainable irrigation option for Pothohar's semi‐arid wheat systems. The study highlights inefficiencies in prevailing practices and the potential of HEIS to bridge yield gaps and improve water productivity in the region's transitioning agroecosystems.

Therapeutic targeting of COX-2 in head and neck cancer: Mechanistic and clinical perspectives - Reena Gupta; Bilal Khaleel Midhin; Sabir Ali Siddiqui; Mohammad Abohassan; Pareshkumar N. Patel; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Zainb A. Taleb (DARU Journal of Pharmaceutical Sciences, 2026)

Linking Agro‐Climatic Variability and Field Management to Wheat Yield in a Transition From Rainfed to Reservoir‐Fed Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Climate change poses increasing risks to wheat production in semiarid regions. This study examined long‐term climate trends, wheat yield variability and farmers' perceptions and adaptation in District Rawalpindi, Pakistan. Wheat‐season (November–April) climate data (1989–2019) were analysed alongside a survey of 175 farmers. The results showed a significant increase in T min (0.05°C year −1 , p = 0.03), whereas T max increased slightly but nonsignificantly. Rainfall showed a declining, nonsignificant trend. Wheat yield exhibited high interannual variability with a weak increasing trend. Regression analysis identified rainfall as a significant predictor of yield ( β = 0.002, p = 0.011), explaining 46% of yield variation, with a 1% increase in rainfall increasing yield by 0.34%. Farmers' perceptions aligned with observed trends, with most reporting declining rainfall (78%) and increasing drought frequency (70%). Perception was significantly associated with education and farming experience. Adaptation practices included improved varieties, line sowing and minimum tillage, whereas the adoption of advanced technologies remained limited. Key barriers included knowledge gaps (86%), limited access to technology, financial constraints and weak institutional support. The findings highlight rainfall variability as the primary driver of yield instability and emphasize the need for strengthened advisory services, technology access and institutional support to enhance adaptive capacity.

How Irrigation Systems and Tillage Regimes Shape Wheat Performance and Soil Water Balance in Semi‐Arid Pakistan: A Field–Modelling Approach - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Wheat productivity in semi‐arid regions is constrained by inefficient irrigation, suboptimal tillage and poor soil water management, leading to low yields and high nonproductive water losses. However, the combined effects of irrigation systems and tillage on the soil water balance remain insufficiently quantified under field conditions. This study evaluated the interactive effects of four irrigation–sowing systems—flat‐basin broadcast under flood irrigation (FBC), flat‐basin line sowing (FLC), narrow‐bed furrow irrigation (NLF) and wide‐bed drip irrigation (WLD)—and two tillage regimes (conventional tillage, CT; no‐tillage, NT) on wheat yield, water productivity and soil water balance in the Pothohar region of Pakistan using a randomized complete block design over two seasons (2023–2024 and 2024–2025). The results showed that WLD achieved the highest grain yield (up to 7.95 t ha −1 ), exceeding FBC by > 35% while reducing irrigation water use by 34%–43%. Raised‐bed systems (NLF and WLD) reduced deep percolation losses and improved soil water retention, whereas NT enhanced water productivity by > 30%. These results demonstrate that improved irrigation–sowing systems combined with no‐tillage enhance the soil water balance by reducing nonproductive losses and increasing productive water use, thereby improving wheat productivity under water‐limited conditions.

Harnessing Seawater for Algae-based Omega-3 Production: Microalgal Strain Improvement and Cultivation Strategies for Achieving Commercial Robustness - Hafiza Aroosa Malik; Mohammed Abdullah; Ayesha Shahid; Anqi Zhao; Alexei E. Solovchenko; Abdulrahman H. Alessa; Hussain Alqahtani; Munazza Gull; Raj Boopathy; Muhammad Aamer Mehmood; Jingliang Xu (Current Pollution Reports, 2026)

Next-generation thermal management systems for lithium-ion batteries: Enhancing the performance and safety in electric vehicles - Zahid Bashir; Riaz Hussain; Hafeez Khoharo; Jarrar Ali Jaffri; A.L. Saroj; Shahid Bashir; Jeyraj Selvaraj; Muhammad Shakeel Ahmad (Journal of Environmental Chemical Engineering, 2026)

Oryza rufipogon and diosgenin alleviate cadmium toxicity by limiting grain translocation in rice: Insights from molecular and physiological regulation mechanisms - Minghui Zhong; Zhen Li; Lixia Sun; Shafaqat Ali; Weiwei Xia; Jingwen Liu; Jiacheng Jin; Muhammad Qasim Shahid; Fozia Ghouri (Journal of Environmental Sciences, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Multimodal bioactivities and COX-2 targeted anti-inflammatory mechanism of enzyme-assisted ultrasonic extracted capsicum and zingiber oleoresins: An integrated computational and experimental study - Muhammad Adeel Razzaq; Muhammad Shahid; Zahid Mushtaq; Bushra Akhtar (Food Bioscience, 2026)

Retraction notice to “Dual Z-scheme core-shell PANI-CeO2-Fe2O3-NiO heterostructured nanocomposite for dyes remediation under sunlight and bacterial disinfection” [Environ. Res. 215 (2022) 114140] - Faisal Mukhtar; Tauseef Munawar; Muhammad Shahid Nadeem; Muhammad Naveed ur Rehman; Shoukat Alim Khan; Muammer Koc; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Research, 2026)

Circular valorization of agricultural, industrial, and post-consumer waste into fiber-reinforced composites for environmental sustainability - Muhammad Usman Shahid; Muhammad Noman Shahid; Zulfiqar Ahmad; Hafiz Muhammad Abdullah; Muhammad Muzammil Azad (Environmental Research, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Retraction notice to “Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants” [Environ. Res. 251 (2024) 118675] - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2026)

Beyond insects: High sensitivity of the water fleas to insecticides and implications for ecotoxicological assessment - Tan-Duc Nguyen; Yu-Chen Huang; Thanh Luu Pham; Vu Anh Le; Vinh Quang Tran; Thanh-Son Dao; Marina Arias; Quan Zhang; Yingying Liu; Qian-Mei Luo; Muhammad Shahid Iqbal; Qiong Wu; et al. (Environmental Toxicology and Pharmacology, 2026)

Silver-decorated ZnO nanorods for sunlight-assisted photocatalytic degradation of ciprofloxacin, methyl orange, and 2,4-dinitrophenol in water - Iqra Mazhar; Muhammad Afzaal; Muhammad Altaf; Manzar Sohail; Raja Shahid Ashraf; Abdul-Sattar Nizami (Nanotechnology for Environmental Engineering, 2026)

Kaempferol-loaded solid lipid nanoparticles attenuate cartilage degradation and inflammation by modulating the expression of pro and inflammatory cytokines, MMP-13 and oxidative stress markers in adjuvant induced arthritic rats - Anam Niamat; Aftab Ahmad; Nayla Munawar; Muhammad Shahid; Bushra Akhtar (Inflammopharmacology, 2026)

Boosting Sustainability: Integrating Green Practices With the Circular Economy - Abdul Rehman; Muhammad Ibrahim Shahid; Sajjad Ahmad Baig; Fariha Fatima (Circular Economy and Sustainability, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

AcrAB-NodT overexpression drives envelope destabilization and metal sensitivity in Caulobacter vibrioides - Muhammad Shahid Mehmood; Yohana Amos; Muhammad Ali Abid; Ali Shan Hafeez; Naseeb Danaf (Archives of Microbiology, 2026)

Genome-Wide Identification of Bax Inhibitor (BI) Gene in Potato (Solanum tuberosum) and Response During Begomovirus Infection - Saman Shahid; Riffat Siddique; Muhammad Shafiq; Heba I. Mohamed (American Journal of Potato Research, 2026)

Adsorptive removal of methylene blue from wastewater using sawdust of Cedrus deodara and its composite with iron oxide nanoparticles: a comparative study - Muhammad Shakeel; Shahid Ali; Muhammad Waseem; Bisma Liaqat; Mahnoor Aurangzeb; Aina Noor; Saira Bibi; Uzma Iqbal; Mehmood-ul-Hassan (Environmental Science and Pollution Research, 2026)

Trade adjusted carbon emissions and renewable energy electricity output: Evidence from method of moment quantile regression for N-11 economies - Maaz Amin; Salman Wahab; Bilal Ahmed; Muhammad Imran; Shahid Ali; Sakiru Adebola Solarin (Environment, Development and Sustainability, 2026)

Application of advanced oxidation processes for remediation of rubber industry wastewater: a comprehensive review - Zafran Ullah; Zhen-Yu Tian; Collin G. Joseph; Sabine Neusatz Guilhen; Siow Hwa Teo; Jualang Azlan Gansau; Rosalam Sarbatly; Kartini Alias; Pretibaa Subhramaniyun; Muhammad Naeem Khan; Muhammad Shahid Iqbal (Environmental Science and Pollution Research, 2026)

Hypoxia adaptation in yak: Molecular, Genetic, and Physiological mechanisms of high-altitude resilience - Muhammad Wasique Shahid; Hammad Qaiser; Tanveer Hussain (Livestock Science, 2026)

Bacillus subtilis enhances maize yield by restricting cadmium translocation and modulating ion homeostasis - Haseeb Ahmad; Jiu Yang Mao; Rayyan Khan; Muhammad Ali Shah; Kashif Khan; Muhammad Asad Naseer; Shahid Ali; Rida Rashid; Rui He; Xun Bo Zhou (Journal of Environmental Sciences, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Transition metal (MnCoCuFeCe) based high-entropy oxides catalysts derived from LDH for promoting low-temperature C3H6-SCR reactivity - Sameer Shahid; Yaxin Su; Jacob Senior Atta Owusu; Muhammad Waqar Talib; Huqin Zheng; Wenyi Deng; Bingtao Zhao; Jarosław Zuwała (Fuel, 2026)

Impact of drying temperature-induced protein conformational changes on the regulation of intermolecular interactions and gelation in pea starch-Spirulina composite gel - Kerui Su; Bingyu Shi; Anqi Zhao; Beixiao Zhang; Zhihao Fan; Muhammad Usman; Qi Wang; Xuejing Duan; Hanyu Dong; Ayesha Shahid; Jingliang Xu (Carbohydrate Polymers, 2026)

Evaluating statistical and machine learning bias-correction methods for CMIP6 rainfall projections in a tropical megacity - Nirwani Devi Miniandi; Mohamad Hidayat Jamal; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2026)

Experimental Validation and Computational Deconstruction of Downstream Mutations in MIR5195: Integrating Whole-Exome Sequencing, Structural Dynamics, and Molecular Docking to Decipher Transcriptional Reprogramming in CML - Sameen Shahid; Muhammad Farooq Sabar; Zafar Iqbal (Cell Biochemistry and Biophysics, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

A weighted ensemble DL framework for granular RPV inventory and energy yield analysis in Pakistan - Muhammad Kamran Lodhi; Yumin Tan; Yang Li; Faisal Mumtaz; Shahid Naeem (Remote Sensing Applications: Society and Environment, 2026)

Key metabolic and proteolytic pathways contributing to cadmium tolerance in soybean - Shahid Ali; Hao Yun Liang; Muhammad Ali Shah; Haseeb Ahmad; Yu Xin Chi; Kashif Khan; Xun Bo Zhou (Plant Science, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Valorization of pongamia pinnata (sukhchain) seed oil for sustainable biodiesel production via Na2O/MgFe2O4 catalyst: kinetics, thermodynamic and cost estimation analysis - Ihtisham Wali Khan; Muhammad Shahid; Muhammad Farooq; Abdul Naeem; Yinhai Su; Najm Us Saqib; Fouzia Perveen; Imran Ullah (Biomass and Bioenergy, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Physiological role of light modulation on poultry production, reproductions and welfare: a-systematic review - Yufei Huang; Nisar Ahmed Ujjan; Shahid Faraz Syed; Jameel Ahmed Buzdar; Fethi Ahmet Ozdemir; Muhammad Asif Arain (Veterinary Research Communications, 2026)

Micromorphological assessment of pollen and foliar epidermal traits in Solanaceae using SEM characterization - Mehral Azhar; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Muhammad Rizwan Khan; Khuzin Dinislam; Nigar Mursal; Amna Shahid; Enkelejda Kucaj (The Science of Nature, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Molecular mechanisms of heavy metal uptake, accumulation, and tolerance in sweet potato (Ipomoea batatas): implications for phytoremediation and food safety - Muhammad Shahid; Muhammad Mohsin Altaf; Muhammad Ahsan Altaf; Rafiq Ahmad; Kashif Khan; Cheng-cheng Si (Plant and Soil, 2026)

Genetic and epigenetic mechanisms underlying cadmium (Cd) stress responses in soybean cultivars - Shahid Ali; Ya Huang; Rayan Khan; Kashif Khan; Yu Xin Chi; Muhammad Ali Shah; Muhammad Asad Naseer; Haseeb Ahmad; Wen Jie Chen; Xun Bo Zhou (Plant Cell Reports, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Impact of heat stress on outdoor labor productivity in peninsular malaysia: a spatio-temporal assessment - Najeebullah Khan; Rajab Houmsi; Muhammad Shazril I. Ibrahim; Shamsuddin Shahid (Natural Hazards, 2026)

Myoinositol-mediated regulation of leaf physiology, biochemistry, and water relations confers heat stress tolerance in Quinoa - Rashid Iqbal; Muhammad Sarwar; Basharat Ali; Muhammad Farrukh Saleem; Hassaan Ahmad; Muhammad Shahid; Javed Iqbal; Khairiah Mubarak Alwutayd; Dilfuza Jabborova; Sajad Ali; Ghulam Murtaza (Plant Biosystems, 2026)

Spirulina supplementation and human health: An umbrella review of meta-analysis on randomized controlled trials - Nazila Soufi Amlashi; Fahad Rajab Mahmood; Mirza R. Baig; Tina Saeed Basunduwah; Pareshkumar N. Patel; Gulsara Ruziyeva; Gunjan Singh; Muhammad Shahid Iqbal; Munthar Kadhem; Amirali Ebrahimi (Algal Research, 2026)

mcr gene family evolution and structural mechanisms of colistin resistance: from mcr-1 to emerging variants - Muhammad Shahid Mehmood; Uthpala Kavindi Rupasinghe Koggala Marakkalage; Tabish Arif; Fariha Javaid; Muhammad Ali Abid; Muntha Shahid; Anwar Parvez; Muhammad Nabeel Saddique; Sultan Ali (Archives of Microbiology, 2026)

Distribution and Occurrence of Microplastics in Foliar Deposition Across Tree Species in Lahore - Muhammad Shahid; Sidra Farooq; Rahib Hussain; Tahir Sattar; Abdul Qadir (Archives of Environmental Contamination and Toxicology, 2026)

Spawning and developmental biology of vulnerable catfish, Wallago attu : Implications for quality seed production and stock replenishment - Saeed Akram Khan; Muhammad Khalil Ahmad Khan; Shahid Sherzada (Journal of Fish Biology, 2026)
Freshwater catfish, Wallago attu , is a popular fish species due to its excellent taste and low quantity of intramuscular bones. Scientific and evidence‐based studies on the embryonic and larval development of this vulnerable fish species are limited. We attempted artificial breeding using Ovaprim, and photographs of the embryological events were taken, revealing each stage of early development. For this, a sequence of microscopic analysis was performed using a trinocular digital microscope. Time‐lapse imaging was also performed to calculate the duration of each developmental stage. The eggs were spherical, and highly adhesive, with a diameter of 1.74 ± 0.11 in T1 and T2, 1.86 ± 0.17 and 1.8 ± 0.16 in T3 and T4, respectively. Hatching occurred at 979.33 ± 5.13, 973 ± 21.07, 981.67 ± 11.93 and 969 ± 7.21 min post‐fertilization (mpf) in T1, T2, T3 and T4, respectively. During embryonic development, the blastodisc appeared at 55.33 ± 4.04 (T1), 54.67 ± 5.13 (T2), 58.33 ± 3.79 (T3) and 58.33 ± 3.51 (T4). First cleavage appeared at 64.33 ± 2.08 (T1), 63.67 ± 5.03 (T2), 68 ± 1 (T3) and 66 ± 4.36 (T4) mpf, resulting in two equal blastomeres. Embryonic body movements started at 652 mpf. Free body embryonic development (ranging from the two‐cell to the pre‐hatching stage) took 810 mpf. Hatching occurred at 979.33 ± 5.13 (T1), 973 ± 21.07 (T2), 981.67 ± 11.93(T3) and 969 ± 7.21(T4) mpf, with average larval lengths of 4.88 ± 0.19 (T1), 5 ± 0.16 (T2), 4.88 ± 0.19 (T3) and 4.88 ± 0.28 (T4) mm. Such information will have significant implications on conservation and sustainable seed production of this species. The findings of this study will contribute to the advancement of W. attu aquaculture by providing valuable insights into quality seed production and stock replenishment.

Mapping Diurnal Heat Stress in Nigeria: Spatial and Temporal Changes Over Seven Decades - Mohammed Abdu Nasara; Najeebullah Khan; Mohd Khairul Idlan Muhammad; Amyrhul Abu Bakar; Mohd Ridza Mohd Haniffah; Shamsuddin Shahid (International Journal of Climatology, 2026)
While thermal stress risks are global, Sahelian Africa's localised impacts remain understudied despite rapidly intensifying heat exposure. Climate hazards associated with human thermal stress present considerable challenges to Nigeria's public health and socio‐economic activities, with effects intensified by the nation's heterogeneous climatic characteristics. This research examines the spatial and temporal variability of heat stress in Nigeria from 1950 to 2023. WBGT was selected as the core indicator due to its strong relevance in humid climates and its ability to incorporate metabolic and radiative heat load. Hourly wet‐bulb globe temperature (WBGT) data were derived from 0.1° × 0.1° ERA5‐Land hourly reanalysis datasets using the Liljegren method and subsequently analysed for significant trends using the Mann–Kendall trend test. The results showed that Nigeria's annual mean of daily peak WBGT varies from 24°C in the south to above 28°C in the north. Over the 74‐year period, WBGT increased by approximately 1.2°C in northern Nigeria and by about 0.8°C–1.0°C in the southern regions, with northern regions showing the strongest trends (~0.20°C/decade). The late period (1987–2023) consistently exhibited higher WBGT values than the early period (1950–1986), with increases most pronounced during early morning and late evening hours. Late‐period WBGT values increased across all zones by 0.8°C–1.2°C from September to November, with the largest shifts in southern Nigeria during March–May. These rising WBGT levels have direct implications for public health, outdoor labour productivity and climate adaptation planning—potentially reducing agricultural and construction sector labour capacity by 10%–15% during peak heat months under current thresholds. The day and nighttime variability of WBGT decreased from north to south. These findings underscore urgent needs for improved urban planning (e.g., heat‐resilient infrastructure, shading, ventilation) and stronger rural health access systems to manage growing heat‐related risks. Overall, the study highlights escalating nationwide heat stress and calls for targeted adaptation strategies, including early‐warning systems, expansion of cooling access, occupational heat‐safety guidelines and heat‐sensitive urban and agricultural planning.

Understanding the genetics of cotton regeneration to help improve cotton - Zujun Yin; Muhammad Jawad Akbar Awan; Shahid Mansoor (Trends in Plant Science, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Experimental and predictive advancements in hydrogen enriched compressed natural gas spark ignition engines: a critical review - Muhammad Farhan; Hamza Ahmad Salam; Muhammad Ihsan Shahid; Tianhao Chen; Qiuhong Xiao; Long Jiang; Anas Rao; Xin Li; Fanhua Ma (Fuel, 2026)

Can global energy transition be possible with intergenerational equity in climate efforts? - Muhammad Shahid Siddiqui (Environmental Impact Assessment Review, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Mapping agricultural drought hotspots in Pakistan: a remote sensing-based climate–vegetation nexus - Wisal Khan; Mohamad Hidayat Bin Jamal; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2026)

Polyploidy and zinc nanoparticles enhanced cadmium tolerance by regulating antioxidants and transport proteins - Jingwen Liu; Fozia Ghouri; Lixia Sun; Zihang Lin; Minghui Zhong; Muhammad Farooq; Muhammad Qasim Shahid (Plant Cell Reports, 2026)

Efficacy and safety of lorundrostat in uncontrolled hypertension: A GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Shree Rath; Javeria Javed; Akif Shahid Khan; Abdul Moiz; Muhammad Ansab; Alishba Hameed; Zaryab Bacha; Zarar Ahmad Khan Afridi; Khushal Khan; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Chitosan Mitigates Heat Stress in BT Cotton by Activating Antioxidant Defense System and Improving Water Relations - Abdul Shakoor; Muhammad Farrukh Saleem; Muhammad Zia Ul Haq; Muhammad Shahbaz Farooq; Muhammad Shahid (International Journal of Plant Production, 2026)

Bukiniczia cabulica (Boiss.) Lincz. ameliorate diabetes-induced neuropathy: analgesic, anti-diabetic and anti-neuropathic using enzyme inhibitory, molecular docking and in-vivo studies - Zeeshan Ahmad; Mushtaq Ahmad Mir; Muhammad Shahid; Nasreena Bashir; Alam Zeb; Mehreen Ghufran; Falak Naz; Muhammad Ayaz (Inflammopharmacology, 2026)

Glutathione role in improving leaf physiology, yield and quality of rice (Oryza sativa L.) under high temperature stress at flowering stage - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Awais Arshad; Muhammad Shahid; Amina Rashid (Cereal Research Communications, 2026)

Decadal air quality dynamics in the Yangtze River Delta: Evidence from machine learning–driven analysis - Shah Zaib; Muhammad Zeeshaan Shahid; Imran Shahid (Air Quality, Atmosphere & Health, 2026)

Modeling the interplay of cultivars, irrigation regimes, and planting dates for optimizing cotton productivity in core and non-core cotton areas of Pakistan - Raheel Osman; Muhammad Shahid Iqbal; Zareen Sarfraz; Abid Mahmood; Muhammad Rafiq Shahid; Til Feike; Lin Wang; Shenglei Fu; Syed Tahir Ata-Ul-Karim (Computers and Electronics in Agriculture, 2026)

Synergistic effects in FeP4-NPC-CP Nanocomposites electrocatalysts for Boosted nitrate reduction to ammonia - Ya-Fei Guo; Sajid Mahmood; Anum Bilal; Ali Bahadur; Shahid Iqbal; Ali Hussain; Muhammad Sajjad; Syed Kashif Ali; Salah Knani (Fuel, 2026)

Structural and computational analysis of monkeypox virus methyltransferase: dynamic inhibition mechanisms and their implications for antiviral design - Muhammad Waqas; Syed Ahsan Shahid; Muhammad Shahab; Yongkun Zhu; Aamir Fahira; Zunnan Huang (Molecular Diversity, 2026)

Enhancing Lodging Resistance in Rapeseed Strategies for Sustainable Agriculture and Yield Improvement - Shahid Ullah Khan; Umer Mahmood; Muhammad Sirab Khan; Minchao Qian; Shengting Li; Osama Alam; Yonghai Fan; Hui Wang; Wei Chang; Hameed Gul; Shah Fahad; Kun Lu (Journal of Plant Growth Regulation, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Quantifying key drivers of atmospheric methane across Pakistan using a machine learning approach - Farzana Altaf; Toqeer Muhammad; Shahid Nadeem; Asif Sajjad; Mazhar Iqbal (Environmental Monitoring and Assessment, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Experimental insights on CIRLEM: Enhancing energy efficiency and flexibility in buildings - Mohammad Hosseini; Panayiotis Papadopoulos; Muhammad Salman Shahid; Kavan Javanroodi; Silvia Erba; Etta Grover-silva; Peter Riederer; Amin Moazami; Frederic Wurtz; Benoit Delinchant; Salvatore Carlucci; Mohammadreza Aghaei; et al. (Energy and Buildings, 2026)

Projected bioclimatic shifts in Pakistan: A CMIP6 ensemble analysis under shared socioeconomic pathways - Wisal Khan; Mohamad Hidayat bin Jamal; Mohd Khairul Idlan Muhammad; Najeebullah Khan; Shamsuddin Shahid (Theoretical and Applied Climatology, 2026)

Comparison of various heat stress indices for spatial representation of human thermal discomfort events in Nigeria - Mohammed Abdu Nasara; Ibrahim Mohammed Lawal; Najeebullah Khan; Amyrhul Abu Bakar; Ahmed Hussaini Jagaba; Labib Sharrar; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2026)
Nigeria is experiencing rising temperatures, frequent heat extremes, and increasing exposure to thermal stress. This study is the first to offer a comprehensive, long-term (1950–2023), and spatially comparative analysis of heat stress in Nigeria using four globally recognized thermal indices, Humidex (HD), Normal Effective Temperature (NET), Wet Bulb Globe Temperature (WBGTs), and Universal Thermal Climate Index (UTCI), enabling a more nuanced understanding of regional and index-specific sensitivities to heat extremes across diverse climatic zones. Heatwave events were analyzed based on durations (1-day, 3-day, and 5-day) and periods (daytime, nighttime, and 24-hour mean) for four stress categories: moderate, strong, severe, and extreme. Findings reveal significant variations in heat stress frequency across indices, regions, and event durations. NET consistently recorded the highest number of heat stress events, particularly in northern and highland areas, highlighting its sensitivity to topographical influences. For 1-day nighttime events, NET identified up to 40 strong occurrences in southern Nigeria, while WBGTs recorded over 25 moderate cases in both regions. In consecutive 3-day events, NET reported up to 20 severe cases in northern and southern Nigeria, while WBGTs captured up to 16 extreme daytime events. For prolonged 5-day heatwaves, NET and WBGTs detected up to 12 extreme events, underscoring their responsiveness to extended heat exposure. Conversely, UTCI remained the most conservative for all durations, reflecting its strict physiological threshold. Regional analysis confirms that northern Nigeria experiences a higher frequency of severe and extreme heat stress due to its arid climate and prolonged exposure to solar radiation. Additionally, highland regions, such as Mambila and Plateau, consistently reported elevated event counts by NET and UTCI, demonstrating their effectiveness in capturing microclimatic variations. These results highlight the growing prevalence of heat stress events across Nigeria and the need for tailored heat risk assessments.

Recombination hotspots and genetic variability in foot-and-mouth disease virus genomes: a comparative genomic and phylogeographic analysis - Shahid Hussain; Zixiao Jiang; Hasnain Israr; Jadoon Khan; Muhammad Nasir Riaz; Ijaz Ali; Chengjun Wu; Pir Tariq Shah (Archives of Virology, 2026)

Novel efficacy of pregnane and flavonoid glycosides from Desmidorchis flava in in vivo nociceptive and inflammatory paradigms and their target prediction by cheminformatics approach - Ajmal Khan; Hamdy Kashtoh; Najeeb Ur Rehman; Muhammad Shahid; Irfan Ullah; Asaad Khalid; Afnan Jan; Sobia Ahsan Halim; Kwang-Hyun Baek; Ahmed Al-Harrasi (Natural Product Research, 2025)

High‐Resolution Projections of Urban Heat Island Intensity in Greater Kuala Lumpur Using Machine Learning and CMIP6 GCMs - Nirwani Devi Miniandi; Mohamad Hidayat Jamal; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (International Journal of Climatology, 2025)
Urbanisation has significantly intensified the urban heat island (UHI) effect, particularly in rapidly growing cities like Kuala Lumpur. This study develops 1‐km resolution projections of land surface temperature (LST) using a machine learning‐based downscaling approach that integrates CMIP6 global climate model (GCM) simulations with urbanisation projections under different shared socioeconomic pathways (SSPs). A random forest (RF) model was trained on 1‐km resolution MODIS LST data and urbanisation ratio datasets to estimate GCM‐simulated Earth skin temperature ( T s ) biases. The trained model was then applied to future urbanisation scenarios to project LST anomalies from 2030 to 2090. The analysis revealed a strong positive correlation of 0.785 between the urbanisation ratio and LST anomalies. The RF model accurately predicted LST anomalies with a root mean square error of 1.63°C and a Kling‐Gupta Efficiency of 0.76. The future projections of LST using the multimodel mean of all GCMs revealed an increase in average LST in Kuala Lumpur from 0.7°C (CI: 0.4°C–0.7°C) for SSP1‐2.6 to 1.3°C (CI: 1.2°C–2.9°C) for SSP5‐8.5. The projections of UHI showed an increase ranging from 1°C to 1.9°C for SSP1‐2.6 and from 2.5°C to 3°C for SSP5‐8.5 by 2090 compared to 2030. The results also highlight spatial heterogeneity in UHI expansion, with central urban zones experiencing the most significant warming. This study emphasises the necessity of integrating urban planning strategies, such as increased green spaces, improved urban design, and heat mitigation policies, to address the rising urban temperatures.

Assessment of Growth, Chemical Composition, and Antioxidative Capacity of Coho Salmon (Oncorhynchus kisutch) Alevins Fed Dietary Vitamin A Under Controlled Conditions - Leyong Yu; Hairui Yu; Abdur Rahman; Govindharajan Sattanathan; Han Zhang; Lingyao Li; Shahid Sherzada; Mehnoor Sameer; Muhammad Younus (Fishes, 2025)
Vitamin A (VA) is an essential micronutrient that improves growth, immune activity, and antioxidant responses in fish. This study focuses on optimizing VA dietary levels for Oncorhynchus kisutch (Coho salmon) alevins. A 12-week trial was conducted using seven diets containing graded dietary VA levels of 244, 957, 1902, 3494, 6906, 10,248, and 25,213 IU/kg. A total of 2100 fish were reared in 21 tanks; 100 fish were housed in each tank, and 3 tanks represented one treatment. Peak (SGR) and FBW were observed at 6906 IU/kg. Excess VA levels (>15,000 IU/kg) compromised feed conversion efficacy and led to oxidative stress. Analysis of proximate composition resulted in protein and lipid deposition at optimal VA levels. However, excess may have led to metabolic disturbances and reduced ash content. The activity of the antioxidant enzymes catalase (CA), acid phosphatase (ACP), alkaline phosphatase (AKP), and total superoxide dismutase (T-SOD) revealed biphasic patterns, peaking at 6906 IU/kg and dropping when VA levels were exceeded, inducing pro-oxidant effects. Malondialdehyde (MDA), the indicator of toxicity, had a minimal value of 15,000 IU/kg. VA accumulation in the liver showed a dose-dependent relationship, while excess storage (>25,000 IU/kg) induced hepatotoxicity. Quadratic regression was used to identify the optimum VA levels required in Coho salmon alevins, ranging from 6906 to 10,248 IU/kg. Polynomial quadratic regression results indicated that the predicted dietary inclusion of VA at 3000 IU/kg and 15,000 IU/kg may yield better results of T-SOD and MDA. Real-world experimentation is recommended to explore long-term VA optimization with other nutrients and promote better feed utilization and sustainable aquaculture practices.

Starvation-induced metabolic adaptations in immobilized Desertifilum tharense BERC-3 for improved nutrient recovery from swine wastewater - Muhammad Usman; Md. Asraful Alam; Kerui Su; Anqi Zhao; Muhammad Aamer Mehmood; Zhang Beixiao; Ayesha Shahid; A.E. Solovchenko; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Mining-impacted stream condition (MISC): A framework for evaluating heavy metal impacts from historical gold mining in Victoria, Australia - Mokhinabonu Mardonova; Muhammad Kashif Shahid; Rouzbeh Abbassi; Bandita Mainali (Journal of Environmental Management, 2025)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Analysis of exhaust heat recovery and hydrogen production by steam methane reforming under different operating conditions of the HCNG engine - Muhammad Ihsan Shahid; Muhammad Farhan; Anas Rao; Muhammad Saddam Hussain; Xianlei Zhu; Hamza Ahmad Salam; Tianhao Chen; Xin Li; Fanhua Ma (Fuel, 2025)

Nutritional, pharmaceutical, and health benefits of sunflower seeds (Helianthus annuus L.): A comprehensive review of food applications - Salah Laaraj; Ashiq Hussain; Emaan Shahid; Fozia Bakhtawar; Muhammad Zia; Ayesha Najam; Nabeela Zulfiqar; Sherouk Hussein Sweilam; Abdelaziz Ed-Dra; Kaoutar Elfazazi (Food and Humanity, 2025)

Valorization of fruit and vegetable by-products for protein extraction and their functional applications in food and non-food sectors - Laiba Khalid; Ifrah Jabeen; Tanveer Ahmad; Muhammad Inam-ur-Raheem; Arashi Shahid; Teresa Cirillo; Francesco Esposito (Food and Bioproducts Processing, 2025)

Sacrificial agent-free H2O2 production driven by S-scheme photocatalysis over hierarchical ZnO/UiO-66-NH2 heterojunction - Muhammad Adnan Qaiser; Jinhe Li; Wei Ren; Shahid Khan; Syed Bilal Ahmed; Waqar Ahmad Qureshi; Mohamed Hussein Abdurahman; Weikang Wang; Qinqin Liu (Chemical Engineering Journal, 2025)

Effect of okra polysaccharides extract powder on mixolab attributes, physicochemical characteristics and in-vitro starch digestibility of wheat bread - Mehak Fatima; Allah Rakha; Muhammad Saeed; Muhammad Shahid; Filip Van Bockstaele (Bioactive Carbohydrates and Dietary Fibre, 2025)

Synergistic Sustainable Strategies for Microplastic Pollution Eradication by Hedgehog − Shaped Polyoxometalate − Ionic Liquids Supported Magnetic Biochar - Hameed Ullah; Tahani Rahil Aldhafeeri; Inas A. Ahmed; Khurram Shahzad Munawar; Shahid Hussain; Nadeem Nawaz; Uzma Saleem; Muhammad Sohail; Hafiz Muhammad Asif (Water, Air, & Soil Pollution, 2025)

Morpho-Biochemical and SSR Marker-Based Genetic Diversity Assessment in Fig (Ficus carica) Genotypes - Muhammad Shahid Mumtaz; Muhammad Nafees; Ishtiaq Ahmad; Maryam; Adel A. Rezk; Jian Huang; Rashid Iqbal (Plant Molecular Biology Reporter, 2025)

Circular RNAs MTO1 and ZNF292 as potential diagnostic biomarkers in HIV patients treated with antiretroviral therapy - Mahnoor Fatima; Muhammad Shahid; Iram Amin; Hasnain Javed (Molecular Biology Reports, 2025)

Engineering high yield basmati rice by editing multiple negative regulators of yield - Muhammad Abu Bakar Waqas; Muhammad Jawad Akbar Awan; Imran Amin; Muhammad Arif; Zahid Mukhtar; Shahid Mansoor (Molecular Biology Reports, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Deep Learning Ensemble and Multi-Criteria GIS for High-Fidelity Rooftop Solar Potential Mapping - Muhammad Kamran Lodhi; Yumin Tan; Yang Li; Muhammad Nouman Khan; Shahid Naeem (Journal of Geovisualization and Spatial Analysis, 2025)
Accurately mapping urban rooftop solar potential is essential for cities like Amsterdam that are pursuing net-zero emissions. This study presents an innovative framework that combines high-resolution geospatial data with an advanced deep learning ensemble to identify existing solar panels and untapped suitable rooftop areas. The predictions from a meticulously trained ensemble of deep learning models were integrated using both simple and performance-weighted majority voting. The weighted ensemble achieved an accuracy of 0.95, an F1 score of 0.91, and a Matthews correlation coefficient of 0.88, outperforming individual models. Rooftop suitability was assessed using a multi-criteria approach, which incorporated a high-resolution digital surface model (DSM) to derive slope, aspect, and solar irradiation. A novel solar irradiation model was developed that enhanced the precision of yield estimates by adjusting atmospheric transmissivity and diffuse fraction based on monthly cloud cover data from Amsterdam. This framework provides district-wise spatiotemporal solar irradiation and photovoltaic yield estimates. Based on our model estimates, current installations have a potential of 140 GWh annually, while there is a significant untapped potential of 1276 GWh on suitable rooftops. These detailed insights can help urban planners optimize solar energy deployment and support the city’s carbon neutrality goal by 2050. Graphical Abstract

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Salinity‐induced variations in growth performance, stress biomarkers and biochemical profiles of striped catfish ( Pangasianodon hypophthalmus , Sauvage, 1878) - Muhammad Nouman Riaz; Muhammad Hafeez‐ur‐Rehman; Hamda Azmat; Shahid Mehmood (Journal of Fish Biology, 2025)
Environmental salinity affects the growth, survival rate and physiological functions of fish. In this study, the effects of salinity stress on Pangasianodon hypophthalmus (Sauvage, 1878) fingerlings were examined over a 90‐day period. After acclimatization, a total of 300 P. hypophthalmus fingerlings were randomly assigned into three replicates and divided into five treatment groups with salinity levels of 0‰, 6‰, 12‰, 18‰, and 24‰ and with a stocking density of 20 fish per aquarium. After 90 days, the final weight, weight gain, weight gain percentage and specific growth rate significantly ( p p p p p p p p p p P. hypophthalmus in inland saline groundwater is 12‰, which ensures the maximum survival rate.

FinTech, environmental innovation, and social capital drive environmental and economic development in Asia - Yun Li; Muhammad Naeem Shahid; Muhammad Umar Islam; Muhammad Ishtiaq; Falak Sher (Environment, Development and Sustainability, 2025)

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Spatiotemporal heterogeneity of evapotranspiration controlling factors and their trends in Pakistan - Najeebullah Khan; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Salah ud Din; Zulhilmi Ismail; Shamsuddin Shahid (Acta Geophysica, 2025)
Effective climate change mitigation planning in the water and agriculture sectors necessitates a thorough understanding of trends in potential evapotranspiration (ETp) and its driving factors. This study quantitatively assessed the impact of varying meteorological conditions on ETp across Pakistan. We deciphered the dynamics of recent ETp shifts by analyzing trends in meteorological variables using Princeton Global Meteorological Forcing data (daily maximum and minimum temperatures, wind speed, solar radiation, and relative humidity) at 0.25° resolution. Sobol's sensitivity analysis quantified the influence of each climatic variable on ETp. Nonparametric statistical tests identified trends in ETp and its influencing factors. Our findings reveal wind speed as the most critical element controlling ETp across all seasons in Pakistan, followed by solar radiation and temperature. Daily ETp exhibited increasing trends in the north, west, and east, ranging from 0.05 to 0.4 mm/decade. This rise in ETp can be primarily attributed to increasing temperatures, while other parameters like wind speed and solar radiation remained relatively constant. These results suggest that continued global warming-driven ETp increases may pose significant challenges for Pakistan's water supply and agricultural irrigation systems.

Harnessing metal-organic frameworks (MOFs) in agriculture: Mechanisms and application strategies for management of plant diseases - Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Yumna Rasheed; Faizah Amer Altihani; Mohamed Hashem; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2025)

Occurrence and molecular characterization of root-knot nematodes on tunnel-grown cucumber (Cucumis sativus) in Balochistan province of Pakistan - Syed Shams Ullah; Amjad Abbas; Muhammad Dildar Gogi; Shahid Siddique; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Submergence stress in plants: molecular mechanisms, physiological changes, and adaptive responses - Noreen Iftikhar; Muhammad Saad Bhutta; Narmeen Tariq Zaman; Ayesha Khalid; Ayesha Latif; Saira Azam; Naila Shahid; Aneela Yasmeen; Abdul Qayyum Rao (Physiology and Molecular Biology of Plants, 2025)

Characterization of ambient air quality and its relationship with respiratory morbidity in typical cities of Northwest China (NWC) - Shah Zaib; Jianjiang Lu; Gao Yan; Xiaowen Yin; Xiaoning Lei; Muhammad Zeeshaan Shahid; Azhar Siddique; Mariam A. Yousaf Al-Nesf (Air Quality, Atmosphere & Health, 2025)

Leveraging immunoinformatic for the rational design of highly immunogenic multi-epitope subunit vaccines against Dugbe virus: a molecular docking and simulation approach - Ali khan; Safir Ullah Khan; Fazal Akbar; Fakhrul Hassan; Zafar Ali; Haji Khan; Shahid Ali; Muhammad Yousaf; Hadi M. Yassine; Sergio Crovella; Muhammad Suleman (In Silico Pharmacology, 2025)

Corrigendum to ‘Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting’ [Chemosphere 310 (2023) 136835] - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2025)

Glyceraldehyde-3-phosphate dehydrogenase facilitates Mycoplasma synoviae colonisation in the lower respiratory system - Sahar Zare; Marc S. Marenda; Sathya N. Kulappu Arachchige; Pollob Shil; Muhammad A. Shahid; Somayeh Kordafshari; Chathuri H. Rodrigo; Amin Kawarizadeh; Denise O’Rourke; Amir H. Noormohammadi (Veterinary Microbiology, 2025)

Scenario analysis of Saudi Arabia's residential solar energy incentives - Sikandar Abdul Qadir; Amjad Ali; Md Tasbirul Islam; Muhammad Shahid (Utilities Policy, 2025)

A novel approach towards green extraction of environmentally friendly anthraquinone based natural dye from amaltas fruits for leather coloration - Shahid Adeel; Fatima Batool; Tanvir Ahmad; Marwa Bashir; Noman Habib; Muhammad Imran; Rony Mia (Sustainable Chemistry and Pharmacy, 2025)

Corrigendum to “Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience” [Sci. Total Environ. 998 (2025) 180305] - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Biochar and GO doped biochar powder for photocatalysis, adsorption, and latent fingermark detection - Abaid Ullah; Aliya Zahid; Shaista Ali; Aniza Latif; Muhammad Shahid; Atia Sarfraz; Muhammad Akhyar Farrukh (Journal of Water Process Engineering, 2025)

Ultrahigh-porosity peony-like magnesium oxide for the superior adsorption of arsenic (III) and arsenic (V) from aqueous solutions - Ghulam Asghar; Duc Anh Nguyen; Thi Hai Chau Dong; Sumaira Manzoor; Shahid Ali; Muhammad Mansha; Shehzada Muhammad Sajid Jillani; Safyan Akram Khan (Journal of Hazardous Materials, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Optimization of superheated steam extraction of essential oil from Citrus limetta Peel by response surface methodology - Muhammad Adnan Ayub; Ambreen Fatima; Yousef M. Alanazi; Muhammad Asif Javaid; Abdullah Ijaz Hussain; Muhammad Shahid; Muhammad Zubair; Kim D. Thomspon (Innovative Food Science & Emerging Technologies, 2025)

Bimetallic metal-organic frameworks as versatile electrocatalysts for water splitting in neutral and alkaline environments - Syed Arfan Haider; Tehseen Mushtaq; Bakhtawar Sajjad; Munazza Shahid; Muhammad Altaf; Ayman Nafady; Ghayoor Abbas Chotana; Manzar Sohail; Shahid Rasul; Raja Shahid Ashraf (Fuel, 2025)

Retraction notice to “Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles” [Environ. Res. 233 (2023) 116477] - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2025)

Spatiotemporal dynamics of the interactions between urban surface temperature and extreme hourly rainfall in Nigerian cities - Khalid Sulaiman; Mohd Ridza Mohd Haniffah; Al-Amin Danladi Bello; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid; Abdullahi Sule Argungu; Bashir Tanimu (Theoretical and Applied Climatology, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Preliminary Detection of Bats-associated Influenza A virus from Pakistan - Sidra Rahman; Syed Ahsan Shahid; Hassan Ayaz; Sajid Ali Shah; Muhammad Ali (Current Microbiology, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Effect of Bioactive Peptides and Encapsulated Butyric Acid on Growth Performance, Gut Health, Immune Status and Nutrient Digestibility in Broiler Chickens - Mohammad Ahmad Qazi; Ehsaan Ullah Khan; Saima Naveed; Shahid Mehmood; Muhammad Muneeb; Muhammad Talha; Muhammad Shabir Shaheen; Sohail Ahmad (International Journal of Peptide Research and Therapeutics, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Exploring water use pathways under deep decarbonization scenarios in Canada at subnational scales using GCAM-Canada - Osama Younis; Evan G.R. Davies; Diego V. Chiappori; Matthew Binsted; Muhammad-Shahid Siddiqui; Evan J. Arbuckle; Nick Macaluso (Journal of Environmental Management, 2025)

Towards energy efficiency in Pakistan: An analysis of increasing integrated fuel demand using LEAP forecasting and backcasting - Muhammad Shahid; Kafait Ullah; Kashif Imran; Amjad Ali (Fuel, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Heavy metals removal and reduction of heavy metal phytotoxicity by Arthrobacter, Bacillus, and Pseudomonas strains harboring genes encoding metal resistance - Muhammad Tahir; Muhammad Nasir; Tahir Naqqash; Muhammad Shahid; Abu Bakr Umer Farooq; Muhammad Akram; Muhammad Arshad; Muhammad Kamran; Urooj Khan (Biocatalysis and Agricultural Biotechnology, 2025)

Exogenous Zinc Alleviates Post-Anthesis Heat Stress by Improving the Defense Mechanism and Leaf Physiology of Bread Wheat - Muhammad Sarwar; Muhammad Farrukh Saleem; Aleena Anwar; Hassaan Ahmad; Basharat Ali; Muhammad Shahid; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd-Allah (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing accuracy in flexural strength prediction of glass fibre-reinforced concrete via TPE-XGB algorithm and explainable machine learning - Muhammad Abdullah Khan; Anas Rahat Ullah; Danish Mukhtiar; Muhammad Shahid Siddique; Muhammad Hammad Iqbal; Waleed Bin Inqiad (Innovative Infrastructure Solutions, 2025)
This study aims to accurately predict the flexural strength (FS) of glass fiber reinforced concrete (GFRC) using advanced machine learning (ML) techniques. A novel algorithm, tree structured parzen estimator based extreme gradient boosting (TPE-XGB), is proposed by integrating Bayesian optimization (TPE) for automated hyperparameter tuning with the predictive strength of XGB. In addition to TPE-XGB, other ML algorithms including bagging regressor (BR), gene expression programming (GEP), and multi expression programming (MEP) are also employed for comparison. A comprehensive dataset consisting of 227 experimental instances of GFRC flexural strength was compiled from 33 internationally published studies. The models were trained and evaluated using statistical error metrics, k fold cross validation, scatter plots, and residual analysis. Results showed that all models performed reliably, with TPE-XGB achieving the highest prediction accuracy (testing R 2 value of 0.972). In contrast, GEP and MEP, described as grey box models that produce interpretable mathematical expressions, offered empirical equations for FS prediction which enhanced transparency. To further address the non-transparent nature of black box models like TPE-XGB, explainable machine learning (XML) techniques were applied. These included SHAP (Shapley Additive Explanations), Individual Conditional Expectation (ICE), and Partial Dependence Plots (PDP). The analysis revealed that water to cement ratio, quantities of fine and coarse aggregates, and glass fiber content were the most influential variables affecting the flexural performance of GFRC. Finally, a graphical interface is proposed to demonstrate the practical usability of the developed models. This study contributes both accurate prediction tools and interpretable insights, supporting improved and informed design practices in concrete technology.

Unlocking the Geoheritage Potential of Hingol National Park (HNP), Pakistan: Geological and Geomorphological Insights Through Multi-Satellite Remote Sensing Data and Field Geology Validation - Muhammad Yaseen; Rujun Chen; Jawad Ahmad; Shahid Ali Shah; Shah Fahad; Muhammad Naveed Anjum; Syed Tanvir Shah (Geoheritage, 2025)

Sustainable development in Asian countries: exploring the nexus between economic growth and environmental sustainability - Shahid Iqbal; Muhammad Zada; Hafiza Iram Naseem; Jehan Zeb (Clean Technologies and Environmental Policy, 2025)

Cadmium and zinc inflows through wastewater irrigation govern soil metal balances in wheat-sorghum cropping system - Ayta Umar; Muhammad Nadeem; Shahid Hussain (Environmental Monitoring and Assessment, 2025)

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Empowering Saudi Arabia's sustainable energy future: A LEAP-Based approach for balancing energy supply and demand - Muhammad Shahid; Amjad Ali; Sikandar Abdul Qadir; Md Tasbirul Islam (Utilities Policy, 2025)

Let the BOOSTER boost photosynthesis and plant productivity - Niaz Ahmad; Muhammad Jawad Akbar Awan; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2025)

Machine learning-driven prediction of Visual Range under changing climate conditions over complex terrain using AOD and CMIP6 climate simulations - Sadaf Javed; Muhammad Imran Shahzad; Muhammad Zeeshaan Shahid; Jun Wang; Imran Shahid (Remote Sensing Applications: Society and Environment, 2025)

Sustainable immobilization strategy for Desertifilum tharense BERC-3 on corncobs to enhance biomass production and high-value metabolites - Muhammad Usman; Md Asraful Alam; Ayesha Shahid; Zhang Beixiao; Aqib Zafar Khan; Anqi Zhao; A.E. Solovchenko; Muhammad Aamer Mehmood; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Carbon nanotubes oriented bifunctional electrocatalyst supported on flexible material for overall water splitting - Alizah Jabeen; Ahmed M. Fallatah; Tahani Rahil Aldhafeeri; A. Alhadhrami; Abdulraheem SA Almalki; Sheraz Yousaf; Zeinhom M. El-Bahy; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Translational potential of GADD45α: biomarker and therapeutic target in age-associated neurodegeneration and longevity - Imran Kazmi; Fahad A. Al-Abbasi; Mustafa Zeyadi; Misbahuddin Rafeeq; Alaa Hamed Habib; Johar Iqbal; Sami I. Alzarea; Omar Awad Alsaidan; Muhammad Shahid Nadeem (Biogerontology, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Driving innovation in fast-food industry: integrating green HRM, green empowerment, and green CSR - Jamshed Khalid; Mi Chuanmin; Muhammad Umair Ashraf; Muhammad Haroon Rasheed; Muhammad Shahid Rasheed (Environment, Development and Sustainability, 2025)

Biogenic silver nanoparticles to control rice blast caused by Magnaporthe oryzae - Muhammad Shahid; Paul K. Goetze; Usman Shafqat; Young-Ki Jo (Physiological and Molecular Plant Pathology, 2025)

Probing the synergistic effect of MXene (TiCT) and MWCNTs on NiWO for superior water-splitting and supercapacitor studies - Amna Irshad; Mirza Mahmood Baig; Seung Goo Lee; Imran Shakir; Zeid A. ALOthman; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Correction to: Physiological and biochemical responses of the achachairu tree (Garcinia humilis) to the combined effects of salinity and flooding - Federico W. Sanchez; Jonathan H. Crane; Haimanote K. Bayabil; Ali Sarkhosh; Muhammad A. Shahid; Bruce Schaffer (Plant and Soil, 2025)

Adaptive response of rare mountain sedge (Carex Ecostata C.B. Clarke) to hyper-cold environments - Ansa Asghar; Amina Ameer; Farooq Ahmad; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Mingzhou Qin; Asima Asghar; Shahid Ali Khan; Hao Yang Li; Zhan Fei Zhang (Plant and Soil, 2025)

Physiological and biochemical responses of the achachairu tree (Garcinia humilis) to the combined effects of salinity and flooding - Federico W. Sanchez; Jonathan H. Crane; Haimanote K. Bayabil; Ali Sarkhosh; Muhammad A. Shahid; Bruce Schaffer (Plant and Soil, 2025)

Multivariate Statistical Evaluation of 20 Metals/Metalloid Levels in the Serum of Patients with Prostate Gland Diseases - Muhammad Abdul Qayyum; Mian H. R. Mahmood; Tahir Farooq; Ahmad Irfan; Shahid Iqbal; Nazim Hussain (Indian Journal of Clinical Biochemistry, 2025)

Recombinant production and characterization of novel carboxypeptidase from thermophilic archaeon Thermococcus siculi - Saima Iftikhar; Maida Wahid; Muhammad Shahid Nadeem; Farheen Aslam; Khushi Muhammad (Biologia, 2025)

Transboundary river water quality assessment: a case study of Kabul River Basin, Pakistan - Kashif Hussain; Muhammad Shahid Iqbal; Sarfraz Munir; Hazrat Bilal (Environmental Science and Pollution Research, 2025)

A hybrid machine learning-based past performance and envelope approach for rainfall projection in Sarawak, Malaysia - Zulfaqar Sa'adi; Shamsuddin Shahid; Mohammed Sanusi Shiru; Kamal Ahmed; Mahiuddin Alamgir; Mohamad Rajab Houmsi; Lama Nasrallah Houmsi; Zainura Zainon Noor; Muhammad Wafiy Adli Ramli (Urban Climate, 2025)

Cytological observation and transcriptome analysis reveal that NTFR1 is a new tetraploid rice fertility gene using the tetraploid fertility-directed lines - Hao Fan; Kai Li; Mengzhu Hu; Zijuan Huang; Haibin Guo; Xiang Li; Zhixiong Chen; Lan Wang; Muhammad Qasim Shahid; Xiangdong Liu; Jinwen Wu (Plant Science, 2025)

Metabolomic, biochemical, and cytological observations reveal β-Pinene's protective effects against cadmium toxicity in salt-tolerant rice - Fozia Ghouri; Jiacheng Jin; Shafaqat Ali; Minghui Zhong; Jingwen Liu; Weiwei Xia; Fengliang Jin; Muhammad Qasim Shahid (Journal of Environmental Management, 2025)

Molecular mechanisms and softening effects of edible acids on the intermuscular bones of grass carp (Ctenopharyngodon idella) - Mujahid Niaz; Muhammad Shahid; Noshaba Munawar; Zhihao Zhong; Shucheng Liu; Lianhong Guo; Jie Zhu (Food Chemistry, 2025)

Spatial variation of building energy consumption in Egypt based on high-resolution typical meteorological year data - Mohammed Rady; Mohammed Magdy Hamed; Ahmed Abdiaziz Alasow; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Energy and Buildings, 2025)

Characteristics of aerosols and planetary boundary layer dynamics during biomass burning season - Muhammad Zeeshaan Shahid; Muhammad Imran Shahzad; Sundas Jaweria; Sadaf Javed; Shah Zaib; Imran Shahid (Natural Hazards, 2025)
The northeastern region of Pakistan (NEP) has experienced increased haze episodes over the past decade, primarily due to enhanced biomass burning activities during the post-monsoon season. Economic growth, urbanization and industrial development also controbuted to high pollutants levels that leads to decline in air quality and visibility. These elevated pollution levels over NEP (69–75.5°E, 27.4–34°N) are influenced by both meteorological conditions and anthropogenic activities. This study investigates aerosol concentrations before, during, and after the haze episode during November 2021 using model simulations and remote sensing data. The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2), along with satellite observations from the Moderate Resolution Imaging Spectroradiometer (MODIS), are used for validation and analysis of this haze episode. The results illustrate the key contributors to this haze event and showed the there is significant increases in aerosol components such as sulfate, black carbon, organic carbon, dust and aerosol optical depth (AOD). The planetary boundary layer (PBL) height, measured with Ceilometer LIDAR, showed decreasing trend in height from October to December that support aerosol accumulation near the surface during the the month of November. This month is also biomass burning, crop residue burning, season in the region. These haze episodes also impacts the atmospheric visibility that dropped below 2 km in November. These findings provide key insights into the complex interactions between meteorology, emissions, and haze formation in NEP region, and will provide policy makers to design effective mittigation strategies.

Integrated Application of Drought-Tolerant Phosphate Solubilizing Bacteria and Native P Source Improves P Availability with Sustainable Wheat Production - Hafiz Shahid Hussain; Saira Tabbasum; Naima Mahreen; Mahreen Yahya; Khansa Ejaz; Zoya Aslam; Muhammad Imtiaz; Ejaz ul Islam; Zahid Iqbal Sajid; Sumera Yasmin (Journal of Soil Science and Plant Nutrition, 2025)

Managing Fertilizer Rates and Tillage Depth to Improve Nitrogen Use Efficiency and Soil Health - Abdul Wakeel; Abdul Qadeer; Zunaira Bano; Muhammad Rizwan Shahid; Muhammad Rizwan; Aysha Kiran; Muhammad Sanaullah; Tariq Aziz; Robert Martin Rees; Arti Bhatia; Julia Drewer (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Evaluating evapotranspiration models for precise aridity mapping based on UNEP- aridity classification - Dauda Pius Awhari; Mohamad Hidayat Bin Jamal; Mohd Khairul Idlan Muhammad; Istifanus Akila Bardey; Shamsuddin Shahid (Earth Science Informatics, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

A Comprehensive Review on Chemical Composition and Pharmacological Properties of Rosa damascena Mill. - Arshia Shahid; Mohd. Vaseem; Md. Arshad; Mohammad Khushtar; Mohd. Afroz Ahmad; Mohd. Ajmal; Saurabh Kumar Chauhan; Abubakar; Muhammad Arif (Current Pharmacology Reports, 2025)

Trace element removal from wastewater by agricultural biowastes: A data analysis on removal efficacy and optimized conditions - Muhammad Shahid; Sana Khalid; Zeid A. ALOthman; Abdullah A. Al-Kahtani; Irshad Bibi; Rabia Naz; Natasha Natasha; Nabeel Khan Niazi; Jibran Iqbal; Changseok Han; Noor S. Shah; Behzad Murtaza (Science of The Total Environment, 2025)

Unveiling the potential of Ce-In2S3 microflowers encased in graphene: Enhancing synergistic effects with Ce as an electron mediator for photocatalytic annihilation of organic dyes - Fatimah Mohammed A. Alzahrani; Tahani Rahil Aldhafeeri; Imed Boukhris; M.S. Al-Buriahi; Muhammad Shahid; Khadija Chaudhary; Muhammad Farooq Warsi (Journal of Water Process Engineering, 2025)

Energy metabolism, antioxidant defense system, metal transport, and ion homeostasis are key contributors to Cd tolerance in SSSL derived from wild rice - Humera Ashraf; Fozia Ghouri; Lixia Sun; Weiwei Xia; Sawaira Ashraf; Muhammad Zahid Ashraf; Xuelin Fu; Shafaqat Ali; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2025)

Effect of Spirulina platensis on the structure and aggregation of gluten proteins to improve texture and physiochemical properties of wheat noodles - Kerui Su; ZhiHao Fan; Muhammad Usman; Anqi Zhao; Hanyu Dong; Xuejing Duan; Longfei Weng; Ayesha Shahid; Jingliang Xu (Food Hydrocolloids, 2025)

Thermally efficient hydrophobic zirconia ceramic nanofiber membrane for enhanced membrane distillation performance - Min Wei Boey; Shahid Ali Khan; Xiaolu Li; Jiawei Sun; Muhammad Usman Farid; Alicia Kyoungjin An (Chemical Engineering Journal, 2025)

Assessing the efficacy of simplified temperature-based PET models in replicating penman–monteith drought frequency - Dauda Pius Awhari; Mohamad Hidayat Bin Jamal; Mohd Khairul Idlan Bin Muhammad; Mohammed Abdu Nasara; Najeebullah Khan; Zulfaqar Sa’adi; Mohammed Khalid Othman; Shamsuddin Shahid (Theoretical and Applied Climatology, 2025)

Ecotoxicological investigation of arsenic contamination within the water-soil-fruit-human continuum - Muhammad Shafique Khalid; Nimra Farooq; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Samina Khalid; Hafiz Faiq Bakht; Ghulam Mustafa Shah; Muhammad Asif Naeem; Ghulam Abbas; Behzad Murtaza (Environmental Geochemistry and Health, 2025)

Spatio‐Temporal Dynamics of Vegetation and Land Surface Temperature in Saudi Arabia: Impacts of Climate Change on Agricultural Sites From 2010 to 2023 - Mazen E. Assiri; Md. Arfan Ali; Lama Alamri; Muhammad Haroon Siddiqui; Ayman S. Ghulam; Shamsuddin Shahid (International Journal of Climatology, 2025)
Saudi Arabia has one of the greatest water shortages and the least vegetation in the world, which is potentially exacerbating the issue of environmental impacts. Therefore, it is crucial to understand the interaction between climate change, vegetation dynamics and land surface temperature (LST). The present study investigates the spatio‐temporal distributions, variations, change detection and trends of vegetation dynamics and surface temperature over eight agricultural sites in Saudi Arabia using the Normalised Difference Vegetation Index (NDVI) and LST from Landsat 7 (Enhance Thematic Mapper Plus: ETM + ) and Landsat 8 (operational land imager: OLI) measurements for the period 2010–2023. The study also examined the relationship between NDVI, LST and climate variables such as air temperature, rainfall, relative humidity and soil moisture. Results showed that an NDVI > 0.20 represents vegetation in Saudi Arabia. Higher values of NDVI were found in Baysh, Jazan province, compared to other agricultural sites. Significant annual and seasonal variations in NDVI were also observed across eight major agricultural sites in Saudi Arabia, attributable to the region's varying climate conditions. Vegetation expansion in 2023 exceeded that in 2014 in Buraydah (304.34 km 2 ), Tabarjal (63.81 km 2 ), Hail (33.20 km 2 ), Al Qirw (22.53 km 2 ) and Baysh (3.07 km 2 ), while reductions were noted in Wadi Al Dawasir (274.58 km 2 ), Tabuk (88.56 km 2 ) and Al Ahsa (27.30 km 2 ). The LST over soil and vegetated surfaces showed that vegetation notably reduced LST at Hail (3.14°C), Al Ahsa and Wadi Al Dawasir (5.43°C), Buraydah (4.53°C), Baysh (2.71°C), Al Qirw (5.17°C), Tabuk (6.24°C) and Tabarjal (3.13°C). The study found that NDVI, LST and climate variables are positively and negatively correlated, which indicates a significant impact of climate change on vegetation patterns. The findings of this study are highly relevant for informing agricultural and environmental policy development in Saudi Arabia, with a focus on enhancing vegetation cover, mitigating the impacts of rising temperatures and advancing sustainable agricultural practices to address the challenges posed by climate change.

Impact of End-capped Acceptor Modification in Anthanthrone-Based D-π-A Type Donor Materials for Organic and as Hole Transporting Materials for Perovskite Solar Cells - Nabeel Shahzad; Shahzad Ali Shahid Chatha; Riaz Hussain; Shahid Hussain; Javed Iqbal; Muhammad Adnan (Journal of Fluorescence, 2025)

Unraveling the Complexity of Alzheimer’s Disease: Insights into Etiology and Advancements in Treatment Strategies - Bakhtawar Khan; Muhammad Khalid Iqbal; Muhammad Ajmal Khan; Hamid Khan; Mubin Mustafa Kiyani; Shahid Bashir; Shao Li (Journal of Molecular Neuroscience, 2025)

Decentralized municipal solid waste management system (DMSWMS) as an alternative to centralized MSWMS (CMSWMS) for HEIs based on case study of the University of the Punjab, Lahore, Pakistan - Sidra Shahid; Muhammad Shafiq; Firdaus-e-Bareen (Environmental Monitoring and Assessment, 2025)

Exploration of natural colourant of ( Solanum melongena L.) brinjal plant residues for fabric dyeing: a novel approach towards textile processing - Fatima Batool; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; Sahar Mumtaz; Muhammad Hussaan (Natural Product Research, 2025)

Heavy metal contamination in some commercial marine fishes of Pakistan - Sania Riaz; Muhammad Javed Khan; Iqra Rani; Asad Ali; Muhammad Asghar Qazi; Mehnoor Sameer; Khadija; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Role of plant growth-promoting rhizobacteria in sustainable agriculture: Addressing environmental and biological challenges - Abdul Wahab; Farwa Batool; Gholamreza Abdi; Murad Muhammad; Shahid Ullah; Wajid Zaman (Journal of Plant Physiology, 2025)

Recovery and treatment of cooling tower blowdown water: Challenges, recent advancement, and future perspectives - Syed Taufiq Ahmad; Ashfaq Ahmad; Rizwan Ahmad; Ahmed Fuwad; Azeem Mushtaq; Muhammad Kashif Shahid (Journal of Environmental Chemical Engineering, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Comparative analysis of bias correction methods for projecting extreme precipitation and temeprature indices in Pakistan - Zulfiqar Ali; Mohd Khairul Idlan Muhammad; Mansour Almazroui; Shamsuddin Shahid (Atmospheric Research, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Unveiling the Potential of Protein-Based Sustainable Antibacterial Materials - Iqra Ghouri; Muslum Demir; Shahid Ali Khan; Muhammad Adil Mansoor; Mudassir Iqbal (Probiotics and Antimicrobial Proteins, 2025)

Biochemical investigation of FOXP3 genetic polymorphism and its association with biochemical parameters in pre-eclampsia patients - Muhammad Sajid Hamid Akash; Francis Victor; Kanwal Rehman; Amjad Hussain; Mudassar Shahid; Asif Shahzad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2025)

Perfecting prime editing: achieving precise edits in dicots - Niaz Ahmad; Muhammad Jawad Akbar Awan; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2025)

Foaming in wastewater treatment plants: Deciphering biological foaming and challenges in MBR systems - Muhammad Ibrahim; Narada Dayarathne; Jun Wei Lim; Shukra Raj Paudel; Muhammad Kashif Shahid; Bandita Mainali (Journal of Water Process Engineering, 2025)

Melatonin mitigates nickel oxide nanoparticles induced phytotoxicity in soybean by reducing metal accumulation, enhancing antioxidant defense and promoting nitrogen assimilation - Kashif Khan; Rayyan Khan; Zhuo Liu; Shahid Ali; Muhammad Asad Naseer; Muhammad Ali Shah; Haseeb Ahmad; Xun Bo Zhou (Journal of Hazardous Materials, 2025)

Quest for environmental management and sustainability: Evaluating the drivers of territorial and consumption-based carbon emissions in G-20 economies - Muhammad Adnan Bashir; Li Qing; Shahid Manzoor; Shahzad Khan Durrani; Lin Jingting; Nasir Sultan (Journal of Environmental Management, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Molecular diversity and phylogenetic analysis of ten sheep breeds from Khyber Pakhtunkhwa, Pakistan, based on mitochondrial D-loop sequences - Shabir Ahmed; Muhammad Shahid Nadeem; Anna M. Johansson; Elisabeth Jonas; Khushi Muhammad; Sardar Azhar Mehmood (Mammalian Genome, 2025)

Burkholderia sp. AQ12-mediated Molecular Adjustments Assist Growth of Salt-stressed Cotton (Gossypium hirsutum L.) By Modulating Biochemical Status and Nutrient Acquisition Patterns - Sidra Batool; Sijal Fatima; Uzma Qaisar; Muhammad Shahid; Muhammad Sohail Akram (Journal of Soil Science and Plant Nutrition, 2025)

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Qualitative Traits of Heat Stressed Bread Wheat (Triticum aestivum L.) were Improved by Exogenous Potassium Signaling - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Abdul Shakoor; Khalid Mahmood; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2025)

Implications of nociceptor receptors and immune modulation: emerging therapeutic targets for autoimmune diseases - Syeda Asloob Fatima; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Muhammad Shahid; Fozia Anjum; Fatma Hussain; Aisha Mobashar; Maham Ashraf (Inflammopharmacology, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Liver transcriptome analysis reveals the molecular response to hibernation challenge in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Muhammad Shahid Iqbal; Xiaoqi Ai; Qingjun Zhu; Ijaz Khan; Zeeshan Ali; Tian Lan; Li Ding; Meiling Hong (Frontiers in Marine Science, 2025)
Hibernation is a physiological strategy animals use to survive in hostile environments with extreme temperature challenges and food scarcity. During this state, significant changes occur in metabolism and cellular function, with numerous stress response pathways recalibrated to survive physiological challenges that could otherwise be fatal. Numerous studies were performed to explain the molecular mechanisms of mammalian hibernation, but detailed analyses remain scarce in reptiles. Given the limited understanding of the mechanisms regulating hibernation, we performed a comprehensive analysis of liver gene expression in the Chinese softshell turtle ( Pelodiscus sinensis ) comparing summer active (SA), hibernation (H), and early arousal (EA) states using RNA-sequencing. A total of 435 million high-quality reads were generated, identifying 3,508, 3,607, and 2,993 differentially expressed genes (DEGs) in the SA vs. H, H vs. EA, and EA vs. SA respectively. Gene ontology analysis revealed a shift in metabolic fuel utilization, with the down-regulation of metabolic and cellular processes during hibernation, reflecting a conserved strategy for energy conservation. The transition from hibernation to early arousal was marked by up-regulation of immune-related genes (e.g., CXCL12, ITGA4, PIGR) and endocrine regulators (e.g., CDKN1A, DLL4, IGF1R), facilitating metabolic recovery and cellular protection. Besides, we observed dynamic changes in carbohydrate and lipid metabolism, with down-regulation of hexokinase 2 (HK2) and glucose transporters during hibernation, and up-regulation of lipid metabolism genes (LSS, GPLD1) to support membrane integrity and signaling. Our findings provide insights into the molecular mechanisms underlying hibernation and arousal in ectotherms, with implications for understanding metabolic adaptations, immune regulation, and stress responses in extreme conditions.

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Sensory chemistry of Spirulina: Unveiling trends and innovations in aromatic volatile organic compound biosynthesis in off-flavors and odor mitigation strategies - Ayesha Shahid; Zihao Fan; Kerui Su; Anqi Zhao; Muhammad Aamer Mehmood; Jo-Shu Chang; A.E. Solovchenko; Md Asraful Alam; Jingliang Xu (Trends in Food Science & Technology, 2025)

Recent advances of in-well hydrogen production with integrated in-situ carbon dioxide sequestration: A comprehensive review - Mohamed Hamdy; Muhammad Zubair Shahid; Ahmad Salam Farooqi; Mohammed El-Adawy; Mohamed Mahmoud; Sulaiman A. Alarifi; Medhat A. Nemitallah (Process Safety and Environmental Protection, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

Magnetically recyclable Mn and Co doped r-GO based LaFeO3 nano-composite for tuning the optical and solar light driven photo-catalytic applications - Shahid Iqbal; Muhammad Jamshaid; Firdous Bibi; Najla AlMasoud; Taghrid S. Alomar; Rashid Iqbal; Qasim Raza; Ambreen Kalsoom (Journal of Water Process Engineering, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Periphyton biofilms formulation and application for the removal of trace pollutants from water - Khurram Shahzad; Shahid Mahmood; Azeem Khalid; Rai Muhammad Amir; Rab Nawaz; Marlia Mohd Hanfiah; Zaini Bin Sakawi; Muzammil Anjum (International Biodeterioration & Biodegradation, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Breaking barriers in energy storage: 3D printed SiOC/Bi2O3 nanocomposites for high-performance asymmetric supercapacitors - Ali Asghar; Muhammad Shahid Rashid; Muhammad Saqib; Karim Khan; Zhiyuan Liu; Changyong Liu; Zhangwei Chen (Chemical Engineering Journal, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Integrated Weed Management in Sunflower Using a Hybrid Mixture and Reduced Herbicide Dose - Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Shahid Ibni Zamir; Amina Shahbaz; Muhammad Saqib (Journal of Crop Health, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Evaluating the safety and effectiveness of tolvaptan in patients with heart failure and renal impairment: a systematic review and meta-analysis - Aashish Kumar; Umer Iqbal; Shafin Bin Amin; Syed Ali Arsal; Syed Muhammad Sinaan Ali; Muhammad Ashir Shafique; Muhammad Saad Shahid; Aimen Naz; Emediong Santhus Asuka (European Journal of Clinical Pharmacology, 2025)

Molecular characterization of chilli leaf curl virus and ‘Candidatus Phytoplasma trifolii’ infecting Capsicum annuum, India - Vineeta Pandey; Aarshi Srivastava; Smriti Mall; Ramwant Gupta; Abdullah M. Al-Sadi; Rakesh Kumar Verma; Muhammad Shafiq Shahid; R. K. Gaur (Vegetos, 2025)

Influence of pro-environmental behavior (PEB) on environmental sustainability: empirical evidence from health supplements industry - Faryal Salman; Muhammad Shahid Khan (Environment, Development and Sustainability, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Comparative Nutritional Profiling of Economically Important Shrimp Species in Pakistan - Muhammad Bhatti; Shahid Sherzada; Sohail Ahmad; Muhammad Qazi; Amina Ayub; Saeed Khan; Muhammad Khan; Iqra Rani; Nimra Hussain; Joanna Nowosad; Dariusz Kucharczyk (Journal of Marine Science and Engineering, 2025)
Shrimp are widely recognized as a nutritious and flavorful food choice due to their tender and delicious meat. This study evaluated the nutritional composition of three economically important shrimp species: Penaeus merguiensis, Penaeus monodon, and Penaeus indicus, collected from the coastal areas of Pakistan. All shrimp species were found to be high in protein and low in fat content. The ratio of essential amino acids (EAAs), non-essential amino acids (NEAAs), and total amino acids (TAAs) varied significantly (p ≤ 0.05) among species, with P. indicus showing slightly higher values. Regarding fatty acid analysis, total saturated fatty acid content was found to be 35.04% in P. merguiensis, 52.43% in P. monodon, and 44.77% in P. indicus. Similarly, the polyunsaturated fatty acid content was found to be 26.24%, 26.77%, and 24.74%, in P. merguiensis, P. monodon, and P. indicus, respectively. Based on nutrient yield, P. monodon stands out as the most nutrient-dense species, followed by P. indicus and P. merguiensis. Overall, the present study suggests that all shrimp species can be used as a healthy choice of food and a good source of animal protein for human consumption. These findings provide valuable insights into the role of shrimp in promoting a healthy and balanced diet.

A novel integrated multicriteria decision analysis framework for group decision-making in evapotranspiration model selection - Dauda Pius Awhari; Mohamad Hidayat Bin Jamal; Mohd Khairul Idlan Bin Muhammad; Shamsuddin Shahid (Environment, Development and Sustainability, 2025)

Assessing the impact of bifenthrin, neonicotinoids, and insect growth regulators on three aphid species and their predators in Brassica fields: implications for pest management strategies - Muhammad Razaq; Shahid Atta; Rizwan Ahmed Pasha (International Journal of Tropical Insect Science, 2025)

Changing pattern of urban landscape and its impact on thermal environment of Lahore; Implications for climate change and sustainable development - Tahir Sattar; Nigar Fatima Mirza; Muhammad Asif Javed; Muhammad Nasar-u-Minallah; Shahid Malik (Environmental Monitoring and Assessment, 2025)

Heavy metals concentration and human health risk assessment in selected shrimp species of Pakistan - Alveena Draz; Muhammad Asghar Qazi; Talib Hussain; Owais Ahmad; Muhammad Mahd Nazir; Muhammad Bilal Bhatti; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Health Star Rating Labels: A systematic review and future research agenda - Muhammad Junaid Shahid Hasni; Mohsin Abdur Rehman; Nicolas Pontes; Muhammad Zafar Yaqub (Food Quality and Preference, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Advancements in MXene-based 3D printing-based technologies - Ali Asghar; Muhammad Shahid Rashid; Muhammad Hanif; Imed Boukhris; Zhangwei Chen; Muhammad Saqib; Qumail Arshad; P. Rosaiah; Saood Ali; Iftikhar Hussain (Chemical Engineering Journal, 2025)

CMIP5 and CMIP6: contrasting perspectives on Nigeria’s climate transformation - Bashir Tanimu; Mohammed Magdy Hamed; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Zaher Mundher Yaseen; Ahmed Abdiaziz Alasow; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2025)

Characterization of meningitis-causing bacteria, with focus on genomic and pangenomic study of multi-drug resistant Streptococcus pneumoniae from cerebrospinal fluid - Rehan Ali; Kashif Ali; Muhammad Aurongzeb; Khalid Al-Regaiey; Junaid Ahmed Kori; Muhammad Irfan; Yasmeen Rashid; Danah Al Abduljabbar; Imdad Kaleem; Shahid Bashir (Antonie van Leeuwenhoek, 2025)

Formation of particulate matter in the ambient air of Dhaka city, Bangladesh - Md. Yeasin Pabel; Md. Fakrul Islam; Muhammad Nurul Huda; Shahid Akhtar Hossain; M. Muhibur Rahman; Md. Mominul Islam (Air Quality, Atmosphere & Health, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Clonal gamete-mediated polyploid genome design for stacking genomes - Muhammad Jawad Akbar Awan; Imran Amin; Goetz Hensel; Shahid Mansoor (Trends in Plant Science, 2024)

Rice and heavy metals: A review of cadmium impact and potential remediation techniques - Weiwei Xia; Fozia Ghouri; Minghui Zhong; Syed Asad Hussain Bukhari; Shafaqat Ali; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Hydrogen production techniques and use of hydrogen in internal combustion engine: A comprehensive review - Muhammad Ihsan Shahid; Anas Rao; Muhammad Farhan; Yongzheng Liu; Hamza Ahmad Salam; Tianhao Chen; Fanhua Ma (Fuel, 2024)

Triangular relation of food processing, nutrition, and osteoarthritis: A solution for the management and prevention of osteoarthritis? - Arashi Shahid; Ammar B. Altemimi; Iahtisham -Ul-Haq; Muhammad Inam-ur-Raheem; Roshina Rabail; Muhammad Hamdan Rashid; Sadia Kafeel; Muhammad Saad Akram; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Removal of airborne particulate matter by evergreen tree species in Dhaka, Bangladesh - Saif Shahrukh; Richard Baldauf; Robert Popek; Mohammad Moniruzzaman; Muhammad Nurul Huda; Md. Mominul Islam; Shahid Akhtar Hossain; Mohammad Enayet Hossain (Environmental Pollution, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Predominance of MGMT promoter methylation among Pakistani glioblastoma patients - Noor Muhammad; Samir Fasih; Bilal Malik; Shahid Hameed; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

Enhancement of Antioxidants’ Enzymatic Activity in the Wheat Crop by Shewanela sp. Mediated Zinc Oxide Nanoparticles Against Heavy Metals Contaminated Wastewater - Irfan Haidri; Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Usman Shafqat; Sadia Mustafa; Faisal Mahmood (Journal of Soil Science and Plant Nutrition, 2024)

Recent development towards the novel applications and future prospects for cellulose-metal organic framework hybrid materials: a review - Zeenat Qamar; Awais Ali Aslam; Farheen Fatima; Sadaf Ul Hassan; Muhammad Shahid Nazir; Zulfiqar Ali; Sameer Ahmed Awad; Aqeel Ahmad Khan (Environmental Science and Pollution Research, 2024)

Citric acid-driven cadmium uptake and growth promotion mechanisms in Brassica napus - Saiqa Menhas; Kashif Hayat; Daohui Lin; Muhammad Shahid; Jochen Bundschuh; Saiyong Zhu; Sikandar Hayat; Weiping Liu (Chemosphere, 2024)

Rare homozygous cilia gene variants identified in consanguineous congenital heart disease patients - Daniel A. Baird; Hira Mubeen; Canan Doganli; Jasmijn B. Miltenburg; Oskar Kaaber Thomsen; Zafar Ali; Tahir Naveed; Asif ur Rehman; Shahid Mahmood Baig; Søren Tvorup Christensen; Muhammad Farooq; Lars Allan Larsen (Human Genetics, 2024)
Congenital heart defects (CHD) appear in almost one percent of live births. Asian countries have the highest birth prevalence of CHD in the world. Recessive genotypes may represent a CHD risk factor in Asian populations with a high degree of consanguineous marriages. Genetic analysis of consanguineous families may represent a relatively unexplored source for investigating CHD etiology. To obtain insight into the contribution of recessive genotypes in CHD we analysed a cohort of forty-nine Pakistani CHD probands, originating from consanguineous unions. The majority (82%) of patient’s malformations were septal defects. We identified protein altering, rare homozygous variants (RHVs) in the patient’s coding genome by whole exome sequencing. The patients had a median of seven damaging RHVs each, and our analysis revealed a total of 758 RHVs in 693 different genes. By prioritizing these genes based on variant severity, loss-of-function intolerance and specific expression in the developing heart, we identified a set of 23 candidate disease genes. These candidate genes were significantly enriched for genes known to cause heart defects in recessive mouse models (P < 2.4e−06). In addition, we found a significant enrichment of cilia genes in both the initial set of 693 genes (P < 5.4e−04) and the 23 candidate disease genes (P < 5.2e−04). Functional investigation of ADCY6 in cell- and zebrafish-models verified its role in heart development. Our results confirm a significant role for cilia genes in recessive forms of CHD and suggest important functions of cilia genes in cardiac septation.

Biochemical analysis and fertilization success of Cirrhinus mrigala ova during induced spawning - Shahid Sherzada; Tanveer Ahmad; Saeed Akram Khan; Muhammad Inayat; Sohail Ahmad; Abdur Rahman (Animal Reproduction Science, 2024)

Molecular epidemiology and genetic characterization of hepatitis B virus in two major provinces of Pakistan - Iqra Almas; Saeeda Tariq; Iram Amin; Muhammad Shahid; Muhammad Idrees; Samia Afzal (Archives of Virology, 2024)

Exposure to butylparaben induces oxidative stress and apoptosis in the liver of Polypedates megacephalus tadpole - Xiaoqi Ai; Muhammad Shahid Iqbal; Rui Lin; Xia Wu; Lijun Wang; Meiling Hong (Frontiers in Marine Science, 2024)
Butylparaben (BuP) is a ubiquitous preservative in cosmetics, foods, and medicine. As an emerging pollutant, it has gained wide attention in recent years. Because amphibians have both aquatic and terrestrial life stages and high skin permeability, they are sensitive to environmental changes. To assess the toxic effects of BuP on amphibians, the present study was conducted on the spot-legged tree frog ( Polypedates megacephalus ) tadpoles. In the present study, LC 50 of BuP for 96 h exposures was 3509 µg/L. Then, the tadpoles were exposed to 0, 350 and 2100 µg/L BuP (hereafter named as CK, B1 and B2) for 12, 24 and 48 h, the oxidative stress and apoptosis in the liver were analyzed. The results showed that the content of MDA and activity of SOD and GSH-PX were increased with an increase in BuP exposure. BuP stress significantly altered the expression of Nrf2-Keap1 signal pathway genes. An increase in the expression of JAK-STAT signal pathway genes was observed with an increase in the exposure to BuP concentration at 24 and 48 h. In contrast, the expression of negative regulators of JAK-STAT signal pathway were significantly increased at 12 h and decreased at 24 and 48 h. A significant decrease in pro-apoptosis genes expression ( Bax and Caspase3 ) were observed at 12 h but increased at 24 and 48 h, while the expression of anti-apoptosis gene ( Bcl-2 ) decreased at 24 and 48 h. These results provide a valuable reference point for assessing the ecological and health risks associated with BuP in the environment.

Hydro-geochemistry and age-dependent health risk assessment of nitrate, nitrite, and fluoride in health facilities water: a multivariate analysis - Areej Nadeem; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Muhammad Shahid; Abdullah Ghardan Al-Sehemi; Yasar Nelliyot Kavil; Muhammad Amjad; Muhammad Wakeel (Environmental Science and Pollution Research, 2024)

Global distribution and definitive host range of Echinococcus species and genotypes: A systematic review - Rehman Ali; Shahid Nazeer; Malik Muhammad Sohail Elahi; Emmanuel Gideon Idu; Hongteng Zhang; Hossein Mahmoudvand; Shahid Niaz Khan; Jun Yang (Veterinary Parasitology, 2024)

Urbanization signature on hourly rainfall extremes of Kuala Lumpur - Nirwani Devi Miniandi; Mohd Khairul Idlan Muhammad; Mohamad Hidayat Jamal; Shamsuddin Shahid (Sustainable Cities and Society, 2024)

Servant leadership and citizenship behavior in the Pakistani tourism and hospitality industry: The role of harmonious environmental passion and a green work climate - Yasir Iftikhar; Muhammad Shahid Tufail; Marcos Ferasso; Rizwan Qaiser Danish (Journal of Environmental Management, 2024)

Photocatalytic hydrogen peroxide production: Advances, mechanistic insights, and emerging challenges - Shahid Khan; Muhammad Adnan Qaiser; Waqar Ahmad Qureshi; Syed Najeeb-uz-Zaman Haider; Xiaohui Yu; Weikang Wang; Qinqin Liu (Journal of Environmental Chemical Engineering, 2024)

Modulating glucose metabolism and relieving hypoxia for enhanced Chemo/Photoimmunotherapy with photosensitizing enzymatic nanodrugs - Zhiyuan Zheng; Shan Lu; Yue Wu; Ayşe Başak Kayitmazer; Ayyaz Ahmad; Naveed Ramzan; Muhammad Shahid Rafique; Jintao Yang; Xiaolong Zhou; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Genetic testing perspectives in Pakistani population: a survey on knowledge, attitudes, awareness, and concerns - Mohammad Uzair; Rida Fatima; Shafia Rafiq; Maimoona Jabeen; Hammad Qaiser; Muhammad Arshad; Shahid Bashir (Journal of Community Genetics, 2024)

Salt-Tolerant Plant Growth-Promoting Bacteria (ST-PGPB): An Effective Strategy for Sustainable Food Production - Syeda Tahseen Zahra; Mohsin Tariq; Muhammad Abdullah; Muhammad Kaleem Ullah; Abdul Rafay Rafiq; Aisha Siddique; Muhammad Shafiq Shahid; Temoor Ahmed; Imrana Jamil (Current Microbiology, 2024)

Assessment of Genomic Diversity and Selective Pressures in Crossbred Dairy Cattle of Pakistan - Fakhar un Nisa; Rubab Zahra Naqvi; Fazeela Arshad; Iram Ilyas; Muhammad Asif; Imran Amin; Raphael Mrode; Shahid Mansoor; Zahid Mukhtar (Biochemical Genetics, 2024)

Bibliometric analysis of global climate change and agricultural production: Trends, gaps and future directions - Dauda Pius Awhari; Mohamad Hidayat Bin Jamal; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Irrigation and Drainage, 2024)
Climate change poses a significant threat to global food security, and a comprehensive understanding of its impact on agricultural production is needed. We analysed the Scopus data set between 1993 and 2023. China occupies the leading position in terms of climate change production, and the United States occupies the comprehensive strength position with the largest citation strength output. Notably, a substantial 29% annual publication increase between 2000 and 2015 was noted. Despite prevailing research on specific facets, a pronounced gap exists in global‐scale studies focusing on the direct impact of climate change on agricultural production and yield, with a predominant concentration in regional analyses. Collaboration in this area continues to occur within developed nations, but the rate of growth at the international level is relatively low. In addition, the frequency of co‐occurrence analysis of keywords revealed that climate change and sustainability are the focal keywords, but yield, food security, irrigation and rice production have yet to be identified. The results of this research will help in designing a policy for water resource management for irrigation planning and an adaptative food security management strategy and provide a feature research guide.

Improving environmental and economic sustainability of cutlery manufacturing in a developing nation through energy reduction and energy transition initiatives - Muhammad Aqib; Shamraiz Ahmad; Shahid Ikramullah Butt (Environmental Science and Pollution Research, 2024)

Retraction Note: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2024)

Fault root cause analysis using degree of change and mean variable threshold limit in non-linear dynamic distillation column - Muhammad Shahid; Haslinda Zabiri; Syed Ali Ammar Taqvi; Mansoor Hai (Process Safety and Environmental Protection, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Ultrasonic-assisted green extraction and incorporation of Spirulina platensis bioactive components into turmeric essential oil-in-water nanoemulsion for enhanced antioxidant and antimicrobial activities - Muhammad Abdur Rehman Shah; Yajie Zhang; Yi Cui; Xinjuan Hu; Feifei Zhu; Santosh Kumar; Gang Li; Ameer Ali Kubar; Shahid Mehmood; Shuhao Huo (Food Chemistry, 2024)

Unveiling the nexus between atmospheric visibility, remotely sensed pollutants, and climatic variables across diverse topographies: A data-driven exploration empowered by artificial intelligence - Sadaf Javed; Muhammad Imran Shahzad; Imran Shahid (Atmospheric Pollution Research, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Assessment of future drought sensitivity shift associated with crop yield loss risk in the Anthropocene - Muhammad Waseem; Tahira Khurshid; Muhammad Shahid; Muhammad Atiq Ur Rehman Tariq; Jiaqing Xiao; Tao Yang; Pengfei Shi (Hydrological Sciences Journal, 2024)

Artificial neural network modeling for the prediction, estimation, and treatment of diverse wastewaters: A comprehensive review and future perspective - Muhammad Ibrahim; Adnan Haider; Jun Wei Lim; Bandita Mainali; Muhammad Aslam; Mathava Kumar; Muhammad Kashif Shahid (Chemosphere, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Spatiotemporal analysis of soil moisture drought in the Horn of Africa - Ahmed Abdiaziz Alasow; Mohammed Magdy Hamed; Mohammed Rady; Mohamed Abdillahi Arab; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2024)

Tree-ring based summer temperature variability since 1790 CE in the Hindu Kush region of northern Pakistan - Fayaz Asad; Muhammad Adil; Sabrina Shahid; Nasrullah Khan; Ru Huang; Haifeng Zhu (International Journal of Biometeorology, 2024)

Molecular identification and characterization of iris yellow spot virus (IYSV) and garlic virus X (GVX) infecting Allium species - Muhammad Usman Shahid; Abid Riaz; Tahira Shafique; Mayasar I. Al-zaban; Diaa Abd El-Moneim; Sheikh Mansoor; Yong Suk Hung; Hyeon-Jin Sun (Plant Biotechnology Reports, 2024)

Retraction Note: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2024)

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

Retraction Note: Techno-economic analysis of biogas production from domestic organic wastes and locally sourced material: the moderating role of social media based-awareness - Shahid Ali; Qingyou Yan; Huaping Sun; Muhammad Irfan (Environmental Science and Pollution Research, 2024)

In vitro exploration of Acinetobacter strain (SG-5) for antioxidative potential and phytohormone biosynthesis in maize (Zea mays L.) cultivars differing in cadmium tolerance - Saghir Abbas; Kashif Tanwir; Muhammad Hussaan; Sajid Masood; Qasim Ali; Ali Raza; Muhammad Shahid; Hassan Javed Chaudhary; Saba Mushtaq; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2024)

A multiplex PCR assay to detect mislabelling in fish products - Komal; Shahid Sherzada; Muhammad Imran; Saeed Akram Khan; Abdul Wajid (Food Additives & Contaminants Part B-Surveillance, 2024)

Zeugodacus fruit flies (Diptera: Tephritidae) host preference analysis by machine learning-based approaches - Naila Nazir; Sehar Fatima; Muhammad Aasim; Faheem Yaqoob; Khalid Mahmood; Seyid Amjad Ali; Shahid Iqbal Awan; Ihsan ul Haq (Computers and Electronics in Agriculture, 2024)

Principal Component Analysis (PCA) and feature importance-based dimension reduction for Reference Evapotranspiration (ET 0 ) predictions of Taif, Saudi Arabia - Rab Nawaz Bashir; Olfa Mzoughi; Muhammad Ali Shahid; Nazik Alturki; Oumaima Saidani (Computers and Electronics in Agriculture, 2024)

Salicylic acid-driven innate antiviral immunity in plants - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2024)

Corrigendum to “Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential” [Environ. Res. 252 (2024) 118945/ ER-23-14694R1] - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nadir; Sailesh Ranjitkar (Environmental Research, 2024)

Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nader; Sailesh Ranjitkar (Environmental Research, 2024)

Identification of bacterial community in a rapid composting method using 16SrDNA genes sequencing - Muhammad Shahid; Waqar Ahmed; Abdul Basit Khan; Zafar Iqbal Shams; Afsheen Arif (Biodegradation, 2024)

Depositional and diagenetic studies of clastic reservoirs zone in the Cretaceous Lower Goru Formation, Sindh Monocline, South Pakistan - Jawad Ahmed Jan; Mumtaz Muhammad Shah; Hamad ur Rahim; Shahid Iqbal; Samina Jahandad; Muhammad Jamil; Rayan Khalil; Yawar Amin (Journal of Earth System Science, 2024)

Inhibitory potential of Syzygium aromaticum against Fusarium oxysporum f. sp. lycopersici: In-vitro analysis and molecular docking studies - Muhammad Atif; Tehmina Anjum; Ahmad Ali Shahid; Ahmad Hassan; Waheed Akram (South African Journal of Botany, 2024)

Modern ecofriendly approach for extraction of luteolin natural dye from weld for silk fabric and wool yarn dyeing - Syed Ali Raza Naqvi; Kaif ul-Wara; Shahid Adeel; Rony Mia; Mozhgan Hosseinnezhad; Luqman Jameel Rather; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Enhancing reliability in climate projections: A novel approach for selecting global climate models - Bashir Tanimu; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Unveiling the impact of textile materials to prevent viral infections: Urgency for awareness and public safety† - Muhammad Zaryab Waleed; Khezina Rafiq; Muhammad Zeeshan Abid; Muhammad Burhan; Raed H. Althomali; Shahid Iqbal; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2024)

RETRACTED: Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Unveiling the chemical profile, synergistic antibacterial and hemolytic effects of Cymbopogon citratus and Tachyspermum ammi leaves - Shabbir Hussain; Amina Zahid; Muhammad Imran; Shazma Massey; Muhammad Riaz; Muhammad Sagir; Muhammad Shahid; Wissem Mnif; Shahid Iqbal; Munawar Iqbal; Arif Nazir (Biocatalysis and Agricultural Biotechnology, 2024)

Comparison of conventional and machine learning methods for bias correcting CMIP6 rainfall and temperature in Nigeria - Bashir Tanimu; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Zaher Mundher Yaseen; Mohammad Kamruzzaman; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2024)

Recent synthetic approaches towards thienothiophenes: a potential template for biologically active compounds - Ayesha Rafiq; Sana Aslam; Matloob Ahmad; Muhammad Shahid Nazir; Ambar Farooq; Sadia Sultan (Molecular Diversity, 2024)

Mass-spectrometric analysis of APOB polymorphism rs1042031 (G/T) and its influence on serum proteome of coronary artery disease patients: genetic-derived proteomics consequences - Muneeza Zafar; Imran Riaz Malik; Munazza Raza Mirza; Fazli Rabbi Awan; Arkadiusz Nawrocki; Misbah Hussain; Haq Nawaz Khan; Shahid Abbas; Muhammad Iqbal Choudhary; Martin R. Larsen (Molecular and Cellular Biochemistry, 2024)

Sustainable production of bread wheat under terminal heat stress: an investigation of foliar selenium-mediated biochemical regulations in association with yield - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Muhammad Aown Sammar Raza; Shakeel Ahmad Anjum; Arshad Hussain (Cereal Research Communications, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

Changes in human heat discomfort and its drivers in Bangladesh - Adila Tanim Ekra; Mohammed Magdy Hamed; Zulfiqar Ali; Mohd Khairul Idlan Bin Muhammad; Md Munir Hayet Khan; Mohammad Kamruzzaman; Shamsuddin Shahid (Urban Climate, 2024)

Bioactive compounds isolated from Solanum nigrum remarkably inhibit cancerous activity in cancer cell lines - Aisha Nawaz; Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Shafia Arshad; Zeeshan Shamim (South African Journal of Botany, 2024)

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Ecotoxicity of the fluoroquinolone antibiotic delafloxacin to the water flea Simocephalus vetulus and its offspring under the influence of calcium modulation - Tan-Duc Nguyen; Tomoaki Itayama; Quang Vinh Tran; Thanh-Son Dao; Muhammad Shahid Iqbal; Thanh Luu Pham (Science of The Total Environment, 2024)

Biomonitoring potentially toxic elements in atmospheric particulate matter of greater Dhaka region using leaves of higher plants - Zuairia Binte Jashim; Saif Shahrukh; Shahid Akhtar Hossain; Jahan-E-Gulshan; Muhammad Nurul Huda; Md. Mominul Islam; Mohammad Enayet Hossain (Environmental Monitoring and Assessment, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Efficacy of different blood meals for the mass rearing of Aedes aegypti (Diptera: Culicidae) population - Shahid Majeed; Muhammad Sufyan; Asim Abbasi; Muhammad Binyameen; Ramish Saleem; Wafa A. H. Alkherb; Shahla Faisal; Jamil Ijaz; Hira Hameed (International Journal of Tropical Insect Science, 2024)

Methyl-salicylate (MeSA)-mediated airborne defence - Muhammad Arslan Mahmood; Muhammad Jawad Akbar Awan; Rubab Zahra Naqvi; Shahid Mansoor (Trends in Plant Science, 2024)

Prediction of drought regulating gene (s) in barley (Hordeum vulgare L.) using express sequence tags (ESTs) through in silico approaches - Muhammad Naveed Shahid; Fatima Maqbool; Saifullah (South African Journal of Botany, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Modelling photoperiod in enhancing hydrogen production from Chlorella vulgaris sp. while bioremediating ammonium and organic pollutants in municipal wastewater - Fatima Musa Ardo; Kuan Shiong Khoo; Mohamad Zulfadhli Ahmad Sobri; Uganeeswary Suparmaniam; Baranitharan Ethiraj; Aliya Fathima Anwar; Sze Mun Lam; Jin Chung Sin; Muhammad Kashif Shahid; Sabah Ansar; Anita Ramli; Jun Wei Lim (Environmental Pollution, 2024)

Occurrence of diverse plant growth promoting bacteria in soybean [Glycine max (L.) Merrill] root nodules and their prospective role in enhancing crop yield - Mohsin Tariq; Nimra Tahreem; Marriam Zafar; Ghulam Raza; Muhammad Shahid; Muhammad Zunair; Wajeeha Iram; Syeda Tahseen Zahra (Biocatalysis and Agricultural Biotechnology, 2024)

Chlorangium ahmadii sp. nov. and Circinaria darelensis sp. nov. two new species of lichenized Ascomycetes from Pakistan - Alla Ud Din; Muhammad Shahid Iqbal; Abdul Nasir Khalid; Abdul Rehman Niazi (Plant Systematics and Evolution, 2024)

Sublethal impacts of Buprofezin and Pyriproxyfen on cotton mealybug Phenacoccus solenopsis through transgenerational hormesis - Sabir Hussain; Khalid Ali Khan; Muhammad Rafiq Shahid; Tooba Ather; Lal Khan; Amna Bibi; Sadia Kanwal; Nadia Hussain Ahmad; Ali Jan Bugti (Phytoparasitica, 2024)

Integrated Continuous Process Design for Crystallisation, Spherical Agglomeration, and Filtration of Lovastatin - Cameron J. Brown; John McGinty; Muhammad T. Islam; Nazer Rajoub; Omid Arjmandi-Tash; Sara Ottoboni; Muhid Shahid; Stephanie J. Urwin; Ye Seol Lee; Magdalene W. S. Chong; Foteini Papathanasiou; Aruna S. Prakash; et al. (Journal of Pharmaceutical Innovation, 2024)
Purpose This work seeks to improve the particle processability of needle-like lovastatin crystals and develop a small-footprint continuous MicroFactory for its production. Methods General conditions for optimal spherical agglomeration of lovastatin crystals and subsequent product isolation are developed, first as batch processes, and then transferred to continuous MicroFactory operation. Results Methyl isobutyl ketone is a suitable bridging liquid for the spherical agglomeration of lovastatin. Practical challenges including coupling unit operations and solvent systems; mismatched flow rates and inconsistent suspension solid loading were resolved. The successful continuous production of lovastatin spherical agglomerates (D 50 = 336 µm) was achieved. Spherical agglomeration increased the density of the bulk lovastatin powder and improved product flowability from poor to good, whilst maintaining lovastatin tablet performance. Conclusion A continuous, integrated MicroFactory for the crystallisation, spherical agglomeration, and filtration of lovastatin is presented with improved product particle processability. Up to 16,800 doses of lovastatin (60 mg) can be produced per day using a footprint of 23 m 2 .

Correction to: Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2024)

Isolation and characterization of Rhizobium from non-leguminous potato plants: New frontiers in Rhizobium research - Tahir Naqqash; Kauser Abdullah Malik; Asma Imran; Sohail Hameed; Muhammad Shahid; Muhammad Kashif Hanif; Afshan Majeed; Muhammad Arshad; Jan Dirk van Elsas (Biology and Fertility of Soils, 2024)

Retraction Note: evaluating the environmental impact and economic practicability of solar home lighting systems: a roadmap towards clean energy for ecological sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Muhammad Sajjad Hussain; Muhammad Arshad (Environmental Science and Pollution Research, 2024)

Retraction Note: Economic development, social media awareness, and technological innovation in biogas sector under climate change in the post-COVID-19 pandemic conditions - Shahid Ali; Qingyou Yan; Azer Dilanchiev; Muhammad Irfan; Narmina Balabeyova (Environmental Science and Pollution Research, 2024)

Does no-till crop management mitigate gaseous emissions and reduce yield disparities: An empirical US-China evaluation - Awais Shakoor; Elise Pendall; Muhammad Saleem Arif; Taimoor Hassan Farooq; Shahid Iqbal; Sher Muhammad Shahzad (Science of The Total Environment, 2024)

Response to Comments on “Effect of soil amendments on trace element-mediated oxidative stress in plants: Meta-analysis and mechanistic interpretations” by Shahid (2021) - Muhammad Shahid (Journal of Hazardous Materials, 2024)

Identifying changes to key APSIM-wheat constants to sensibly simulate high temperature crop response in Pakistan - Muhammad Rizwan Shahid; Abdul Wakeel; Muhammad Sana Ullah; Donald S. Gaydon (Field Crops Research, 2024)

Teat morphology across five buffalo breeds: a multi-country collaborative study - Carlo Boselli; Angela Costa; Massimo De Marchi; Muhammad A. Zia; Muhammad Q. Shahid; Nasim Ahmad; Ivan Fasulkov; Manol Karadaev; Yordanka Ilieva; Pencho Penchev; Fatemeh Derisavi; Mohammad Nikookar; et al. (Tropical Animal Health and Production, 2024)

Algae-derived bioactive compounds as potential pharmaceuticals for cancer therapy: A comprehensive review - Lubna Anjum Minhas; Muhammad Kaleem; Hafiz Muhammad Umer Farooqi; Farzana Kausar; Rooma Waqar; Theophilus Bhatti; Shahid Aziz; Dong Won Jung; Abdul Samad Mumtaz (Algal Research, 2024)

Rooftop rainwater harvesting potential for kitchen gardening in the Rawal watershed, Pakistan - Ghani Akbar; Shahid Hameed; Zafar Islam; Muhammad Asif; Arshad Ashraf (Arabian Journal of Geosciences, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Gene drive in plants emerges from infancy - Muhammad Jawad Akbar Awan; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2024)

Enhancing silk dyeing with eco-friendly colorant extracted from Cassia fistula brown pods using green mordants - Mariam Younis; Shahid Adeel; Muhammad Zulqurnain Haider; Rony Mia; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Ecofriendly process optimization of natural dye extraction from clove (Syzygium aromaticum L.) using response surface methodology and artificial neural network modeling - Muhammad Aftab; Tanvir Ahmad; Shahid Adeel; Maria Javed (Sustainable Chemistry and Pharmacy, 2024)

Microwave-assisted cleaner extraction of tannin from Terminalia chebula: A promising green method for sustainable leather dyeing - Marwa Bashir; Shahid Adeel; Muhammad Aftab; Rony Mia; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Spatially explicit estimation of freshwater fish stock biomass with limited data: A case study of an endangered endemic fish on the Tibetan Plateau, China - Kunyuan Wanghe; Shahid Ahmad; Xin Zhou; Fei Tian; Sijia Liu; Bingzheng Zhou; Ghulam Nabi; Guojie Wang; Kemao Li; Shenglong Jian; Huamin Jiang; Shengxue Chen; et al. (Science of The Total Environment, 2024)

Alleviated lead toxicity in rice plant by co-augmented action of genome doubling and TiO2 nanoparticles on gene expression, cytological and physiological changes - Fozia Ghouri; Munazzam Jawad Shahid; Minghui Zhong; Muhammad Azam Zia; Sarah Owdah Alomrani; Jingwen Liu; Lixia Sun; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Soil Application of Potassium Maintains Growth, Water Relations, Yield and Seed Quality of Quinoa in Salt Affected Soils - Mehmood Ejaz; Muhammad Amir Bakhtavar; Shahid Iqbal; Mahmood Alam Khan; Raheela Jabeen; Nazish Jabeen; Ali Raza (Journal of Crop Health, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

A novel approach for evaluation of CMIP6 GCMs in simulating temperature and precipitation extremes of Pakistan - Zulfiqar Ali; Mohammad Magdy Hamed; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid (International Journal of Climatology, 2024)
The study used a hybrid approach to evaluate the performance of 20 global climate models (GCMs) from CMIP6 in reproducing 20 extreme temperature and precipitation indices over Pakistan. This study first analysed the future simulations of extremes and discarded the GCMs whose projections fell outside the 95% confidence interval. The remaining GCMs' performance was evaluated using the Kling Gupta Efficiency‐based criteria. The changes in extreme climatic events in Pakistan were projected using the multi‐model ensemble (MME) median of the selected GCMs for four shared socioeconomic pathways (SSPs) in two future periods, 2020–2059 and 2060–2099. Four GCMs' showed inconsistency in projecting future climatic extremes and were discarded initially. The past performance of the remaining GCMs revealed EC‐Earth3‐Veg‐LR, GFDL‐ESM4, MRI‐ESM2‐0 and NOR‐ESM2‐MM to be effective in reproducing extreme indices for the historical period. The MME median of the selected GCMs showed a gradual increase in most of the temperature and precipitation extreme indices in the future periods for all SSPs across the country. Specifically, it showed a higher increase in daily maximum temperature (TXx) by 4.5–5°C, daily minimum temperature (TNn) by more than 4.5°C, consecutive days with a temperature higher than the 95th percentile (WSDI) by >160 days, one‐day maximum rainfall by 9–15 mm and days with precipitation above the 95th percentile by >50 mm in northern high‐elevated areas during 2060–2099 for SSP585. Similarly, a higher increase in TXx by 4.5–5°C, TNn by >4.5°C, WSDI by 140 days and tropical nights by 40–60 days was also found in the western arid region during 2060–2099 for SSP585. The study highlights that northern high‐elevated and western arid regions are at a higher risk of extreme temperatures and precipitation due to climate change.

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

Ultrafiltration membrane fabricated from polyethylene terephthalate plastic waste for treating microalgal wastewater and reusing for microalgal cultivation - Hemamalini Rawindran; Nur Arif bin Hut; Dhita Karunia Vrasna; Pei Sean Goh; Jun Wei Lim; Chin Seng Liew; Chii-Dong Ho; Hooi-Siang Kang; Muhammad Kashif Shahid; Hui-Suan Ng; Mohamed A. Habila; Kuan Shiong Khoo (Chemosphere, 2024)

Exploration of microplastic concentration in indoor and outdoor air samples: Morphological, polymeric, and elemental analysis - Khadija Sharaf Din; Muhammad Fahim Khokhar; Shahid Ikramullah Butt; Abdul Qadir; Farhan Younas (Science of The Total Environment, 2024)

How can natural resource dependence, environmental-related technologies and digital trade protect the environment: Redesigning SDGs policies for sustainable environment? - Muhammad Zubair Ashraf; Wei Wei; Muhammad Usman; Shahid Mushtaq (Resources Policy, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Advanced nanomaterials and metal-organic frameworks for catalytic bio-diesel production from microalgal lipids – A review - Zohaib Saddique; Muhammad Imran; Shoomaila Latif; Ayesha Javaid; Shahid Nawaz; Nemira Zilinskaite; Marcelo Franco; Ausra Baradoke; Ewa Wojciechowska; Grzegorz Boczkaj (Journal of Environmental Management, 2024)

Scalable synthesis of MOF-derived Nd2O3@C and V2O5@C nanohybrid: Efficient electrocatalyst for OER in alkaline medium - Tauseef Munawar; Ambreen Bashir; Muhammad Shahid Nadeem; Faisal Mukhtar; Sumaira Manzoor; Muhammad Naeem Ashiq; Shoukat Alim Khan; Muammer Koc; Faisal Iqbal (Fuel, 2024)

Correction: Molecular characterization of bread quality contributing high and low‑molecular‑weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Molecular characterization of bread quality contributing high and low-molecular-weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Salinity effects on the consistency limits and shear strength of cohesive soils of the Red River, Fargo, North Dakota - Muhammad Shahid Iqbal; Stephanie S. Day (Bulletin of Engineering Geology and the Environment, 2024)

Zinc Oxide Nanoparticles Significant Role in Poultry and Novel Toxicological Mechanisms - Arjmand Fatima; Tean Zaheer; Kaushik Pal; Rao Zahid Abbas; Tayyaba Akhtar; Sultan Ali; Muhammad Shahid Mahmood (Biological Trace Element Research, 2024)

Effect of hydrodynamic aeration on bioelectricity generation from photoautotrophic Spirulina platensis in biophotovoltaic devices - Jia-Chun Chin; Fong-Lee Ng; Hooi-Siang Kang; Binbin Li; Pei Sean Goh; Jun Wei Lim; Ayman A. Ghfar; Abdallah A.A. Mohammed; Muhammad Kashif Shahid (Algal Research, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

RETRACTED ARTICLE: Techno-economic analysis of biogas production from domestic organic wastes and locally sourced material: the moderating role of social media based-awareness - Shahid Ali; Qingyou Yan; Huaping Sun; Muhammad Irfan (Environmental Science and Pollution Research, 2023)

Effect of multiwalled carbon nanotubes on compressive behavior of concrete at elevated temperature for mass concreting - Kashan Nisar; Muhammad Shahid Siddique; Muhammad Rizwan; Syed Hassan Farooq; Muhammad Usman; Asad Hanif (European Journal of Environmental and Civil Engineering, 2023)

Modulation of metal transporters, oxidative stress and cell abnormalities by synergistic application of silicon and titanium oxide nanoparticles: A strategy for cadmium tolerance in rice - Mingyu Lai; Fozia Ghouri; Samreen Sarwar; Sarah Owdah Alomrani; Muhammad Riaz; Fasih Ullah Haider; Jingwen Liu; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Chemosphere, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Climate change variables modify microbial community structure and soil enzymes involved in nitrogen and phosphorus metabolism - Muhammad Bashir Ahmed Siddique; Azeem Khalid; Allah Ditta; Shahid Mahmood; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Rhizosphere, 2023)

Coal fly ash supported Ag@Bi2WO6: A novel heterogeneous nanocomposite for effective sunlight driven photocatalytic degradation of dye - Muhammad Zubair Saleem; Nimra Nadeem; Muhammad Shahbaz; Nabil Al-Zaqri; Shahid Rasul; Saima Noreen; Muhammad Zahid; Imran shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Friedelin and Glutinol induce neuroprotection against ethanol induced neurotoxicity in pup’s brain through reduction of TNF-α, NF-kB, caspase-3 and PARP-1 - Marva Sandhu; Hafiz Muhammad Irfan; Laiba Arshad; Aman Ullah; Shahid Ali Shah; Hussain Ali (NeuroToxicology, 2023)

Tricks and tracks in resource recovery from wastewater using bio-electrochemical systems (BES): A systematic review on recent advancements and future directions - Lavanya Addagada; Mukesh Goel; Muhammad Kashif Shahid; Sundramurthy Venkatesa Prabhu; Sasmita Chand; Naresh Kumar Sahoo; Prangya Ranjan Rout (Journal of Water Process Engineering, 2023)

Comprehensive analysis of greenhouse gas emissions and emission factors in a Korean domestic wastewater treatment plant: Insights into mechanisms and pathways for climate change mitigation - Muhammad Kashif Shahid; Younggyun Choi (Journal of Water Process Engineering, 2023)

Potential of milk fat globule membrane's phospholipids and anhydrous milk fat based nanostructured lipid carriers for enhanced bioaccessibility of vitamin D3 - Bina Zarif; Muhammad Haris; Ramla Shahid; Tauqir A. Sherazi; Abdur Rahman; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Proteosomes based on milk phospholipids and proteins to enhance the stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Ramla Shahid; Tayyaba Noor; Muhammad Imran (Food Chemistry, 2023)

Modeling the energy mix and economic costs of deep decarbonization scenarios in a CGE framework - Elisabeth A. Gilmore; Madanmohan Ghosh; Peter Johnston; Muhammad-Shahid Siddiqui; Nick Macaluso (Energy and Climate Change, 2023)

Recent advances in chitosan-based materials; The synthesis, modifications and biomedical applications - Yasir Iqbal; Iqbal Ahmed; Muhammad Faisal Irfan; Shahzad Ali Shahid Chatha; Muhammad Zubair; Aman Ullah (Carbohydrate Polymers, 2023)

An Integrated Approach for Biodegradation of Toxic Azo Dyes and Wastewater Recycling by Azoreductase Gene–Harboring Bacillus paramycoides Strain AM-3 - Awais Maqsood; Khola Tazeen; Sabir Hussain; Faisal Mahmood; Muhammad Shahid (Water, Air, & Soil Pollution, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Fine mapping and candidate gene analysis of a major QTL for oil content in the seed of Brassica napus - Qing Zhao; Jian Wu; Lei Lan; Muhammad Shahid; Muhammad Uzair Qasim; Kaidi Yu; Chunyu Zhang; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2023)

Genetic insights into crossbred dairy cattle of Pakistan: exploring allele frequency, linkage disequilibrium, and effective population size at a genome-wide scale - Fakhar un Nisa; Haiba Kaul; Muhammad Asif; Imran Amin; Raphael Mrode; Shahid Mansoor; Zahid Mukhtar (Mammalian Genome, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Arsenic level in groundwater and biological samples in Khanewal, Pakistan - Najeeb Ullah Khan; Muhammad Shahid; Sana Khalid; Natasha Natasha; Zeid A. Alothman; Abdullah A. Al-Kahtani; Muhammad Imran; Behzad Murtaza (Environmental Geochemistry and Health, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

Chromium removal from aqueous solution using bimetallic Bi0/Cu0-based nanocomposite biochar - Behzad Murtaza; Aqsa Naseer; Muhammad Imran; Noor S. Shah; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Muhammad Shahid; Jibran Iqbal; Ghulam Abbas; Natasha Natasha; Muhammad Amjad (Environmental Geochemistry and Health, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Comparative Analysis of IgG Antibody Titers Induced by Three Different SARS-COV-2 Vaccines in Healthy Adults of Pakistan - Nayab Batool Rizvi; Hassam Farooq; Qaiser Alam Khan; Muhammad Zeeshan Rana; Sehrish Zaffar; Muhammad Shahid; Nazim Hussain (Current Microbiology, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Comprehensive evaluation of hydro-chemical processes, suitability, health risks, and sources of groundwater contamination using compositional data analysis, Nizampur basin, Pakistan - Assad Ullah; Wajid Ali; Said Muhammad; Jehangir Ijaz; Faseeha Amir; Shahid Iqbal (Groundwater for Sustainable Development, 2023)

3D cellular lattice like-Ti3C2 MXene based aerogels embedded with metal selenides particles for energy storage and water splitting applications - Khadija Chaudhary; Beriham Basha; Sonia Zulfiqar; Sheraz Yousaf; Eric W. Cochran; M.S. Al-Buriahi; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2023)

Sugarcane-bagasse-ash in enhanced mesophilic Co-digestion for biogas and nutrient recovery: A concept of developing rural circular bioeconomy - Shahid Mumtaz; Yasir Abbas; Iftikhar Ahmad; Ahmed Hassan; Muhammad Farhan Saeed; Sining Yun; Zainab M. Almarhoon; Mohamed Shelkh; Ahmed M. Hassan; P. Rosaiah; Maduru Suneetha; Awais Ahmad (Environmental Research, 2023)

Deciphering the Impact of Acinetobacter sp. SG-5 Strain on Two Contrasting Zea mays L. Cultivars for Root Exudations and Distinct Physio-Biochemical Attributes Under Cadmium Stress - Saghir Abbas; Muhammad Tariq Javed; Muhammad Shahid; Kashif Tanwir; Muhammad Hamzah Saleem; Nabeel Khan Niazi (Journal of Plant Growth Regulation, 2023)

Does biogas energy influence the sustainable development of entrepreneurial business? An application of the extended theory of planned behavior - Shahid Ali; Qingyou Yan; Muhammad Irfan; Fengyi Ai; Huaping Sun; Zhang Xiaochun (Environmental Science and Pollution Research, 2023)

Performance evaluation of CMIP6 GCMs for the projections of precipitation extremes in Pakistan - Zulfiqar Ali; Mohammad Magdy Hamed; Mohd Khairul Idlan Muhammad; Zafar Iqbal; Shamsuddin Shahid (Climate Dynamics, 2023)

The impact of CSR and green consumption on consumer satisfaction and loyalty: moderating role of ethical beliefs - Sohail Ahmad; Muhammad Irfan Shakir; Afshan Azam; Shahid Mahmood; Qingyu Zhang; Zaheer Ahmad (Environmental Science and Pollution Research, 2023)

An efficient virus-induced gene silencing of PDS gene in Solanum lycopersicum (cv. Rio Grande) and its functional analysis - Iqra Mehboob; Muhammad Mughees; Ayesha Baig; Shaukat Ali; Yasar Sajjad; Shahid Iqbal; Zahoor Hussain; Sajid Fiaz; Farhat Abbas; Kotb A. Attia; Asmaa M. Abushady; Mohammad Maroof Shah (Brazilian Journal of Botany, 2023)

Environmental friendly utilization of plant wastes in combination as a source of natural colorants for binary mordanted silk dyeing - Nimra Amin; Shahid Adeel; Fazal-ur-Rehman; Muhammad Naveed Anjum (Environmental Science and Pollution Research, 2023)

Occurrence and characterization of Alternaria alternata causing leaf spot of soybean (Glycine max) in Pakistan - Muhammad Ismail Buzdar; Nasim Ahmed; Muhammad Jawad Akbar Awan; Saleem. Ur-Rahman; Muhammad Abu Bakar Waqas; Ghulam Raza; Fathia Mubeen; Shahid Mansoor; Imran Amin (Journal of Plant Pathology, 2023)

Microbe-oriented nanoparticles as phytomedicines for plant health management: An emerging paradigm to achieve global food security - Muhammad Noman; Temoor Ahmed; Usman Ijaz; Amir Hameed; Muhammad Shahid; Azizullah; Dayong Li; Fengming Song (Critical Reviews in Food Science and Nutrition, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Microwave-assisted santalin extraction from Pterocarpus santalinus for mordanted woolen yarn dyeing - Maria Mahboob; Shahid Adeel; Samra Barkaat; Tanvir Ahmad; Meral Özomay; Rony Mia; Somayeh Mirnezhad; Muhammad Zuber (Sustainable Chemistry and Pharmacy, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Bifunctional photothermal membrane for high-temperature interfacial solar steam generation and off-grid sterilization - Laila Noureen; Shahid Zaman; Waqas Ali Shah; Qian Wang; Muhammad Humayun; Qiyong Xu; Xinwei Wang (Chemical Engineering Journal, 2023)

Sunlight filtered via translucent-colored polyvinyl chloride sheets enhanced the light absorption capacity and growth of Arthrospira platensis cultivated in a pilot-scale raceway pond - Santosh Kumar; Ameer Ali Kubar; Feifei Zhu; Cong Shao; Yi Cui; Xinjuan Hu; Jiheng Ni; Muhammad Abdur Rehman Shah; Shengjie Ding; Shahid Mehmood; Shuhao Huo (Bioresource Technology, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

A new species of Lobothallia (Megasporaceae, Pertusariales, Ascomycota) from Pakistan - Rizwana Zulfiqar; Fatima Razzaq; Muhammad Shahid Iqbal; Abdul Nasir Khalid (Plant Systematics and Evolution, 2023)

Genome-wide analysis and expression profiling of YUCCA gene family associated with plant vigor in Japanese apricot (prunus mume Sieb. Et zucc) - Faisal Hayat; Yang Bai; Shahid Iqbal; Chengdong Ma; Muhammad Moaaz Ali; Muhammad Adnan Shahid; Mahmood Ul Hasan; Walid F. A. Mosa; Ummara Khan; Huang Xiao; Zhihong Gao (Horticulture, Environment, and Biotechnology, 2023)

Sustainable production of bread wheat using laser land levelling and sowing methods as potent regulators of carbon sequestration, fuel consumption and water use in the arid environment of Bahawalpur, Pakistan - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Shakeel Ahmad Anjum; Arshad Hussain (Irrigation and Drainage, 2023)
Excessive use of water in wheat is associated with high fuel consumption and the emission of carbon dioxide into the environment. This study was conducted with the objectives to decrease water use and the associated fuel consumption and carbon dioxide emissions and to improve the productivity of wheat on a sustainable basis using LASER levelling and sowing methods as potent modulators of these adversities. The experiment was conducted in the research area of the Agronomic Research Station Bahawalpur over 3 years using a split‐plot experimental design and four replications. Treatments contained LASER levelling in the main plot (L 0 = no LASER levelling, L 1 = LASER levelling) and sowing methods in split plots (S 1 = broadcast, S 2 = ridge sowing and S 3 = drill sowing). Less water use, fuel consumption and emission of carbon dioxide were quantified under ‘LASER levelling’ and under ‘ridge sowing’ compared to other treatments. Regarding wheat crop productivity, the same treatment combination (LASER levelling and ridge sowing) resulted in more fertile tillers, grains per spike, 1000‐grain weight and grain yield. Therefore, we concluded that ‘LASER levelling’ and ‘ridge sowing’ have the potential to reduce the cost involved and environmental pollution (by reducing fuel consumption) and improve water use efficiency, grain yield and yield components of wheat compared to other treatments. Moreover, strong negative associations of water use, fuel consumption and carbon dioxide emissions with the grain yield of wheat were recorded.

RETRACTED ARTICLE: Inquiring asymmetric effects of oil prices, money supply, and domestic debt on consumer prices: an empirical evidence from Pakistan - Muhammad Shahid Hassan; Najam ul Hassan; Rukhsana Kalim; Muhammad Ibrahim Saeed; Haider Mahmood (Environmental Science and Pollution Research, 2023)

Large-scale wind power grid integration challenges and their solution: a detailed review - Muhammad Shahid Mastoi; Shengxian Zhuang; Malik Haris; Mannan Hassan; Asif Ali (Environmental Science and Pollution Research, 2023)

Investigating symmetrical influence of economic expansion, oil price, and industrial production on trade deficit: a policy pathway toward three neighboring Asian states - Muhammad Bilal Arif; Arshad Mahmood Malik; Gulnaz Hameed; Aadil Hameed Shah; Nigah Hussain; Rabia Shahid (Environmental Science and Pollution Research, 2023)

Viral vectors as carriers of genome-editing reagents - Muhammad Jawad Akbar Awan; Afzal Akram; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2023)

Chemical profiling and biological activities of Dipterygium glaucum Decne.: An in-vivo, in-vitro and in-silico evaluation - Afia Shahid; Duraiz Ahmed Khan; Hanan Y. Aati; Asmaa E. Sherif; Chitchamai Ovatlarnporn; Musaddique Hussain; Huma Rao; Muhammad Imran Khan; Muhammad Younus; Abdul Basit; Kashif ur Rehman Khan (South African Journal of Botany, 2023)

Moringa oleifera: Processing, phytochemical composition, and industrial applications - Karima Gharsallah; Leila Rezig; Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; M.Abbas Ali; Sook Chin Chew (South African Journal of Botany, 2023)

Identification, characterization and expression profiling of salt-stress responsive proteinase inhibitor in Gossypium arboreum L. - Muhammad Naveed Shahid; Sarfraz Kiani; Bushra Rashid; Tayyab Husnain (South African Journal of Botany, 2023)

Effect of NDF levels of complete pelleted diet and dietary transition period on rumen pH, growth performance, digestibility, and blood indices in fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

The protective role of tetraploidy and nanoparticles in arsenic-stressed rice: Evidence from RNA sequencing, ultrastructural and physiological studies - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Lixia Sun; Muhammad Riaz; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Pleiotropic melatonin-mediated responses on growth and cadmium phytoextraction of Brassica napus: A bioecological trial for enhancing phytoremediation of soil cadmium - Saiqa Menhas; Xijia Yang; Kashif Hayat; Jochen Bundschuh; Xunfeng Chen; Nan Hui; Dan Zhang; Shaohua Chu; Yuanfei Zhou; Esmat F. Ali; Muhammad Shahid; Jörg Rinklebe; et al. (Journal of Hazardous Materials, 2023)

Fundamental alteration of cellular biochemicals from attached microalgae onto palm kernel expeller waste upon optimizing the growth environment in forming adhesion complex - Hemamalini Rawindran; Kuan Shiong Khoo; Baranitharan Ethiraj; Uganeeswary Suparmaniam; Wai Hong Leong; Ratchaprapa Raksasat; Chin Seng Liew; Nurul Tasnim Sahrin; Man Kee Lam; Worapon Kiatkittipong; Jun Wei Lim; Zakariyya Uba Zango; et al. (Environmental Research, 2023)

RETRACTED: Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2023)

Environmental impact assessment of the manufacturing of glass packaging solutions: Comparative scenarios in a developing country - Muhammad Usman Ali Khan; Shamraiz Ahmad; Shahid Ikramullah Butt (Environmental Impact Assessment Review, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Does Exogenous Selenium Elicited Biochemical Regulations Make Economic Improvements in Terminally Heat-Stressed Bread Wheat? An Evidence from Marginal Analysis - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Bao-Luo Ma; Shakeel Ahmad Anjum; Arshad Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Predicting chemical speciation of metals in soil using Visual Minteq - Sana Khalid; Muhammad Shahid; Zeid A. Alothman; Abdullah A. Al-Kahtani; Behzad Murtaza; Camille Dumat (Soil Ecology Letters, 2023)

Can bioenergy act as an entrepreneurial opportunity for the sustainable economic development of an emerging economy? A socio-technical approach - Shahid Ali; Qingyou Yan; Jin Hu; Muhammad Irfan; Huaping Sun (Environmental Science and Pollution Research, 2023)

Recent trends in environmental sustainability - Muhammad Shahid; Hafiz Faiq Bakhat; Ghulam Mustafa Shah; Behzad Murtaza (Environmental Science and Pollution Research, 2023)

Global digital divide and environmental degradation in Africa - Sana Sarwar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum; Azeem Sardar; Nazia Yasmeen; Rameen Shahid (Environmental Science and Pollution Research, 2023)

WeiTsing: A guard of the stele - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Shahid Mansoor (Molecular Plant, 2023)

Milk phospholipids and buttermilk based composite nanosystems for enhanced stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Abdur Rahman; Tauqir A. Sherazi; Ramla Shahid; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Microwaves as sustainable approach for artificial ripening of date fruit cv. Khupra to reduce fruit waste - Tayyaba Alvi; Muhammad Kashif Iqbal Khan; Abid Aslam Maan; Muhammad Shahid; Shyam Sablani (Food Bioscience, 2023)

Usage of the XGBoost and MARS algorithms for predicting body weight in Kajli sheep breed - Asim Faraz; Cem Tırınk; Hasan Önder; Uğur Şen; Hafiz Muhammad Ishaq; Nasir Ali Tauqir; Abdul Waheed; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2023)

Phytohormones Mediated Modulation of Abiotic Stress Tolerance and Potential Crosstalk in Horticultural Crops - Muhammad Ahsan Altaf; Rabia Shahid; Ravinder Kumar; Muhammad Mohsin Altaf; Awadhesh Kumar; Latif Ullah Khan; Muhammad Saqib; Muhammad Azher Nawaz; Bushra Saddiq; Saraj Bahadur; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

Surface water quality, public health, and ecological risks in Bangladesh—a systematic review and meta-analysis over the last two decades - Hazrat Bilal; Xiaowen Li; Muhammad Shahid Iqbal; Yonglin Mu; Roberto Xavier Supe Tulcan; Muhammad Asad Ghufran (Environmental Science and Pollution Research, 2023)

Assessment of lithium bioaccumulation by quinoa (Chenopodium quinoa willd.) and its implication for human health - Saira Afzal; Hafiz Faiq Bakhat; Muhammad Shahid; Ghulam Mustafa Shah; Ghulam Abbas (Environmental Geochemistry and Health, 2023)

Use of agricultural bio-wastes to remove arsenic from contaminated water - Zunaira Shabbir; Muhammad Shahid; Natasha; Sana Khalid; Samina Khalid; Muhammad Imran; Muhammad Imran Qureshi; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

A critical analysis of wastewater use in agriculture and associated health risks in Pakistan - Natasha; Muhammad Shahid; Sana Khalid; Behzad Murtaza; Hasnain Anwar; Ali Haidar Shah; Aneeza Sardar; Zunaira Shabbir; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - Yousra Riaz; Samra Barkaat; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Muhammad Zuber; Meral Ozomay; Shahnaz Parveen Khattak (Environmental Science and Pollution Research, 2023)

Sustainable utilization of apple pomace and its emerging potential for development of functional foods - Muhammad Asif; Tahreem Javaid; Zafar Ullah Razzaq; Muhmmad Kashif Iqbal Khan; Abid Aslam Maan; Saria Yousaf; Ayesha Usman; Sidra Shahid (Environmental Science and Pollution Research, 2023)

Effective assessment of biopolymer-based multifunctional sorbents for the remediation of environmentally hazardous contaminants from aqueous solutions - Shahid Nawaz; Andleeb Tabassum; Sara Muslim; Tayyaba Nasreen; Ausra Baradoke; Tak H. Kim; Grzegorz Boczkaj; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Plant disease management with amelioration of systemic resistance in soybean by endophytic fungi associated with GC-MS metabolic profiling of Chaetomium sp., - Hafiza Farhat; Faizah Urooj; Nida Sohail; Shahid Ullah; Muhammad Shaiq Ali (Physiological and Molecular Plant Pathology, 2023)

Synergistic photocatalytic performance of Fe@Fe2O3 core-shell nanostructures supported on g-C3N4 nanosheets for RhB and phenol decolorization: Fabrication, characterization, and mechanistic insights - Shahid Iqbal; Jianjun Liu; Hecheng Ma; Wenqi Liu; Shengli Zuo; Yingchun Yu; Ni Yan; Muhammad Asim Mushtaq (Journal of Water Process Engineering, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

Impact of alternate Mn doping in ternary nanocomposites on their structural, optical and antimicrobial properties: Comparative analysis of photocatalytic degradation and antibacterial activity - Noor Tahir; Muhammad Zahid; Asim Jillani; Suman Tahir; Muhammad Yaseen; Qamar Abbas; Rana Abdul Shakoor; Syed Zajif Hussain; Imran Shahid (Journal of Environmental Management, 2023)

Boosting the electrochemical activities of MnO2 for next-generation supercapacitor application: Adaptation of multiple approaches - Muhammad Usman Khalid; Khadijah Mohammedsaleh Katubi; Sonia Zulfiqar; Z.A. Alrowaili; Muhammad Aadil; M.S. Al-Buriahi; Muhammad Shahid; Muhammad Farooq Warsi (Fuel, 2023)

Seasonal variation in non-point source heavy metal pollution in Satpara Lake and its toxicity in trout fish - Hamid Hussain; Shahid Mahmood; Azeem Khalid; Khurram Shahzad; Muhammad Zubair Anjum (Environmental Monitoring and Assessment, 2023)

Recent progress on the heavy metals ameliorating potential of engineered nanomaterials in rice paddy: a comprehensive outlook on global food safety with nanotoxicitiy issues - Temoor Ahmed; Muhammad Noman; Muhammad Rizwan; Shafaqat Ali; Muhammad Shafiq Shahid; Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Cellular and Non-cellular Antioxidant Properties of Vitamin E–Loaded Metallic-Quercetin/Polycaprolactone Nanoparticles for the Treatment of Melanogenesis - Nasreen Ramzan; Muhammad Azeem; Khalid Mahmood; Shahid Shah; Fazal Rahman Sajid Chughtai; Muhammad Hanif; Nabeela Ameer; Zakia Bashir; Farhan Siddique; Muhammad Qaisar (AAPS PharmSciTech, 2023)

Sustainable green revolution through the development of solar power projects in Pakistan: a techno-economic analysis - Shahid Ali; Qingyou Yan; Huaping Sun; Muhammad Irfan (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Economic development, social media awareness, and technological innovation in biogas sector under climate change in the post-COVID-19 pandemic conditions - Shahid Ali; Qingyou Yan; Azer Dilanchiev; Muhammad Irfan; Narmina Balabeyova (Environmental Science and Pollution Research, 2023)

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

A graft that crafts nontransgenic and genome-edited plants - Muhammad Jawad Akbar Awan; Muhammad Qasim Aslam; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2023)

Phytochemical analysis, in-vitro biological activities and Pearson correlation of total polyphenolic content with antioxidant activities of Ziziphus mauritiana fruit pulp and seed during different ripening stages - Shehla Parveen; Naeema Bukhari; Mamona Nazir; Waseem Akhtar Qureshi; Asma Yaqoob; Muhammad Shahid (South African Journal of Botany, 2023)

The role of natural resources, clean energy and technology in mitigating carbon emissions in top populated countries - Meihan Liu; Shi Baisheng; Majed Alharthi; Muhammad Shahid Hassan; Imran Hanif (Resources Policy, 2023)

Investigating resource curse/blessing hypothesis: An empirical insights from Luxembourg, the Netherlands, and Portugal economies - Shengming Chen; Muhammad Shahid Hassan; Ayesha Latif; Abdul Rafay; Haider Mahmood; Xiaowei Xu (Resources Policy, 2023)

Spatial distribution and accumulation of arsenic in biological samples and associated health risks by drinking groundwater in Bahawalnagar, Pakistan - Muhammad Shahid; Sana Khalid; Natasha Natasha; Tasveer Zahra Tariq; Zeid A. Alothman; Abdullah A. Al-Kahtani; Muhammad Imran; Behzad Murtaza (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Frugal innovation as a source of sustainable entrepreneurship to tackle social and environmental challenges - Muhammad Shehryar Shahid; Mokter Hossain; Subhan Shahid; Tehreem Anwar (Journal of Cleaner Production, 2023)

Green synthesis of iron oxide nanoparticles using Bombax malabaricum for antioxidant, antimicrobial and photocatalytic applications - Sunmbal Awais; Hira Munir; Jawayria Najeeb; Fozia Anjum; Khalida Naseem; Naghmana Kausar; Muhammad Shahid; Muhammad Irfan; Nayra Najeeb (Journal of Cleaner Production, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Estimation of G × E Interaction of Lentil Genotypes for Yield using AMMI and GGE Biplot in Pakistan - Maria Ghaffar; Muhammad Jawad Asghar; Muhammad Shahid; Jaffar Hussain (Journal of Soil Science and Plant Nutrition, 2023)

RETRACTED ARTICLE: Evaluating the environmental impact and economic practicability of solar home lighting systems: a roadmap towards clean energy for ecological sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Muhammad Sajjad Hussain; Muhammad Arshad (Environmental Science and Pollution Research, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Improving Significant Wave Height Prediction Using a Neuro-Fuzzy Approach and Marine Predators Algorithm - Rana Muhammad Adnan Ikram; Xinyi Cao; Tayeb Sadeghifar; Alban Kuriqi; Ozgur Kisi; Shamsuddin Shahid (Journal of Marine Science and Engineering, 2023)
This study investigates the ability of a new hybrid neuro-fuzzy model by combining the neuro-fuzzy (ANFIS) approach with the marine predators’ algorithm (MPA) in predicting short-term (from 1 h ahead to 1 day ahead) significant wave heights. Data from two stations, Cairns and Palm Beach buoy, were used in assessing the considered methods. The ANFIS-MPA was compared with two other hybrid methods, ANFIS with genetic algorithm (ANFIS-GA) and ANFIS with particle swarm optimization (ANFIS-PSO), in predicting significant wave height for multiple lead times ranging from 1 h to 1 day. The multivariate adaptive regression spline was investigated in deciding the best input for prediction models. The ANFIS-MPA model generally offered better accuracy than the other hybrid models in predicting significant wave height in both stations. It improved the accuracy of ANFIS-PSO and ANFIS-GA by 8.3% and 11.2% in root mean square errors in predicting a 1 h lead time in the test period.

Sustainable environment quality: moderating role of renewable energy consumption in service sector for selected HDR listed countries - Mubasher Iqbal; Muhammad Shahid Hassan; Noman Arshed (Environmental Science and Pollution Research, 2023)

Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - Shahid Adeel; Hira Akram; Muhammad Usman; Tanveer Hussain Bokhari; Muhammad Aftab; Meral Ozomay (Environmental Science and Pollution Research, 2023)

Relating biogas technology and environmental impact assessment: a roadmap towards clean energy for environmental sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Shah Fahad (Environmental Science and Pollution Research, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

PASTE: a high-throughput method for large DNA insertions - Muhammad Jawad Akbar Awan; Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Shahid Mansoor (Trends in Plant Science, 2023)

Design and economic evaluation of a novel amine-based CO2 capture process for SMR-based hydrogen production plants - Muhammad Zubair Shahid; Jin-Kuk Kim (Journal of Cleaner Production, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

Superior leaf physiological performance contributes to sustaining the final yield of cotton (Gossypium hirsutum L.) genotypes under terminal heat stress - Muhammad Sarwar; Muhammad Farrukh Saleem; Najeeb Ullah; Asjad Ali; Brian Collins; Muhammad Shahid; Muhammad Kashif Munir; Sang-Min Chung; Manu Kumar (Physiology and Molecular Biology of Plants, 2023)

Improving the Spike Initiation and Flowering Stage Heat Tolerance in Bread Wheat Through Foliar Application of Potassium - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Arshad Hussain (Journal of Plant Growth Regulation, 2023)

Removal of Toxic Metals from Water by Nanocomposites through Advanced Remediation Processes and Photocatalytic Oxidation - Ahmad Farhan; Misbah Zulfiqar; Samiah; Ehsan Ullah Rashid; Shahid Nawaz; Hafiz M.N. Iqbal; Teofil Jesionowski; Muhammad Bilal; Jakub Zdarta (Current Pollution Reports, 2023)
Purpose of Review Heavy and toxic metals are becoming more prevalent in the water sources of the globe, which has detrimental repercussions for both human health and the health of ecosystems. The summary of recent findings on treatment possibilities of toxic metal species by nanomaterials should facilitate the development of more advanced techniques of their removal. Recent Findings The high concentrations of chromium, mercury, and arsenic identified in wastewater cause a hazard to human health. There is a wide variety of nanoadsorbents and nanophotocatalysts used for heavy/hazardous metal removal. Recent research has resulted in the production of advanced nanostructures that exhibit extraordinary heavy/hazardous metal adsorption effectiveness and photocatalytic diminution of metal ions. These nanostructures have physically and chemically tunable features. Summary In this review article, the use of carbon-based nanomaterials, polymer-based nanomaterials, and semiconductor-based nanomaterials are extensively discussed to remove mercury, chromium, and arsenic ions from wastewater by the adsorption process. Advanced nanomaterials involved in photocatalytic reduction are also comprehensively discussed.

Cottonseed oil: A review of extraction techniques, physicochemical, functional, and nutritional properties - Tahreem Riaz; Muhammad Waheed Iqbal; Shahid Mahmood; Iqra Yasmin; Ali Ahmad Leghari; Abdur Rehman; Anam Mushtaq; Khubaib Ali; Muhammad Azam; Muhammad Bilal (Critical Reviews in Food Science and Nutrition, 2023)

Graphene loaded TiO2 submicron spheres scattering layer for efficient dye-sensitized solar cell - Muhammad Umair Shahid; Norani Muti Mohamed; Ali Samer Muhsan; Siti Nur Azella Zaine; Mehboob Khatani; Asfand Yar; Waqar Ahmad; Muhammad Babar Hussain; Asma A. Alothman; Mohammed Sheikh Saleh Mushab (Chemosphere, 2023)

Semi-supervised adaptive PLS soft-sensor with PCA-based drift correction method for online valuation of NOx emission in industrial water-tube boiler - Saidatul Hasniza Hasnen; Muhammad Shahid; H. Zabiri; Syed Ali Ammar Taqvi (Process Safety and Environmental Protection, 2023)

Polyploidy and zinc oxide nanoparticles alleviated Cd toxicity in rice by modulating oxidative stress and expression levels of sucrose and metal-transporter genes - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Mingyu Lai; Lixia Sun; Jinwen Wu; Xiangdong Liu; Shafaqat Ali; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Biogenic synthesis and characterization of ZnO nanoparticles for degradation of synthetic dyes: A sustainable environmental cleaner approach - Atizaz Rasool; Shumaila Kiran; Tahsin Gulzar; Shazia Abrar; Abdul Ghaffar; Muhammad Shahid; Sofia Nosheen; Saba Naz (Journal of Cleaner Production, 2023)

Mechanistic behaviour of Chlorella vulgaris biofilm formation onto waste organic solid support used to treat palm kernel expeller in the recent Anthropocene - Hemamalini Rawindran; Rabbani Syed; Abdulaziz Alangari; Kuan Shiong Khoo; Jun Wei Lim; Nurul Tasnim Sahrin; Uganeeswary Suparmaniam; Ratchaprapa Raksasat; Chin Seng Liew; Wai Hong Leong; Worapon Kiatkittipong; Muhammad Kashif Shahid; et al. (Environmental Research, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

Seed-borne Curvularia lunata deteriorating seed health and germination of soybean - Muhammad Ismail Buzdar; Muhammad Jawad Akbar Awan; Saleem Ur Rahman; Rubab Zahra Naqvi; Ghulam Raza; Shahid Mansoor; Imran Amin (Biologia, 2023)

Sustainable development goals perspective: nexus between Christians’ religious tourism, geopolitical risk, and CO2 pollution in Italy - Muhammad Zahid Nawaz; Jinguang Guo; Shahid Nawaz; Sadam Hussain (Environmental Science and Pollution Research, 2023)

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

CuO-decorated MOF derived ZnO polyhedral nanostructures for exceptional H2S gas detection - Shahid Hussain; Jesse Nii Okai Amu-Darko; Mingsong Wang; Asma A. Alothman; Mohamed Ouladsmane; Samar A. Aldossari; Muhammad Shahzeb Khan; Guanjun Qiao; Guiwu Liu (Chemosphere, 2023)

Characterisation of bushfire residuals in source water and removal by coagulation - Narada Dayarathne; Michael J. Angove; Muhammad Kashif Shahid; Shukra Raj Paudel; Rupak Aryal; Bandita Mainali (Science of The Total Environment, 2023)

Tissue specific expression of bacterial cellulose synthase (Bcs) genes improves cotton fiber length and strength - Sidra Akhtar; Ahmad Ali Shahid; Sana Shakoor; Mukhtar Ahmed; Sehrish Iftikhar; Muhammad Usmaan; Sahar Sadaqat; Ayesha Latif; Adnan Iqbal; Abdul Qayyum Rao (Plant Science, 2023)

Water adsorption properties of microalgae powders: Thermodynamic analysis and structural characteristics - Xinfeng Cheng; Pan Ling; Muhammad Shahid Iqbal; Fangfang Liu; Jingyan Xu; Xiaoran Wang (Journal of Stored Products Research, 2023)

Current knowledge and implementations of Bemisia tabaci genomic technologies for sustainable control - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Hamid Anees Siddiqui; Imran Amin; Shahid Mansoor (Journal of Pest Science, 2023)

Characterization of tomato leaf curl Palampur virus naturally infecting wild melon in Oman - Muhammad Shafiq Shahid (Indian Phytopathology, 2023)

Effect of freshwater and wastewater irrigation on buildup of toxic elements in soil and maize crop - Muhammad Shahid; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Irshad Bibi; Tasveer Zahra Tariq; Natasha Natasha; Sana Khalid; Nabeel Khan Niazi; Behzad Murtaza (Environmental Monitoring and Assessment, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Effect of straw particle size in high grain complete pelleted diet on growth performance, rumen pH, feeding behavior, nutrient digestibility, blood and carcass indices of fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Bioactive compound identification and in vitro evaluation of antidiabetic and cytotoxic potential of Garcinia atroviridis fruit extract - Muhammad Shahid; Shazrul Fazry; Ahmad Azfaralariff; Ahmed Abdul Kareem Najm; Douglas Law; Mukram M. Mackeen (Food Bioscience, 2023)

Effects of age, body weight, semen collection frequency and holding duration on semen traits of broiler breeder reared under different housing systems - Muhammad Shabir Shaheen; Sadaf Aslam; Shahid Mehmood; Muhammad Tariq; Yassar Abbas; Hassan Ashfaq; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Spatial distribution, health risk assessment, and public perception of groundwater in Bahawalnagar, Punjab, Pakistan: a multivariate analysis - Zafar Iqbal; Muhammad Imran; Natasha; Ghani Rahman; Muhammad Miandad; Muhammad Shahid; Behzad Murtaza (Environmental Geochemistry and Health, 2023)

The role of various ameliorants on geochemical arsenic distribution and CO2-carbon efflux under paddy soil conditions - Muhammad Mahroz Hussain; Irshad Bibi; Fawad Ali; Zulfiqar Ahmad Saqib; Muhammad Shahid; Nabeel Khan Niazi; Khalid Hussain; Sabry M. Shaheen; Hailong Wang; Qamar Shakil; Jörg Rinklebe (Environmental Geochemistry and Health, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

CRISPR/Cas9-mediated genome editing in diploid and tetraploid potatoes - Aneela Yasmeen; Allah Bakhsh; Sara Ajmal; Momna Muhammad; Sahar Sadaqat; Muhammad Awais; Saira Azam; Ayesha Latif; Naila Shahid; Abdul Qayyum Rao (Acta Physiologiae Plantarum, 2023)

Correction to: Exploring the linkage between export diversification and ecological footprint: evidence from advanced time series estimation techniques - Shahid Ali; Muhlis Can; Muhammad Ibrahim Shah; Junfeng Jiang; Zahoor Ahmed; Muntasir Murshed (Environmental Science and Pollution Research, 2023)

Microwave-assisted sustainable exploration of cocklebur leaves (Xanthium strumarium L.) as a novel source of distinct yellow natural colorant for dyeing cotton fabric - Muhammad Hussaan; Ahmad Raza; Noman Habib; Shahid Adeel; Naeem Iqbal; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2023)

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Improving editing efficiency of prime editor in plants - Niaz Ahmad; Muhammad Jawad Akbar Awan; Shahid Mansoor (Trends in Plant Science, 2023)

The role of clean and unclean energy resources in inspecting N-shaped impact of industrial production on environmental quality: A case of high polluting economies - Jinchao Gao; Muhammad Shahid Hassan; Rukhsana Kalim; Arshian Sharif; Tarek Tawfik Yousef Alkhateeb; Haider Mahmood (Resources Policy, 2023)

One-pot solvothermal synthesis of highly catalytic Janus transition metal phosphides (TMPs) for high performance OER - Zeenat; Zahoor Ahmad; Adnan Maqbool; Muhammad Asif Hussain; Rami Adel Pashameah; Amber Shahzadi; Nosheen Nazar; Shahid Iqbal; Abdullah K. Alanazi; Muhammad Naeem Ashiq; Hala M. Abo-Dief (Fuel, 2023)

Analyzing the impact of drought on agriculture: evidence from Pakistan using standardized precipitation evapotranspiration index - Anwar Hussain; Khan Zaib Jadoon; Khalil Ur Rahman; Songhao Shang; Muhammad Shahid; Nuaman Ejaz; Himayatullah Khan (Natural Hazards, 2023)

Assessment of wild turmeric–based eco-friendly yellow natural bio-colorant for dyeing of wool fabric - Noman Habib; Aamir Ali; Shahid Adeel; Fazal-ur-Rehman; Muhammad Aftab; Asma Inayat (Environmental Science and Pollution Research, 2023)

Multiple begomoviruses infecting soybean; a case study in Faisalabad, Pakistan - Saleem U. Rahman; Ghulam Raza; Muhammad Zubair; Nasim Ahmed; Leslie L. Domier; Nousheen Jamil; Shahid Mansoor; Imran Amin (Biologia, 2022)

Molecular epidemiology and characterization of Babesia bovis in cattle of Khyber Pakhtunkhwa province, Pakistan - Muhammad Shoaib; Muhammad Imran Rashid; Haroon Akbar; Ali Ahmad Sheikh; Shahid Hussain Farooqi; Amel Ayari-Akkari; Habab M. Yassin; Rajwali Khan (Tropical Animal Health and Production, 2022)

“Cutting the Mustard” with Induced Pluripotent Stem Cells: An Overview and Applications in Healthcare Paradigm - Tapan Behl; Ishnoor Kaur; Aayush Sehgal; Sukhbir Singh; Neelam Sharma; Sridevi Chigurupati; Shatha Ghazi Felemban; Amal M. Alsubayiel; Muhammad Shahid Iqbal; Saurabh Bhatia; Ahmed Al-Harrasi; Simona Bungau; et al. (Stem Cell Reviews and Reports, 2022)

Recent trends in green synthesis of silver, gold, and zinc oxide nanoparticles and their application in nanosciences and toxicity: a review - Muhammad Musaddiq Shah; Khurshid Ahmad; Bashir Ahmad; Shahid Masood Shah; Hamid Masood; Muhammad Aamir Ramzan Siddique; Rasheed Ahmad (Nanotechnology for Environmental Engineering, 2022)

Exogenous Selenium as a Potent Modulator of Antioxidants, Osmo-protectants, Lipid Peroxidation, and Wheat Grain Yield Under Terminal Heat Stress - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Haroon Zaman Khan (Journal of Soil Science and Plant Nutrition, 2022)

Plant Growth-Promoting Rhizobacteria Significantly Improves Growth Attributes and Photosynthetic Machinery in Wheat - Tahir Naqqash; Mahreen Fatima; Saif-ur-Rehman; Sherien Bukhat; Muhammad Shahid; Ghulam Shabir; Muhammad Tahir; Muhammad Arshad; Muhammad Babar (Journal of Plant Growth Regulation, 2022)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Impact of Probiotic Geotrichum candidum QAUGC01 on Health, Productivity, and Gut Microbial Diversity of Dairy Cattle - Shahid Zaman; Madeeha Gohar; Hafsa Kanwal; Afia Chaudhary; Muhammad Imran (Current Microbiology, 2022)

Integration of RT-LAMP and Microfluidic Technology for Detection of SARS-CoV-2 in Wastewater as an Advanced Point-of-Care Platform - Ahmed Donia; Muhammad Furqan Shahid; Sammer-ul Hassan; Ramla Shahid; Aftab Ahmad; Aneela Javed; Muhammad Nawaz; Tahir Yaqub; Habib Bokhari (Food and Environmental Virology, 2022)

Modeling the economic viability and performance of solar home systems: a roadmap towards clean energy for environmental sustainability - Shahid Ali; Qingyou Yan; Azer Dilanchiev; Muhammad Irfan; Shah Fahad (Environmental Science and Pollution Research, 2022)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Acinetobacter schindleri SR-5–1 decipher morpho-physio-biochemical and nutritional improvements to Pisum sativum L. and Linum usitatissimum L. maintained under wastewater/cadmium stress - Sherjeel Hashmat; Kashif Tanwir; Saghir Abbas; Muhammad Shahid; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Sustainable eco-friendly extraction of yellow natural dye from haar singhar (Nyctanthes arbor-tritis) for bio coloration of cotton fabric - Muhammad Yameen; Shahid Adeel; Hunaira Nasreen; Fazal-ur-Rehman; Abdul Ghaffar; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Modeling the fecal contamination (fecal coliform bacteria) in transboundary waters using the scenario matrix approach: a case study of Sutlej River, Pakistan - Muhammad Shahid Iqbal; Majedul Islam; Mujtaba Hassan; Hazrat Bilal; Izaz Ali Shah; Tzoraki Ourania (Environmental Science and Pollution Research, 2022)

Asymptomatic populus alba: a tree serving as a reservoir of begomoviruses and associated satellites - Roma Mustafa; Muhammad Hamza; Atiq Ur Rehman; Hira Kamal; Muhammad Nouman Tahir; Shahid Mansoor; Brian E. Scheffler; Rob W. Briddon; Imran Amin (Australasian Plant Pathology, 2022)

Environmental friendly silk and cotton dyeing using natural colorant of Bougainvillea (Bougainvillea glabra) flowers: the sustainable approach towards textile industry - Warda Rasool; Shahid Adeel; Fatima Batool; Sheikh Asrar Ahmad; Sahar Mumtaz; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Flooding tolerance in plants: from physiological and molecular perspectives - Nasrullah; Shahid Ali; Muhammad Umar; Lifang Sun; Muhammad Naeem; Humaira Yasmin; Naeem Khan (Brazilian Journal of Botany, 2022)

Tournament incentives and environmental performance: the role of green innovation - Shahid Ali; Junfeng Jiang; Ramiz ur Rehman; Muhammad Kaleem Khan (Environmental Science and Pollution Research, 2022)

Projection of Hot and Cold Extremes in the Amu River Basin of Central Asia using GCMs CMIP6 - Obaidullah Salehie; Tarmizi bin Ismail; Mohammed Magdy Hamed; Shamsuddin Shahid; Mohd Khairul Idlan Muhammad (Stochastic Environmental Research and Risk Assessment, 2022)

Antimicrobial activity of the biologically synthesized zinc oxide nanoparticles against important rice pathogens - Ayesha Iftikhar Cheema; Temoor Ahmed; Ali Abbas; Muhammad Noman; Muhammad Zubair; Muhammad Shahid (Physiology and Molecular Biology of Plants, 2022)

Energy-growth hypothesis: testing non-linearity by considering production function approach for Spanish economy - Muhammad Shahid Hassan; Haider Mahmood; Saba Yousaf (Environmental Science and Pollution Research, 2022)

Deciphering distinct root exudation, ionomics, and physio-biochemical attributes of Serratia marcescens CP-13 inoculated differentially Cd tolerant Zea mays cultivars - Kashif Tanwir; Muhammad Shahid; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Hassan Javed Chaudhary; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

Response of sorghum and millet to poultry and farmyard manure–based biochar treatments - Muhammad Fraz Ali; Ummar Ali; Shahid Bilal; Usman Zulfiqar; Sidra Sohail; Tajamul Hussain (Arabian Journal of Geosciences, 2022)

Acceleration of flow modeling using a freeware 2D GPU-shallow water equations code - Prince Mahmood; Sajjad Haider; Hamza Farooq Gabriel; Muhammad Shahid; Zain Syed (Arabian Journal of Geosciences, 2022)

Environmental friendly pollution free bio-dyeing of wool with haar singhar (Coral Jasmine) flower extract - Shahid Adeel; Sehrish Ahmad; Noman Habib; Muhammad Jawwad Saif; Fatima Batool; Muhammad Aftab (Environmental Science and Pollution Research, 2022)

Modeling factors of biogas technology adoption: a roadmap towards environmental sustainability and green revolution - Shahid Ali; Qingyou Yan; Asif Razzaq; Irfan Khan; Muhammad Irfan (Environmental Science and Pollution Research, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

Investigating feasible sites for multi-purpose small dams in Swat District of Khyber Pakhtunkhwa Province, Pakistan: socioeconomic and environmental considerations - Anwar Hussain; Khalil Ur Rahman; Muhammad Shahid; Sajjad Haider; Quoc Bao Pham; Nguyen Thi Thuy Linh; Saad Shauket Sammen (Environment, Development and Sustainability, 2022)

Expression and characterization of heparinase II with MBP tag from a novel strain, Raoultella NX-TZ-3-15 - Yinyin Li; Yue Lin; Yingzi Jiang; Hafiza Mahreen Mehwish; Muhammad Shahid Riaz Rajoka; Liqing Zhao (Archives of Microbiology, 2022)

Spatial evaluation of precipitation patterns in the catchment area of Malir River during monsoon spells of 2019 through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Muhammad Arsalan; Shahid Naseem; Humaira Kanwal (Arabian Journal of Geosciences, 2022)

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Influence of biochar on trace element uptake, toxicity and detoxification in plants and associated health risks: A critical review - Natasha Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Muhammad Asif Naeem; Nabeel Khan Niazi; Filip M. G. Tack; James Anthony Ippolito; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Situational assessment for fecal sludge management in major cities of Pakistan - Nida Maqbool; Muhammad Arslan Shahid; Sher Jamal Khan (Environmental Science and Pollution Research, 2022)

Protection against reinforcement corrosion using various hydroxy acid-based rust converters: tests in mortar medium - Muhammad Salman; Muhammad Ali Sikandar; Hassan Nasir; Muhammad Waseem; Shahid Iqbal (European Journal of Environmental and Civil Engineering, 2022)

Effect of slow release nitrogenous fertilizers and biochar on growth, physiology, yield, and nitrogen use efficiency of sunflower under arid climate - Muhammad Waqar; Muhammad Habib-ur-Rahman; Muhammad Usama Hasnain; Shahid Iqbal; Abdul Ghaffar; Rashid Iqbal; Muhammad Iftikhar Hussain; Ayman EL Sabagh (Environmental Science and Pollution Research, 2022)
Sunflower plants need nitrogen consistently and in higher amount for optimum growth and development. However, nitrogen use efficiency (NUE) of sunflower crop is low due to various nitrogen (N) losses. Therefore, it is necessary to evaluate the advanced strategies to minimize N losses and also improve sunflower productivity under arid climatic conditions. A field trial was conducted with four slow release nitrogenous fertilizers [SRNF (bacterial, neem, and sulfur-coated urea and N loaded biochar)] and three N levels (100% = 148 kg N ha −1 , 80% = 118 kg N ha −1 , and 60% = 89 kg N ha −1 ) of recommended application (100%) for sunflower crop under arid climatic conditions. Results showed that neem-coated urea at 148 kg N ha −1 significantly enhanced crop growth rate (CGR) (19.16 g m −2 d −1 ) at 60–75 days after sowing (DAS); leaf area index (2.12, 3.62, 5.97, and 3.00) at 45, 60, 75, and 90 DAS; and total dry matter (14.27, 26.29, 122.67, 410, and 604.33 g m −2 ) at 30, 45, 60, 75, and 90 DAS. Furthermore, higher values of net leaf photosynthetic rate (25.2 µmol m −2 s −1 ), transpiration rate (3.66 mmol s −1 ), and leaf stomatal conductance (0.39 mol m −2 s −1 ) were recorded for the same treatment. Similarly, neem-coated urea produced maximum achene yield (2322 kg ha −1 ), biological yield (9000 kg ha −1 ), and harvest index (25.8%) of the sunflower crop. Among various N fertilizers, neem-coated urea showed maximum NUE (20.20 kg achene yield kg −1 N applied) in comparison to other slow release N fertilizers. Similarly, nitrogen increment N 60 showed maximum NUE (22.40 kg grain yield kg −1 N applied) in comparison to N 80 and N 100 . In conclusion, neem-coated urea with 100% and 80% of recommended N would be recommended for farmers to get better sunflower productivity with sustainable production and to reduce the environmental nitrogen losses.

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Carbon and nitrogen metabolism in peach trees on different Prunus rootstocks in response to flooding - Trequan McGee; Bruce Schaffer; Muhammad Adnan Shahid; Jose X. Chaparro; Ali Sarkhosh (Plant and Soil, 2022)

Application of zinc oxide nanoparticles immobilizes the chromium uptake in rice plants by regulating the physiological, biochemical and cellular attributes - Farwa Basit; Muhammad Mudassir Nazir; Muhammad Shahid; Saghir Abbas; Muhammad Tariq Javed; Tahir Naqqash; Yihan Liu; Guan Yajing (Physiology and Molecular Biology of Plants, 2022)

An overview of sucrose transporter (SUT) genes family in rice - Lixia Sun; Ruilian Deng; Jingwen Liu; Mingyu Lai; Jinwen Wu; Xiangdong Liu; Muhammad Qasim Shahid (Molecular Biology Reports, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Biocidal activity of green synthesized silver nanoformulation by Azadirachta indica extract a biorational approach against notorious cotton pest whitefly, Bemisia tabaci (Homoptera; Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2022)

The impact of electric power consumption on economic growth: a case study of Portugal, France, and Finland - Muhammad Shahid Hassan; Haider Mahmood; Anam Javaid (Environmental Science and Pollution Research, 2022)

Arsenic-induced oxidative stress in Brassica oleracea: Multivariate and literature data analyses of physiological parameters, applied levels and plant organ type - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Samina Khalid; Nasir Masood; Saeed Ahmad Qaisrani; Nabeel Khan Niazi; Camille Dumat (Environmental Geochemistry and Health, 2022)

Collaborative-trust approach toward malicious node detection in vehicular ad hoc networks - Shahid Sultan; Qaisar Javaid; Arif Jamal Malik; Fadi Al-Turjman; Muhammad Attique (Environment, Development and Sustainability, 2022)

Prospects of Multiproduct Algal Biorefineries Involving Cascading Processing of the Biomass Employing a Zero-Waste Approach - Sana Malik; Ayesha Shahid; Muhammad Nabeel Haider; Mahwish Amin; Michael J. Betenbaugh; Muhammad Aamer Mehmood; Muhammad Adnan Ul Haq; Achmad Syafiuddin; Raj Boopathy (Current Pollution Reports, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

Exploring the linkage between export diversification and ecological footprint: evidence from advanced time series estimation techniques - Shahid Ali; Muhlis Can; Muhammad Ibrahim Shah; Junfeng Jiang; Zahoor Ahmed; Muntasir Murshed (Environmental Science and Pollution Research, 2022)

Sustainable natural coloring potential of bitter gourd (Momordica charantia L.) residues for cotton dyeing: innovative approach towards textile industry - Fatima Batool; Shahid Adeel; Naeem Iqbal; Muhammad Azeem; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Sustainable isolation of licorice (Glycyrrhiza glabra L.)-based yellow natural colorant for dyeing of bio-mordanted cotton - Shahid Adeel; Shumaila Kiran; Mazhar Abbas; Fatima Batool; Muhammad Hussaan; Nimra Amin (Environmental Science and Pollution Research, 2022)

Evaluating the impact of the environment on depleting groundwater resources: a case study from a semi-arid and arid climatic region - Khalil Ur Rahman; Anwar Hussain; Nuaman Ejaz; Muhammad Shahid; Zheng Duan; Babak Mohammadi; Pham Ngoc Hoai; Quoc Bao Pham; Khaled Mohamed Khedher; Duong Tran Anh (Hydrological Sciences Journal, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Effects of replacement of wheat straw with corn stover-based TMR on growth performance, behavioral characteristics, selected blood metabolites, and nutrient digestibility in Beetal bucks - Faisal Majeed; Saeed Ahmed; Muhammad Afzal Rashid; Muhammad Qamar Shahid; Imran Mohsin (Tropical Animal Health and Production, 2022)

Development of new machine learning model for streamflow prediction: case studies in Pakistan - Rana Muhammad Adnan; Reham R. Mostafa; Ahmed Elbeltagi; Zaher Mundher Yaseen; Shamsuddin Shahid; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2022)

Evaluation of Sarcopenia Using Biomarkers of the Neuromuscular Junction in Parkinson’s Disease - Asima Karim; M. Shahid Iqbal; Tahir Muhammad; Rizwan Qaisar (Journal of Molecular Neuroscience, 2022)

Melatonin Mitigates Cadmium Toxicity by Promoting Root Architecture and Mineral Homeostasis of Tomato Genotypes - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Safina Naz; Muhammad Mohsin Altaf; Latif Ullah Khan; Milan Kumar Lal; Rahul Kumar Tiwari; Awais Shakoor (Journal of Soil Science and Plant Nutrition, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

Nanocrystals: Characterization Overview, Applications in Drug Delivery, and Their Toxicity Concerns - Mohammed Asadullah Jahangir; Syed Sarim Imam; Abdul Muheem; Ananda Chettupalli; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Imran Kazmi; Muhammad Afzal; Sultan Alshehri (Journal of Pharmaceutical Innovation, 2022)

Sequence stratigraphy, depositional and diagenetic environments of the late Cambrian glauconite bearing oolitic limestones in the Kelan Section, Shanxi, China - Muhammad Riaz; G M Bhat; Khalid Latif; Tehseen Zafar; Shahid Ghazi (Journal of Earth System Science, 2022)

Morphology and genesis of the Cambrian oncoids in Wuhai Section, Inner Mongolia, China - Muhammad Riaz; Khalid Latif; Tehseen Zafar; Enzhao Xiao; Shahid Ghazi (Carbonates and Evaporites, 2022)

Muricazine, a new hydrazine derivative from Ranunculus muricatus L. with antioxidant, lipoxygenase and urease inhibitory activities - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Muhammad Shahid; Mehreen Lateef; Salman Zafar (Natural Product Research, 2022)

Isolation and identification of two new compounds from the seeds of Moringa oleifera and their antiviral and anti-inflammatory activities - Yongai Xiong; Muhammad Shahid Riaz Rajoka; MengXun Zhang; Zhendan He (Natural Product Research, 2022)

Performance and welfare of dairy buffaloes subjected to different cooling strategies during subtropical summer - Musa Bah; Muhammad Qamer Shahid; Talat Naseer Pasha; Khalid Javed (Tropical Animal Health and Production, 2022)

Sugarcane Breeding in Pakistan - Shahid Afghan; Waqas Raza Arshad; Muhammad Ehsan Khan; Karim Baksh Malik (Sugar Tech, 2022)

Anti-Huntington’s Effect of Butin in 3-Nitropropionic Acid-Treated Rats: Possible Mechanism of Action - Sultan Alshehri; Fahad A. Al-Abbasi; Mohammed M. Ghoneim; Syed Sarim Imam; Muhammad Afzal; Khalid Saad Alharbi; Muhammad Shahid Nadeem; Nadeem Sayyed; Imran Kazmi (Neurotoxicity Research, 2022)

Characterization of new COBRA like (COBL) genes in wheat (Triticum aestivum) and their expression analysis under drought stress - Muhammad Zaheer; Shoaib Ur Rehman; Sultan Habibullah Khan; Shahmeer Shahid; Awais Rasheed; Rabia Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Characterization and thermal behavior of marble from northwestern Pakistan - Atta Ur Rehman; Waqas Ahmed; Shahid Azam; Muhammad Sajid (Innovative Infrastructure Solutions, 2022)

Photocatalytic degradation of methylene blue using polyaniline-based silver-doped zinc sulfide (PANI-Ag/ZnS) composites - Sidra Mazhar; Umair Yaqub Qazi; Nimra Nadeem; Muhammad Zahid; Abdul Jalil; Fareeda Khan; Iftikhar Ul-Hasan; Imran Shahid (Environmental Science and Pollution Research, 2022)

Multivariate analysis of accumulation and critical risk analysis of potentially hazardous elements in forage crops - Muhammad Usman; Behzad Murtaza; Natasha Natasha; Muhammad Imran; Ghulam Abbas; Muhammad Amjad; Muhammad Shahid; Sobhy M. Ibrahim; Gary Owens; Ghulam Murtaza (Environmental Monitoring and Assessment, 2022)

Understanding the role of atmospheric circulations and dispersion of air pollution associated with extreme smog events over South Asian megacity - Muhammad Bilal; Mujtaba Hassan; Danyal Bin Taufiq Tahir; Muhammad Shahid Iqbal; Imran Shahid (Environmental Monitoring and Assessment, 2022)

Unrevealing arsenic and lead toxicity and antioxidant response in spinach: a human health perspective - Natasha; Muhammad Shahid; Sana Khalid; Mazhar Saleem (Environmental Geochemistry and Health, 2022)

Effects of convective available potential energy, temperature and humidity on the variability of thunderstorm frequency over Bangladesh - Md Wahiduzzaman; Md. Arfan Ali; Jing-Jia Luo; Yu Wang; Md. Jalal Uddin; Shamsuddin Shahid; A. R. M. Towfiqul Islam; Sanjit Kumar Mondal; Ubaydur Rahaman Siddiki; Muhammad Bilal; Zhongfeng Qiu; Ramzah Dambul; et al. (Theoretical and Applied Climatology, 2022)

Designing Fusion Molecules from Antigens of Mycobacterium tuberculosis to Enhance Serodiagnostic Sensitivity in Latent TB Infection and Active TB State - Chandni Yaqoob; Saher Shahid; Aasia Khaliq; Zaib un Nisa; Imran H. Khan; Muhammad Waheed Akhtar (International Journal of Peptide Research and Therapeutics, 2022)

Metal-tolerant Pantoea sp. WP-5 and organic manures enhanced root exudation and phytostabilization of cadmium in the rhizosphere of maize - Muhammad Tahir; Muhammad Bismillah Khan; Muhammad Shahid; Iftikhar Ahmad; Umaira Khalid; Muhammad Akram; Ahmad Dawood; Muhammad Kamran (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Assessment of sustainability and uncertainties of oil markets: mediating determinants of energy use and CO2 emissions - Muhammad Mohsin; Shahid Bashir; Zulfiqar Ali Baloch; Mohammad Hafeez (Environmental Science and Pollution Research, 2022)

Ecofriendly application of coconut coir (Cocos nucifera) extract for silk dyeing - Shahid Adeel; Shumaila Kiran; Muhammad Shahid; Sajid Raza Habib; Noman Habib; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Muriolide, a novel antioxidant lactone from Ranunculus muricatus - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Mehreen Lateef; Muhammad Shahid; Shehla Akbar; Salman Zafar (Natural Product Research, 2021)

Implementation of Vaccinomics and In-Silico Approaches to Construct Multimeric Based Vaccine Against Ovarian Cancer - Muhammad Sufyan; Farah Shahid; Faiza Irshad; Anam Javaid; Muhammad Qasim; Usman Ali Ashfaq (International Journal of Peptide Research and Therapeutics, 2021)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

Functional identification of G. hirsutum genes for their role in normal plant development and resistance against Verticillium dahliae using virus-induced gene silencing - Roma Mustafa; Muhammad Javed Iqbal; Muhammad Hamza; Atiq Ur Rehman; Ismail Buzdar; Hira Kamal; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2021)

Hydrogeochemical and health risk investigation of potentially toxic elements in groundwater along River Sutlej floodplain in Punjab, Pakistan - Sajjad Ahmad; Muhammad Imran; Behzad Murtaza; Natasha; Muhammad Arshad; Rab Nawaz; Abdul Waheed; Hafiz Mohkum Hammad; Muhammad Asif Naeem; Muhammad Shahid; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2021)

Arsenic exposure through drinking groundwater and consuming wastewater-irrigated vegetables in Multan, Pakistan - Mamoona Amir; Salman Asghar; Muhammad Ahsin; Shahid Hussain; Amir Ismail; Muhammad Riaz; Safina Naz (Environmental Geochemistry and Health, 2021)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

First report of Cotton leaf curl Kokhran virus associated with Cotton leaf curl Multan betasatellite infecting soybean in Pakistan - Maddiha Riaz; Muhammad Zubair; Saleem Ur Rahman; Shahid Mansoor (Journal of Plant Pathology, 2021)

RETRACTED ARTICLE: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

Potential of organic and inorganic amendments for stabilizing nickel in acidic soil, and improving the nutritional quality of spinach - Umeed Ali; Muhammad Shaaban; Saqib Bashir; Muhammad Afzal Chhajro; Li Qian; Muhammad Shahid Rizwan; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Science and Pollution Research, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Historical trends in crop water demand over semiarid region of Syria - Rajab Homsi; Shamsuddin Shahid; Zafar Iqbal; Atif Muhammad Ali; Ghaith Falah Ziarh (Theoretical and Applied Climatology, 2021)

Pharmacological evaluation of the gabapentin salicylaldehyde derivative, gabapentsal, against tonic and phasic pain models, inflammation, and pyrexia - Nisar Ahmad; Fazal Subhan; Nazar Ul Islam; Muhammad Shahid; Naseem Ullah; Rahim Ullah; Muhammad Khurram; Muhammad Usman Amin; Shehla Akbar; Ihsan Ullah; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

How energy insecurity leads to energy poverty? Do environmental consideration and climate change concerns matters - Syed Ehsanullah; Quyen Ha Tran; Muhammad Sadiq; Shahid Bashir; Muhammad Mohsin; Robina Iram (Environmental Science and Pollution Research, 2021)

Do economic openness and electricity consumption matter for environmental deterioration: silver bullet or a stake? - Ali Jan; Zhao Xin-gang; Munir Ahmad; Muhammad Irfan; Shahid Ali (Environmental Science and Pollution Research, 2021)

Exploring natural colorant behavior of husk of durum (Triticum durum Desf.) and bread (Triticum aestivum L.) wheat species for sustainable cotton fabric dyeing - Ali Ahmad Khan; Shahid Adeel; Muhammad Azeem; Naeem Iqbal (Environmental Science and Pollution Research, 2021)

Advances in Green Technologies for the Removal of Effluent Organic Matter from the Urban Wastewater - Ayesha Shahid; Aqib Zafar Khan; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Achmad Syafiuddin; Ning Wang; Hui Zhu; Raj Boopathy (Current Pollution Reports, 2021)

Weed flora composition of different barley‐based cropping systems under conventional and conservation tillage practices - Muhammad Naeem; Mubshar Hussain; Muhammad Farooq; Shahid Farooq (Phytoparasitica, 2021)

Melatonin Mitigates Nickel Toxicity by Improving Nutrient Uptake Fluxes, Root Architecture System, Photosynthesis, and Antioxidant Potential in Tomato Seedling - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2021)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Environmental friendly extraction of walnut bark-based juglone natural colorant for dyeing studies of wool fabric - Waseem-ul- Arifeen; Fazal-Ur- Rehman; Shahid Adeel; Muhammad Zuber; Mirza Nadeem Ahmad; Tanvir Ahmad (Environmental Science and Pollution Research, 2021)

Assessing the potential and hydrological usefulness of the CHIRPS precipitation dataset over a complex topography in Pakistan - Muhammad Shahid; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel; Abdul Jabbar Khan; Quoc Bao Pham; Babak Mohammadi; Nguyen Thi Thuy Linh; Duong Tran Anh (Hydrological Sciences Journal, 2021)

Antiparkinsonian activity of Cucurbita pepo seeds along with possible underlying mechanism - Uzma Saleem; Aisha Shehzad; Shahid Shah; Zohaib Raza; Muhammad Ajmal Shah; Shabana Bibi; Zunera Chauhdary; Bashir Ahmad (Metabolic Brain Disease, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

Assessment of rice and wheat production efficiency based on data envelopment analysis - Muhammad Shoaib Aslam; Pan Huan Xue; Shahid Bashir; Yazeed Alfakhri; Mohammad Nurunnabi; Van Chien Nguyen (Environmental Science and Pollution Research, 2021)

Optimizing different adaptive strategies by using crop growth modeling under IPCC climate change scenarios for sustainable wheat production - Muhammad Rizwan Shahid; Abdul Wakeel; Wajid Ishaque; Samia Ali; Kamran Baksh Soomro; Muhammad Awais (Environment, Development and Sustainability, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Deteriorating Habitats and Conservation Strategies to Repopulate the Endangered Indus River Dolphin (Platanista gangetica minor); a Lesson Learned From the Conservation Practices of the Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Ghulam Nabi; Shahid Ahmad; Richard William McLaughlin; Yujiang Hao; Suliman Khan; Naveed Ahmad; Saeed Ahmad; Muhammad Shoaib Kiani; Yuefeng Wu; Dongming Li (Frontiers in Marine Science, 2021)
The Indus River dolphin (IRD; Platanista gangetica minor ) is an endangered and blind freshwater cetacean, endemic to the Indus River system of Pakistan and India. This review article provides detailed information about the major challenges IRDs are facing, and their possible consequences on the population dynamics of the IRD. Furthermore, we have suggested future conservation strategies for the IRD based on the lesson learned from the conservation of the Yangtze finless porpoise (YFP; Neophocaena asiaeorientalis ), a Critically Endangered freshwater cetacean. The major challenges for IRDs are habitat degradation, habitat fragmentation, and several types of industrial and agricultural pollutants. Worsening climatic changes, illegal fishing, and overfishing are additional threats. The construction of several barrages has fragmented the population into several short segments, some of which are too small for the IRDs to survive. In some segments, the population status of the IRD is unknown. In the remaining populations, genetic inbreeding, water shortage, canal entrapment, and altered ecological environment are potent negative factors for the survival of the IRD. Conservation strategies including fishing bans, translocation, and future research (tagging, periodic health assessments, necropsy and virtopsy, understanding the reproductive biology, and genomics) are possible recommendations. Very serious conservation efforts are needed to save the IRD from decline keeping in view the water shortage, pollution, lack of health assessment studies, and habitat degradation and fragmentation.

Studying the foliar selenium-modulated dynamics in phenology and quality of terminal heat-stressed cotton ( Gossypium hirsutum L.) in association with yield - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Muhammad Awais; Amna Saleem; Muhammad Aown Sammar Raza; Bao-Luo Ma (Plant Biosystems, 2021)

Use of multivariate adaptive regression splines for prediction of body weight from body measurements in Marecha (Camelus dromedaries) camels in Pakistan - Cem Tırınk; Ecevit Eyduran; Asim Faraz; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq; Irfan Shahzad Sheikh (Tropical Animal Health and Production, 2021)

Complete nucleotide sequence of a begomovirus associated with an alphasatellite and a betasatellite naturally infecting okra in Jordan - Nida’ M. Salem; Muhammad Shafiq Shahid; Ali Idris; Dina Hattab; Amany Abdeen (Archives of Virology, 2021)

Expression profiling of miRNA-196a biomarker in naïve hepatitis C virus-infected and Sofosbuvir plus Daclatasvir-treated patients - Nazim Hussain; Nimrah Farooq; Muhammad Maqsood; Muhammad Shahid Riaz Rajoka; Muhammad Bilal (Archives of Microbiology, 2021)

Spatio‐temporal evaluation of gridded precipitation products for the high‐altitude Indus basin - Zakir Hussain Dahri; Fulco Ludwig; Eddy Moors; Shakil Ahmad; Bashir Ahmad; Muhammad Shoaib; Irfan Ali; Muhammad Shahid Iqbal; Muhammad Saleem Pomee; Abdul Ghafoor Mangrio; Muhammad Munir Ahmad; Pavel Kabat (International Journal of Climatology, 2021)
The high‐altitude Indus basin is one of the most complex and inadequately explored mountain terrains in the World, where reliable observations of precipitation are highly lacking. Therefore, spatially distributed precipitation products developed at global/regional scale are often used in several scientific disciplines. However, large uncertainties in precipitation estimates of such precipitation data sets often lead to suboptimal outcomes. In this study, performance of 27 widely used gridded precipitation products belonging to three different categories of gauge‐based, reanalysis and merged products is evaluated with respect to high‐quality reference climatologies of mean monthly precipitation. Widely used statistical measures and quantitative analysis techniques are used to analyse the spatial patterns and quantitative distribution of mean monthly, seasonal and annual precipitation at sub‐regional scale. Mean annual precipitation estimates of the gridded data sets are cross validated with the corresponding adjusted streamflows using Turc‐Budyko non‐dimensional analysis. Results reveal poor to moderately good performance of the gridded data sets. Marked differences in spatiotemporal and quantitative distribution of precipitation are found among the data sets. All data sets are consistent in their patterns showing negative or dry bias in wet areas and positive or wet bias in dry areas, although considerable differences in the magnitudes of the biases are noticed at sub‐regional scale. None of the data sets is equally good for all sub‐regions due to very high spatiotemporal variability in their performance at sub‐regional scale. Gauge‐based and merged products performed better in dry regions and during monsoon season, while reanalysis products provided better estimates in wet areas and during winter months. GPCC V8, ERA5 and MSWEP2.2 are found better than their counter‐grouped data sets. Overall, ERA5 is found most acceptable for all sub‐regions, particularly at higher‐altitudes, in wet areas and during winter months.

Genetic and expression deregulation of immunoregulatory genes in rheumatoid arthritis - Muhammad Zhaid Hussain; Ishrat Mahjabeen; Muhammad Shahid Khan; Naila Mumtaz; Syed Uzair Maqsood; Farooq Ikram; Syed Nazir Ahmed; Qurrat-ul-Ain Kalim; Rabia Abbas; Ahmed Ammar Cheema (Molecular Biology Reports, 2021)

A technological innovation and economic progress enhancement: an assessment of sustainable economic and environmental management - Wu Hao; Farhat Rasul; Zobia Bhatti; Muhammad Shahid Hassan; Ishtiaq Ahmed; Nabila Asghar (Environmental Science and Pollution Research, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

Distribution-based effects of disaggregated GDP and environmental quality—a case of quantile on quantile estimates - Muhammad Shahid Hassan; Mubasher Iqbal; Noman Arshed (Environmental Science and Pollution Research, 2021)

Effect of co-application of wastewater and freshwater on the physiological properties and trace element content in Raphanus sativus: soil contamination and human health - Natasha; Muhammad Shahid; Aneeza Sardar; Hasnain Anwar; Sana Khalid; Sajid Hussain Shah; Ali Haidar Shah; Muhammad Bilal (Environmental Geochemistry and Health, 2021)

Prediction of live body weight based on body measurements in Thalli sheep under tropical conditions of Pakistan using CART and MARS - Asim Faraz; Cem Tirink; Ecevit Eyduran; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq (Tropical Animal Health and Production, 2021)

Effect of feeding calcium propionate supplemented cotton seed cake on milk yield, milk composition and aflatoxin concentration in lactating buffaloes - Murtaza Ali Tipu; Anjum Khalique; Muhammad Naveed-ul-Haque; Muhammad Qamer Shahid; Maqsood Akhtar; Mubashir Ilyas (Tropical Animal Health and Production, 2021)

The development of evolutionary computing model for simulating reference evapotranspiration over Peninsular Malaysia - Mohd Khairul Idlan Muhammad; Shamsuddin Shahid; Tarmizi Ismail; Sobri Harun; Ozgur Kisi; Zaher Mundher Yaseen (Theoretical and Applied Climatology, 2021)

Evidence that leaf curl disease of Malva sylvestris in Iran is associated with cotton leaf curl Gezira virus and associated betasatellite - Kaveh Bananej; Muhammad Shafiq Shahid; Muhammad Shafiq (Journal of Plant Pathology, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

Identifying the Annual and Seasonal Trends of Hydrological and Climatic Variables in the Indus Basin Pakistan - Muhammad Shahid; Khalil Ur Rahman (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

RETRACTED ARTICLE: Closed-loop supply chain network design with sustainability and resiliency criteria - Muhammad Salman Shabbir; Arshad Mahmood; Roy Setiawan; Chairun Nasirin; Rusdiyanto Rusdiyanto; Gazali Gazali; Mohd Anuar Arshad; Shahid Khan; Fatima Batool (Environmental Science and Pollution Research, 2021)

Impact of light stimulation during incubation on hatching traits and post-hatch performance of commercial broilers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Abd ur Rehman; Muhammad Usman; Shahid Mehmood; Sohail Ahmad (Tropical Animal Health and Production, 2021)

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Demographic and morphometric features of pink bollworm, Pectinophora gossypiella (Saunder) (Lepidoptera: Gelechiidae) on four host plants - Muhammad Naeem Mushtaq; Muhammad Arshad; Shahid Majeed; Sajid Aleem Khan (International Journal of Tropical Insect Science, 2021)

Spatiotemporal analysis of crop water requirements in Lower Chenab Canal (LCC) Irrigation System for the better management of water resources - Muhammad Usman; Ejaz Hussain; Umair Rabbani; Shahid Ghazi; Syed M. Irteza; Shamaila Gull (Arabian Journal of Geosciences, 2021)

Application of precipitation products for flood modeling of transboundary river basin: a case study of Jhelum Basin - Muhammad Umer; Hamza Farooq Gabriel; Sajjad Haider; Ammara Nusrat; Muhammad Shahid; Muhammad Umer (Theoretical and Applied Climatology, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Microarray analysis of Arabidopsis thaliana exposed to single and mixed infections with Cucumber mosaic virus and turnip viruses - Aminallah Tahmasebi; Bahman Khahani; Elahe Tavakol; Alireza Afsharifar; Muhammad Shafiq Shahid (Physiology and Molecular Biology of Plants, 2021)

Foliar uptake, biotransformation, and impact of CuO nanoparticles in Lactuca sativa L. var. ramosa Hort. - Tiantian Xiong; Ting Zhang; Yuanhong Xian; Zhuangzhuang Kang; Shasha Zhang; Camille Dumat; Muhammad Shahid; Shaoshan Li (Environmental Geochemistry and Health, 2021)

Diversity and recombination analysis of Cotton leaf curl Multan betasatellite associated with cotton leaf curl begomovirus disease complex - Muhammad Zubair; Saleem Ur Rahman; Ishtiaq Hassan; Azhar Hussain Shah; Imran Amin; Shahid Mansoor (Australasian Plant Pathology, 2021)

Interaction of watermelon chlorotic stunt virus with satellites - Muhammad Shafiq; Muhammad Naeem Sattar; Muhammad Shafiq Shahid; Abdullah M. Al-Sadi; Rob W. Briddon (Australasian Plant Pathology, 2021)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Interactive Effect of Biochar and Silicon on Improving Morpho-Physiological and Biochemical Attributes of Maize by Reducing Drought Hazards - Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Madiha Butt; Muhammad Irfan; Muhammad Shahid Rizwan; Hakoomat Ali; Mumtaz A. Cheema (Journal of Soil Science and Plant Nutrition, 2020)

Foliar Potassium-Induced Regulations in Glycine Betaine and Malondialdehyde Were Associated with Grain Yield of Heat-Stressed Bread Wheat (Triticum aestivum L.) - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Haroon Zaman Khan; Abdul Shakoor (Journal of Soil Science and Plant Nutrition, 2020)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

Quantification and risk assessment of heavy metal build-up in soil–plant system after irrigation with untreated city wastewater in Vehari, Pakistan - Tania Sarwar; Muhammad Shahid; Natasha; Sana Khalid; Ali Haidar Shah; Naveed Ahmad; Muhammad Asif Naeem; Zia ul Haq; Behzad Murtaza; Hafiz Faiq Bakhat (Environmental Geochemistry and Health, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Oral supplementation of Ficus religiosa leaf extract adversely affects the selected behavioral aspects of male albino mice - Naheed Akhtar; Shahid Iqbal; Muhammad Faisal Shahzad; Muhammad Latif; Furhan Iqbal (Biologia, 2020)

De Novo Assembly and Annotation of the Juvenile Tuber Transcriptome of a Gastrodia elata Hybrid by RNA Sequencing: Detection of SSR Markers - Yunsheng Wang; Muhammad Qasim Shahid; Fozia Ghouri; Faheem Shehzad Baloch (Biochemical Genetics, 2020)

Pregnancy status and thyroid function in semi-intensive-kept Marecha she-camels (Camelus dromedarius): managerial implications - Asim Faraz; Carlos Iglesias Pastrana; Annamaria Passantino; Ayman Balla Mustafa; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2020)

Identification of significant risks in pediatric acute lymphoblastic leukemia (ALL) through machine learning (ML) approach - Nasir Mahmood; Saman Shahid; Taimur Bakhshi; Sehar Riaz; Hafiz Ghufran; Muhammad Yaqoob (Medical & Biological Engineering & Computing, 2020)

First report of root rot caused by Ceratobasidium sp. AG-Fa on Capsicum annuum in Pakistan - Aliya Tariq; Farah Naz; Muhammad Shahid; Amjad Shahzad Gondle; Abdul Sattar; Muhammad Nabeel; Zobia Jabeen; Imran Hassan (Journal of Plant Pathology, 2020)

Environmental toxicology and associated human health risks - Muhammad Shahid; Muhammad Nadeem; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2020)

Heavy metal contamination and exposure risk assessment via drinking groundwater in Vehari, Pakistan - Sana Khalid; Muhammad Shahid; Natasha; Ali Haidar Shah; Farhan Saeed; Mazhar Ali; Saeed Ahmad Qaisrani; Camille Dumat (Environmental Science and Pollution Research, 2020)

Risk assessment of heavy metal(loid)s via Spinacia oleracea ingestion after sewage water irrigation practices in Vehari District - Aneeza Sardar; Muhammad Shahid; Natasha; Sana Khalid; Hasnain Anwar; Muhammad Tahir; Ghulam Mustafa Shah; Muhammad Mubeen (Environmental Science and Pollution Research, 2020)

Foliar application of lead and arsenic solutions to Spinacia oleracea: biophysiochemical analysis and risk assessment - Natasha; Muhammad Shahid; Sana Khalid (Environmental Science and Pollution Research, 2020)

Fabrication, Physical Characterizations, and In Vitro, In Vivo Evaluation of Ginger Extract-Loaded Gelatin/Poly(Vinyl Alcohol) Hydrogel Films Against Burn Wound Healing in Animal Model - Barkat Ali Khan; Shahid Ullah; Muhammad Khalid Khan; Bushra Uzair; Farid Menaa; Valdir A. Braga (AAPS PharmSciTech, 2020)

Trace elements-induced phytohormesis: A critical review and mechanistic interpretation - Muhammad Shahid; Nabeel Khan Niazi; Jörg Rinklebe; Jochen Bundschuh; Camille Dumat; Eric Pinelli (Critical Reviews in Environmental Science and Technology, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Sodium Exclusion Affects Seed Yield and Physiological Traits of Wheat Genotypes Grown Under Salt Stress - Muhammad Sohail Saddiq; Irfan Afzal; Shahzad M.A. Basra; Shahid Iqbal; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Spatial variation and health risk assessment of fluoride in drinking water in the Chongqing urban areas, China - Dongsheng Zheng; Yonglin Liu; Lili Luo; Muhammad Zeeshaan Shahid; Dongming Hou (Environmental Geochemistry and Health, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Petrographic and rare earth elemental characteristics of Cambrian Girvanella oncoids exposed in the North China Platform: Constraints on forming mechanism, REE sources, and paleoenvironments - Muhammad Riaz; Tehseen Zafar; Khalid Latif; Shahid Ghazi; Enzhao Xiao (Arabian Journal of Geosciences, 2020)

Application of a Dye-Decolorizing Pseudomonas aeruginosa Strain ZM130 for Remediation of Textile Wastewaters in Aerobic/Anaerobic Sequential Batch Bioreactor and Soil Columns - Zahid Maqbool; Muhammad Shahid; Farrukh Azeem; Tanvir Shahzad; Faisal Mahmood; Muzammal Rehman; Tanvir Ahmed; Muhammad Imran; Sabir Hussain (Water, Air, & Soil Pollution, 2020)

Hydrological drought indexing approach in response to climate and anthropogenic activities - Waseem Muhammad; Shahid Muhammad; Noor Muhammad Khan; Chen Si (Theoretical and Applied Climatology, 2020)

Detection and molecular characterization of Clerodendron yellow mosaic virus infecting Volkameria inermis in Pakistan - Afzal Akram; Aqsa Hafeez Khan; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Journal of Plant Pathology, 2020)

First report of pepper leaf curl Bangladesh virus (PepLCBV) associated with cotton leaf curl Multan betasatellite on kidney bean (Phaseolus vulgaris) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Muhammad Zuhaib Khan; Ghulam Raza; Imran Amin; Shahid Mansoor (Journal of Plant Pathology, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Effect of fans and showers on the physiological measures and reproductive performance of Holstein Friesian bulls during subtropical summer - Mahboob Ahmed Butt; Jalees Ahmed Bhatti; Anjum Khalique; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2020)

An investigation on the prevalence of peste des petits ruminants in the camels of Sindh, Pakistan - Hamidur Rahman; Asghar Ali Kamboh; Shahid Hussain Abro; Muhammad Abubakar (Tropical Animal Health and Production, 2020)

Zinc status and its requirement by rural adults consuming wheat from control or zinc-treated fields - Muhammad Ahsin; Shahid Hussain; Zed Rengel; Mamoona Amir (Environmental Geochemistry and Health, 2020)

Cotton leaf curl Kokhran virus in association with Chili leaf curl betasatellite infecting mungbean (Vigna radiata.) and black gram (Vigna mungo.) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Ghulam Raza; Muhammad Zuhaib Khan; Shahid Mansoor; Imran Amin (Australasian Plant Pathology, 2020)

2D numerical modeling of two dam-break flood model studies in an urban locality - Sajjad Haider; Umer Saeed; Muhammad Shahid (Arabian Journal of Geosciences, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations - Naseer Ullah; Allah Ditta; Azeem Khalid; Sajid Mehmood; Muhammad Shahid Rizwan; Muhammad Ashraf; Fathia Mubeen; Muhammad Imtiaz; Muhammad Mazhar Iqbal (Journal of Soil Science and Plant Nutrition, 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

In-vitro evaluation of antimicrobial, antioxidant, alpha-amylase inhibition and cytotoxicity properties of Cannabis sativa - Syed Bilal Shah; Lubna Sartaj; Shahid Hussain; Nabi Ullah; Muhammad Idrees; Asma Shaheen; Muhammad Sufyan Javed; Muhammad Kashif Aslam (Advances in Traditional Medicine, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Composition and source apportionment of saccharides in aerosol particles from an agro-industrial zone in the Indo-Gangetic Plain - Muhammad Usman Alvi; Magdalena Kistler; Imran Shahid; Khan Alam; Farrukh Chishtie; Tariq Mahmud; Anne Kasper-Giebl (Environmental Science and Pollution Research, 2020)

Evaluating the combination of Metarhizium anisopliae and an enhanced form of diatomaceous earth (Grain-Guard) for the environmentally friendly control of stored grain pests - Nadia Saeed; Waqas Wakil; Muhammad Farooq; Muhammad Shakeel; Muhammad Shahid Arain; Qaiser Shakeel (Environmental Monitoring and Assessment, 2020)

Competitiveness, governance and globalization: What matters for poverty alleviation? - Muhammad Shahid Hassan; Samra Bukhari; Noman Arshed (Environment, Development and Sustainability, 2020)

Blood-based gene expression profile of oxidative stress and antioxidant genes for identifying surrogate markers of liver tissue injury in chronic hepatitis C patients - Muhammad Shahid; Muhammad Idrees; Azeem Mehmood Butt; Syed Mohsin Raza; Iram Amin; Afza Rasul; Samia Afzal (Archives of Virology, 2020)

Streptomyces sp. LH 4 promotes plant growth and resistance against Sclerotinia sclerotiorum in cucumber via modulation of enzymatic and defense pathways - Bong-Gyu Mun; Won-Hee Lee; Sang-Mo Kang; Sang-Uk Lee; Seok-Min Lee; Dong Yeol Lee; Muhammad Shahid; Byung-Wook Yun; In-Jung Lee (Plant and Soil, 2020)

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Amna Saleem; Amir Shakeel; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Impact assessment of land use and climate changes on the variation of runoff in Margalla Hills watersheds, Pakistan - Muhammad Shahid; Khalil Ur Rahman; Khaled S. Balkhair; Amjad Nabi (Arabian Journal of Geosciences, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

EVALUATION OF AQUACROP MODEL IN SIMULATING BITTER GOURD WATER PRODUCTIVITY UNDER SALINE IRRIGATION - Kamran Baksh Soomro; Sina Alaghmand; Muhammad Rizwan Shahid; Sanyogita Andriyas; Amin Talei (Irrigation and Drainage, 2020)
The agricultural sector, globally, faces multifaceted challenges to produce more with a minimum amount of water to enhance water productivity (WP). In this regard, crop modelling is an efficient approach for estimating WP and plays a significant role in addressing water management strategies. The present research has been conducted in Malir, Karachi—a semi‐arid region in the Sindh Province of Pakistan. The aim was to evaluate the effects of two different qualities of irrigation water including, fresh quality (IT 1 0.56 dS m −1 ) and saline groundwater (IT 2 2.89 dS m −1 ) on canopy cover (CC), biomass, crop yield and water productivity (WP) of bitter‐gourd. The AquaCrop model was used for the first time for bitter gourd in a semi‐arid region under drip irrigation. Simulations were carried out for two cropping seasons (i.e. season one (summer) and season two (winter). The modelled values were slightly higher than the measured biomass and yield values in both calibration and validation procedures. The performance of the AquaCrop model was estimated through different statistical indicators such as model efficiency ( E ), root mean square error (RMSE), and index of agreement ( d index ). These indicators revealed that the model simulated bitter gourd biomass and crop yield well. In addition, the model's performance was good under all irrigation treatments, with RMSE in the range 1.2–3.7, 0.5–1.8, d index 0.94–0.98 and E 0.93–0.97. The model also overestimated the biomass and crop yield. Overall, the AquaCrop model overestimated biomass and crop yield for both seasons. © 2019 John Wiley & Sons, Ltd.

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

In vitro induction of auto-allotetraploid in a newly developed wild rice line from Oryza alta Swallen - Liusheng Zhang; Fimanekeni Ndaitavela Shivute; Muhammad Qasim Shahid; Nabieu Kamara; Jinwen Wu; Xiangdong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Harnessing natural colorants from algal species for fabric dyeing: a sustainable eco-friendly approach for textile processing - Muhammad Azeem; Naeem Iqbal; Riffat Ayesha Mir; Shahid Adeel; Fatima Batool; Ali Ahmad Khan; Sadaf Gul (Journal of Applied Phycology, 2019)

Zinc and iron complexes of oleanolic acid, (OA) attenuate allergic airway inflammation in rats - Adnan Jehangir; Muhammad Shahzad; Khadija Shahid; Akbar Waheed; Farhana Ayub (Inflammopharmacology, 2019)

Multiple alphasatellites associated with Papaya leaf curl virus and Croton yellow mosaic betasatellite in Croton bonplandianus: first identification of Ageratum yellow vein Singapore alphasatellite in Pakistan - Roma Mustafa; Muhammad Hamza; Muhammad Nouman Tahir; Hira Kamal; Muhammad Zuhaib Khan; Atiq ur Rehman; Brian E. Scheffler; Rob W. Briddon; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2019)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

Effect of fat supplementation on physiological and reproductive performance of Holstein Friesian bulls during summer - Mahboob Ahmed Butt; Jalees Ahmed Bhatti; Anjum Khalique; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2019)

Selection of CMIP5 multi-model ensemble for the projection of spatial and temporal variability of rainfall in peninsular Malaysia - Muhammad Noor; Tarmizi bin Ismail; Shamsuddin Shahid; Kamal Ahmed; Eun-Sung Chung; Nadeem Nawaz (Theoretical and Applied Climatology, 2019)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Green algae, Cladophora glomerata L.–based natural colorants: dyeing optimization and mordanting for textile processing - Riffat Ayesha Mir; Shahid Adeel; Muhammad Azeem; Fatima Batool; Ali Ahmad Khan; Sadaf Gul; Naeem Iqbal (Journal of Applied Phycology, 2019)

Evaluation of the air pollution tolerance index of ornamentals growing in an industrial area compared to a less polluted area - Iftikhar Ahmad; Bilal Abdullah; John Martin Dole; Muhammad Shahid; Khurram Ziaf (Horticulture, Environment, and Biotechnology, 2019)

Ultrasonic assisted improved extraction and dyeing of mordanted silk fabric using neem bark as source of natural colourant - Shahid Adeel; Khalid Mahmood Zia; Muhammad Abdullah; Fazal-ur- Rehman; Mahwish Salman; Mohammad Zuber (Natural Product Research, 2019)

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies - Iram Sharif; Saba Aleem; Jehanzeb Farooq; Muhammad Rizwan; Abia Younas; Ghulam Sarwar; Shahid Munir Chohan (Physiology and Molecular Biology of Plants, 2019)

Removal of pharmaceuticals and personal care products using constructed wetlands: effective plant-bacteria synergism may enhance degradation efficiency - Phuong Minh Nguyen; Muhammad Afzal; Inaam Ullah; Naeem Shahid; Mujtaba Baqar; Muhammad Arslan (Environmental Science and Pollution Research, 2019)

Environment-health link in a context of urban agricultures: studies of oral exposure to pollutants in order promote the human health - Camille Dumat; Aurélie Pelfrêne; Muhammad Shahid (Environmental Science and Pollution Research, 2019)

Foliar uptake of arsenic nanoparticles by spinach: an assessment of physiological and human health risk implications - Natasha; Muhammad Shahid; Camille Dumat; Sana Khalid; Faiz Rabbani; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Abbas; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

Airborne foliar transfer of particular metals in Lactuca sativa L.: translocation, phytotoxicity, and bioaccessibility - Tiantian Xiong; Ting Zhang; Camille Dumat; Sophie Sobanska; Vincent Dappe; Muhammad Shahid; Yuanhong Xian; Xintong Li; Shaoshan Li (Environmental Science and Pollution Research, 2019)

Health risk assessment of drinking arsenic-containing groundwater in Hasilpur, Pakistan: effect of sampling area, depth, and source - Riaz Ahmad Tabassum; Muhammad Shahid; Camille Dumat; Nabeel Khan Niazi; Sana Khalid; Noor Samad Shah; Muhammad Imran; Samina Khalid (Environmental Science and Pollution Research, 2019)

Over 100 years of faults interaction, stress accumulation, and creeping implications, on Chaman Fault System, Pakistan - Muhammad Shahid Riaz; Shan Bin; Shahid Naeem; Wang Kai; Zujun Xie; Syed Mushhad M. Gilani; Umer Ashraf (International Journal of Earth Sciences, 2019)

The first report on serotyping of bluetongue virus in small ruminants of Khyber Pakhtunkhwa province, Pakistan - Amir Iftikhar Malik; Muhammad Ijaz; Tahir Yaqub; Muhammad Zubair Shabir; Muhammad Avais; Awais Ghaffar; Ahmad Ali; Shahid Hussain Farooqi; Khalid Mehmood (Tropical Animal Health and Production, 2019)

Infection of Urtica incisa with chili leaf curl virus and tomato leaf curl betasatellite in Oman - Muhammad Shafiq Shahid; Amir Raza; Muhammad Shafiq; Abdullah M. Al-Sadi; Rob W. Briddon (Journal of Plant Pathology, 2019)

Pcal_0970: an extremely thermostable l-asparaginase from Pyrobaculum calidifontis with no detectable glutaminase activity - Shahid Mahmood Chohan; Naeem Rashid; Muhammad Sajed; Tadayuki Imanaka (Folia Microbiologica, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Biogeochemical behavior of nickel under different abiotic stresses: toxicity and detoxification mechanisms in plants - Nuzhat Ameen; Muhammad Amjad; Behzad Murtaza; Ghulam Abbas; Muhammad Shahid; Muhammad Imran; Muhammad Asif Naeem; Nabeel K. Niazi (Environmental Science and Pollution Research, 2019)

Comparative effect of organic amendments on physio-biochemical traits of young and old bean leaves grown under cadmium stress: a multivariate analysis - Muhammad Shahid; Saliha Shamshad; Abu Bakar Umer Farooq; Marina Rafiq; Sana Khalid; Camille Dumat; Yongqing Zhang; Imtyaz Hussain; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Enterobacter sp. strain Fs-11 adapted to diverse ecological conditions and promoted sunflower achene yield, nutrient uptake, and oil contents - Muhammad Shahid; Sohail Hameed; Mohsin Zafar; Muhammad Tahir; Muhammad Ijaz; Mohsin Tariq; Khadim Hussain; Amanat Ali (Brazilian Journal of Microbiology, 2019)

Combined application of biochar and PGPR consortia for sustainable production of wheat under semiarid conditions with a reduced dose of synthetic fertilizer - Muhammad Ijaz; Muhammad Tahir; Muhammad Shahid; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Khalid Mahmood; Mubshar Hussain (Brazilian Journal of Microbiology, 2019)

Hereditary brain tumor with a homozygous germline mutation in PMS2: pedigree analysis and prenatal screening in a family with constitutional mismatch repair deficiency (CMMRD) syndrome - Shahid Mahmood Baig; Ambrin Fatima; Muhammad Tariq; Tahir Naeem Khan; Zafar Ali; Mohammad Faheem; Humera Mahmood; Patrick Killela; Matthew Waitkus; Yiping He; Fangping Zhao; Sizhen Wang; et al. (Familial Cancer, 2019)

The Rep proteins encoded by alphasatellites restore expression of a transcriptionally silenced green fluorescent protein transgene in Nicotiana benthamiana - Qamar Abbas; Imran Amin; Shahid Mansoor; Muhammad Shafiq; Michael Wassenegger; Rob W. Briddon (VirusDisease, 2019)

Exogenous Potassium–Instigated Biochemical Regulations Confer Terminal Heat Tolerance in Wheat - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Aown Sammar Raza; Muhammad Kashif; Abdul Shakoor; Muhammad Sarwar (Journal of Soil Science and Plant Nutrition, 2019)

Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2019)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Alleviative role of exogenously applied mannitol in maize cultivars differing in chromium stress tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Afzal Hussain; Muhammad Rizwan Shahid; Saud A. Alamri; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Assessment of genetic diversity in round gourd (Praecitrullus fistulosus) germplasm of Pakistan considering morphological characters - Adeel Shahid; Chaudhary Muhammad Ayyub; Mazhar Abbas; Rashid Ahmad (Genetic Resources and Crop Evolution, 2019)

A multivariate analysis of physiological and antioxidant responses and health hazards of wheat under cadmium and lead stress - Behzad Murtaza; Faryal Naeem; Muhammad Shahid; Ghulam Abbas; Noor S. Shah; Muhammad Amjad; Hafiz Faiq Bakhat; Muhammad Imran; Nabeel Khan Niazi; Ghulam Murtaza (Environmental Science and Pollution Research, 2019)

Inorganic fouling control in reverse osmosis wastewater reclamation by purging carbon dioxide - Muhammad Kashif Shahid; Minsu Pyo; Young-Gyun Choi (Environmental Science and Pollution Research, 2019)

Cytological and transcriptome analyses reveal abrupt gene expression for meiosis and saccharide metabolisms that associated with pollen abortion in autotetraploid rice - Lin Chen; Muhammad Qasim Shahid; Jinwen Wu; Zhixiong Chen; Lan Wang; Xiangdong Liu (Molecular Genetics and Genomics, 2018)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Arsenic Level and Risk Assessment of Groundwater in Vehari, Punjab Province, Pakistan - Muhammad Shahid; Muhammad Khalid; Camille Dumat; Sana Khalid; Nabeel Khan Niazi; Muhammad Imran; Irshad Bibi; Iftikhar Ahmad; Hafiz Mohkum Hammad; Riaz Ahmad Tabassum (Exposure and Health, 2018)

Synthesis of new chiral 1,3,4-thiadiazole-based di- and tri-arylsulfonamide residues and evaluation of in vitro anti-HIV activity and cytotoxicity - Maria Shafique; Shahid Hameed; Muhammad Moazzam Naseer; Najim Aboud Al-Masoudi (Molecular Diversity, 2018)

Sustainable survival under climatic extremes: linking flood risk mitigation and coping with flood damages in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Muhammad Usman; M. Amjed Iqbal; Muhammad Arshad; M. Adnan Shahid; Klaus Müller (Environmental Science and Pollution Research, 2018)

Interaction between PGPR and PGR for water conservation and plant growth attributes under drought condition - Naeem Khan; Asghari Bano; Muhammad Adnan Shahid; Wajid Nasim; MD Ali Babar (Biologia, 2018)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Understanding the impacts of climate change and human activities on streamflow: a case study of the Soan River basin, Pakistan - Muhammad Shahid; Zhentao Cong; Danwu Zhang (Theoretical and Applied Climatology, 2018)

Characterization of Huanglongbing disease associated with acid lime (Citrus aurantifolia Swingle) in Oman - Ahmed Al Fahdi; Alghaliya Al-Mamari; Muhammad S. Shahid; Sajeewa S. N. Maharachchikumbura; Claudine M. Carvalho; Simon L. Elliot; Abdullah M. Al-Sadi (Journal of Plant Pathology, 2018)

Molecular characterization and detection of a novel vitivirus infecting blackberry - Mohamed Hassan; Muhammad S. Shahid; Ioannis E. Tzanetakis (Archives of Virology, 2018)

Epigallocatechin Gallate as an anti-obesity therapeutic compound: an in silico approach for structure-based drug designing - Muhammad Shahid Javaid; Noreen Latief; Bushra Ijaz; Usman Ali Ashfaq (Natural Product Research, 2018)

Evidence of genetically diverse virulent mating types of Phytophthora capsici from Capsicum annum L. - Kiran Nawaz; Ahmad Ali Shahid; Louis Bengyella; Muhammad Nasir Subhani; Muhammad Ali; Waheed Anwar; Sehrish Iftikhar; Shinawar Waseem Ali (World Journal of Microbiology and Biotechnology, 2018)

Terminal drought and seed priming improves drought tolerance in wheat - Tahira Tabassum; Muhammad Farooq; Riaz Ahmad; Ali Zohaib; Abdul Wahid; Muhammad Shahid (Physiology and Molecular Biology of Plants, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Correction to: Genome-Wide Analysis of Genetic Variations and the Detection of Rich Variants of NBS-LRR Encoding Genes in Common Wild Rice Lines - Hang Yu; Muhammad Qasim Shahid; Rongbai Li; Wei Li; Wen Liu; Fozia Ghouri; Xiangdong Liu (Plant Molecular Biology Reporter, 2018)

Genome-Wide Analysis of Genetic Variations and the Detection of Rich Variants of NBS-LRR Encoding Genes in Common Wild Rice Lines - Hang Yu; Muhammad Qasim Shahid; Rongbai Li; Wei Li; Wen Liu; Fozia Ghouri; Xiangdong Liu (Plant Molecular Biology Reporter, 2018)

A critical review of mechanisms involved in the adsorption of organic and inorganic contaminants through biochar - Zohaib Abbas; Shafaqat Ali; Muhammad Rizwan; Ihsan Elahi Zaheer; Afifa Malik; Muhammad Ahsan Riaz; Muhammad Rizwan Shahid; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Ensembling Downscaling Techniques and Multiple GCMs to Improve Climate Change Predictions in Cryosphere Scarcely-Gauged Catchment - Muhammad Azmat; Muhammad Uzair Qamar; Shakil Ahmed; Muhammad Adnan Shahid; Ejaz Hussain; Sajjad Ahmad; Rao Arsalan Khushnood (Water Resources Management, 2018)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Introgression and inheritance of charcoal rot (Macrophomina phaseolina) resistance from silver sunflower (Helianthus argophyllus Torr. & A. Gray) into cultivated sunflower (Helianthus annuus L.) - Muhammad Shehbaz; Saeed Rauf; Abdullah M. Al-Sadi; Shahid Nazir; Saira Bano; M. Shahzad; Muhammad Mubashar Hussain (Australasian Plant Pathology, 2018)

Effects of increasing dietary protein supplies on milk yield, milk composition, and nitrogen use efficiency in lactating buffalo - Muhammad Naveed-ul-Haque; Muhammad Uzair Akhtar; Rizwan Munnawar; Saba Anwar; Anjum Khalique; Murtaza Ali Tipu; Fayyaz Ahmad; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2018)

A comparative study to evaluate efficiency of EDTA and calcium in alleviating arsenic toxicity to germinating and young Vicia faba L. seedlings - Marina Rafiq; Muhammad Shahid; Saliha Shamshad; Sana Khalid; Nabeel Khan Niazi; Ghulam Abbas; Muhammad Farhan Saeed; Mazhar Ali; Behzad Murtaza (Journal of Soils and Sediments, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Cadmium Immobilization Potential of Rice Straw-Derived Biochar, Zeolite and Rock Phosphate: Extraction Techniques and Adsorption Mechanism - Saqib Bashir; Muhammad Shahid Rizwan; Abdus Salam; Qingling Fu; Jun Zhu; Muhammad Shaaban; Hongqing Hu (Bulletin of Environmental Contamination and Toxicology, 2018)

A novel mutation in RDH5 gene causes retinitis pigmentosa in consanguineous Pakistani family - Neelam Sultan; Irfan Ali; Shazia Anwer Bukhari; Shahid Mahmood Baig; Muhammad Asif; Muhammad Qasim; Muhammad Imran Naseer; Mahmood Rasool (Genes & Genomics, 2018)

First report of leaf spot caused by Phytophthora capsici on chili pepper (Capsicum frutescens L.) in Pakistan - Kiran Nawaz; Ahmad Ali Shahid; Muhammad Nasir Subhani; Sehrish Iftikhar; Waheed Anwar (Journal of Plant Pathology, 2018)

Sensitivity to house dust mite allergens and prevalence of allergy-causing house dust mite species in Pothwar, Pakistan - Rubaba Hamid Shafique; Shamim Akhter; Shahid Abbas; Muhammad Ismail (Experimental and Applied Acarology, 2018)

Hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) from Pakistan: molecular characterisation by microarray technology - Bushra Jamil; Darius Gawlik; Muhammad Ali Syed; Asim Ali Shah; Shahid Ahmad Abbasi; Elke Müller; Annett Reißig; Ralf Ehricht; Stefan Monecke (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Microwave-assisted extraction and dyeing of chemical and bio-mordanted cotton fabric using harmal seeds as a source of natural dye - Shahid Adeel; Muhammad Zuber; Fazal-ur-Rehman; Khalid Mahmood Zia (Environmental Science and Pollution Research, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Use of statistical analysis to validate ecogenotoxicology findings arising from various comet assay components - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Khalid Abdullah Al-Ghanim; Muhammad Shahreef Masoud; Shahid Mahboob (Environmental Science and Pollution Research, 2018)

Earliness index deters Pectinophora gossypiella incidence on advanced cultivars of Bt cotton - Muhammad Rafiq Shahid; Muhammad Shakeel; Muhammad Farooq; Muhammad Shahid Arain; Chaudhary Muhammad Shahid Hanif; Haichen Yin; Muhammad Akram; Saghir Ahmad (Arthropod-Plant Interactions, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

P21Waf1/Cip1 depletion promotes dexamethasone-induced apoptosis in osteoblastic MC3T3-E1 cells by inhibiting the Nrf2/HO-1 pathway - Dandan Han; Jian Gao; Xiaolong Gu; Jan Georg Hengstler; Limei Zhang; Muhammad Shahid; Tariq Ali; Bo Han (Archives of Toxicology, 2018)

Influence of phosphorous fertilization on copper phytoextraction and antioxidant defenses in castor bean (Ricinus communis L.) - Guoyong Huang; Muhammad Shahid Rizwan; Chao Ren; Guangguang Guo; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Science and Pollution Research, 2018)

A novel trifunctional, family GH10 enzyme from Acidothermus cellulolyticus 11B, exhibiting endo-xylanase, arabinofuranosidase and acetyl xylan esterase activities - Saher Shahid; Razia Tajwar; Muhammad Waheed Akhtar (Extremophiles, 2018)

Role of circulatory microRNAs in the pathogenesis of hepatitis C virus - Iqra Almas; Samia Afzal; Muhammad Idrees; Muhammad Usman Ashraf; Iram Amin; Muhammad Shahid; Khadija Zahid; Sadia Zahid (VirusDisease, 2017)

Evaluation of Green Waste and Popular Twigs Biochar Produced at Low and High Pyrolytic Temperature for Efficient Removal of Metals from Water - Zeshan Aslam; Muhammad Khalid; Muhammad Naveed; Muhammad Shahid; Muhammad Aon (Water, Air, & Soil Pollution, 2017)

Economic assessment of conventional and conservation tillage practices in different wheat-based cropping systems of Punjab, Pakistan - Muhammad Shahzad; Mubshar Hussain; Muhammad Farooq; Shahid Farooq; Khawar Jabran; Ahmad Nawaz (Environmental Science and Pollution Research, 2017)

Phosphate-arsenate relations to affect arsenic concentration in plant tissues, growth, and antioxidant efficiency of sunflower (Helianthus annuus L.) under arsenic stress - Waqas Azeem; Muhammad Ashraf; Sher Muhammad Shahzad; Muhammad Imtiaz; Mumtaz Akhtar; Muhammad Shahid Rizwan (Environmental Science and Pollution Research, 2017)

Synthesis, crystal structure, anti-HIV, and antiproliferative activity of new pyrazolylthiazole derivatives - Murtaza Madni; Shahid Hameed; Muhammad N. Ahmed; Muhammad N. Tahir; Najim A. Al-Masoudi; Christophe Pannecouque (Medicinal Chemistry Research, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Evaluation of short-term health effects among rural women and reduction in household air pollution due to improved cooking stoves: quasi experimental study - Tanzil Jamali; Zafar Fatmi; Afshan Shahid; Aneeta Khoso; Muhammad Masood Kadir; Nalini Sathiakumar (Air Quality, Atmosphere & Health, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Arsenic accumulation and physiological attributes of spinach in the presence of amendments: an implication to reduce health risk - Muhammad Shahid; Marina Rafiq; Nabeel Khan Niazi; Camille Dumat; Saliha Shamshad; Sana Khalid; Irshad Bibi (Environmental Science and Pollution Research, 2017)

A new glycosidic antioxidant from Ranunculus muricatus L. (Ranunculaceae) exhibited lipoxygenasae and xanthine oxidase inhibition properties - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Shahid; Mehreen Lateef (Natural Product Research, 2017)

HCV-induced regulatory alterations of IL-1β, IL-6, TNF-α, and IFN-ϒ operative, leading liver en-route to non-alcoholic steatohepatitis - Rabia Nawaz; Sadia Zahid; Muhammad Idrees; Shazia Rafique; Muhammad Shahid; Ammara Ahad; Iram Amin; Iqra Almas; Samia Afzal (Inflammation Research, 2017)

Enzyme-based solutions for textile processing and dye contaminant biodegradation—a review - Shahzad Ali Shahid Chatha; Muhammad Asgher; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2017)

Chromium tolerance, oxidative stress response, morphological characteristics, and FTIR studies of phytopathogenic fungus Sclerotium rolfsii - Shahid Rafi; Amna Shoaib; Zoia Arshad Awan; Nayab Batool Rizvi; Nafisa; Muhammad Shafiq (Folia Microbiologica, 2017)

Osmopriming with CaCl2 improves wheat (Triticum aestivum L.) production under water-limited environments - Shahid Farooq; Mubshar Hussain; Khawar Jabran; Waseem Hassan; Muhammad S. Rizwan; Tauqeer A. Yasir (Environmental Science and Pollution Research, 2017)

Attribution of runoff change in the alpine basin: a case study of the Heihe Upstream Basin, China - Zhentao Cong; Muhammad Shahid; Danwu Zhang; Huimin Lei; Dawen Yang (Hydrological Sciences Journal, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Impact of Dysdercus koenigii Fabricius (Hemiptera: Pyrrhcoridae) density-dependent population on agronomic and qualitative characteristics of different transgenic cotton varieties - Muhammad Rafiq Shahid; Muhammad Farooq; Muhammad Shakeel; Abid Mahmood; Muhammad Dildar Gogi (Phytoparasitica, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Maximizing maize quality, productivity and profitability through a combined use of compost and nitrogen fertilizer in a semi-arid environment in Pakistan - Shahid Iqbal; Christian Thierfelder; Haroon Zaman Khan; Hafiz Muhammad Rashad Javeed; Muhammad Arif; Muhammad Shehzad (Nutrient Cycling in Agroecosystems, 2017)

Microelectrophoretic study of environmentally induced DNA damage in fish and its use for early toxicity screening of freshwater bodies - Bilal Hussain; Tayyaba Sultana; Salma Sultana; K. A. Al-Ghanim; Shahreef Masood; Muhammad Ali; Shahid Mahboob (Environmental Monitoring and Assessment, 2017)

Predicting Peak Flows in Real Time through Event Based Hydrologic Modeling for a Trans-Boundary River Catchment - Muhammad Adnan Shahid; Piero Boccardo; Muhammad Usman; Adriana Albanese; Muhammad Uzair Qamar (Water Resources Management, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Equilibrium modeling of cadmium biosorption from aqueous solution by compost - Iftikhar Ahmad; Muhammad Javed Akhtar; Iram Bashir Khan Jadoon; Muhammad Imran; Muhammad Imran; Shahid Ali (Environmental Science and Pollution Research, 2017)

Microwave-assisted enhancement of milkweed (Calotropis procera L.) leaves as an eco-friendly source of natural colorants for textile - Muhammad Hussaan; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; M. Tariq Javed; Ali Raza (Environmental Science and Pollution Research, 2017)

Transgenic expression of phytase in wheat endosperm increases bioavailability of iron and zinc in grains - Nabeela Abid; Asia Khatoon; Asma Maqbool; Muhammad Irfan; Aftab Bashir; Irsa Asif; Muhammad Shahid; Asma Saeed; Henrik Brinch-Pedersen; Kauser A. Malik (Transgenic Research, 2017)

Chitosan alleviates phytotoxicity caused by boron through augmented polyamine metabolism and antioxidant activities and reduced boron concentration in Cucumis sativus L. - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Guodong David Liu; Lincoln Zotarelli; Naeem Khan (Acta Physiologiae Plantarum, 2017)

An Investigation of the Innate Immune Response in Bovine Mammary Epithelial Cells Challenged by Prototheca zopfii - Zhaoju Deng; Muhammad Shahid; Limei Zhang; Jian Gao; Xiaolong Gu; Shiyao Zhang; Jiaqi Zou; Séamus Fanning; Bo Han (Mycopathologia, 2016)

Measurement of metal bioaccessibility in vegetables to improve human exposure assessments: field study of soil–plant–atmosphere transfers in urban areas, South China - TianTian Xiong; Camille Dumat; Antoine Pierart; Muhammad Shahid; Yuan Kang; Ning Li; Georges Bertoni; Christophe Laplanche (Environmental Geochemistry and Health, 2016)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Chemical immobilization of Pb, Cu, and Cd by phosphate materials and calcium carbonate in contaminated soils - Guoyong Huang; Xiaojuan Su; Muhammad Shahid Rizwan; Yifei Zhu; Hongqing Hu (Environmental Science and Pollution Research, 2016)

Immobilization of Pb and Cu in polluted soil by superphosphate, multi-walled carbon nanotube, rice straw and its derived biochar - Muhammad Shahid Rizwan; Muhammad Imtiaz; Guoyong Huang; Muhammad Afzal Chhajro; Yonghong Liu; Qingling Fu; Jun Zhu; Muhammad Ashraf; Mohsin Zafar; Saqib Bashir; Hongqing Hu (Environmental Science and Pollution Research, 2016)

First report on fish cysteine as a biomarker of contamination in the River Chenab, Pakistan - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Shahid Mahboob; Muhammad Farooq; Khalid Al-Ghanim; Shahid Nadeem (Environmental Science and Pollution Research, 2016)

Molecular characterization and growth optimization of halo-tolerant protease producing Bacillus Subtilis Strain BLK-1.5 isolated from salt mines of Karak, Pakistan - Nawab Ali; Nimat Ullah; Muhammad Qasim; Hazir Rahman; Shahid Niaz Khan; Abdul Sadiq; Muhammad Adnan (Extremophiles, 2016)

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake - Iftikhar Ahmad; Muhammad Javed Akhtar; Hafiz Naeem Asghar; Umber Ghafoor; Muhammad Shahid (Journal of Plant Growth Regulation, 2016)

Foliar treatment with Lolium perenne (Poaceae) leaf extract alleviates salinity and nickel-induced growth inhibition in pea - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Muhammad Akbar Anjum; Hafiz Haider Ali; Neil Scott Mattson; Francisco Garcia-Sanchez (Brazilian Journal of Botany, 2016)

The role of selenium in amelioration of heat-induced oxidative damage in cucumber under high temperature stress - Rashad Mukhatar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Muhammad Akbar Anjum; Francisco Garcia-Sanchez; Neil Scott Mattson (Acta Physiologiae Plantarum, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Characterization of Prototheca zopfii Genotypes Isolated from Cases of Bovine Mastitis and Cow Barns in China - Muhammad Shahid; Tariq Ali; Limei Zhang; Rongguang Hou; Shiyao Zhang; Laidi Ding; Dandan Han; Zhaoju Deng; Abdur Rahman; Bo Han (Mycopathologia, 2016)

Management of human health risk in the context of kitchen gardens polluted by lead and cadmium near a lead recycling company - Stéphane Mombo; Yann Foucault; Frédéric Deola; Irène Gaillard; Sylvaine Goix; Muhammad Shahid; Eva Schreck; Antoine Pierart; Camille Dumat (Journal of Soils and Sediments, 2016)

Relationship between rhizosphere acidification and phytoremediation in two acacia species - Ghulam Abbas; Muhammad Saqib; Javaid Akhtar; Ghulam Murtaza; Muhammad Shahid; Amjad Hussain (Journal of Soils and Sediments, 2016)

Synergism of polyamines and plant growth regulators enhanced morphogenesis, stevioside content, and production of commercially important natural antioxidants in Stevia rebaudiana Bert - Shahid Akbar Khalil; Nasir Kamal; Muhammad Sajid; Nisar Ahmad; Roshan Zamir; Naveed Ahmad; Shahid Ali (In Vitro Cellular & Developmental Biology - Plant, 2016)

Rice (Oryza sativa L.) hydraulic conductivity links to leaf venation architecture under well-watered condition rather than PEG-induced water deficit - Muhammad Adnan Tabassum; Yuhui Ye; Tingting Yu; Guanglong Zhu; Muhammad Shahid Rizwan; Muhammad Atif Wahid; Shaobing Peng; Yong Li (Acta Physiologiae Plantarum, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Mapping QTL associated with remobilization of zinc from vegetative tissues into grains of barley (Hordeum vulgare) - Shahid Hussain; Zed Rengel; Seyed A. Mohammadi; Asghar Ebadi-Segherloo; Muhammad A. Maqsood (Plant and Soil, 2016)

A novel homozygous splicing mutation of CASC5 causes primary microcephaly in a large Pakistani family - Sandra Szczepanski; Muhammad Sajid Hussain; Ilknur Sur; Janine Altmüller; Holger Thiele; Uzma Abdullah; Syeda Seema Waseem; Abubakar Moawia; Gudrun Nürnberg; Angelika Anna Noegel; Shahid Mahmood Baig; Peter Nürnberg (Human Genetics, 2016)

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes - Naila Shahid; Sana Tahir; Abdul Q. Rao; Sameera Hassan; Anwar Khan; Ayesha Latif; Muhammad Au Khan; Bushra Tabassum; Ahmed A. Shahid; Ahmed U. Zafar; Tayyab Husnain (Biologia, 2015)

A case study of Precambrian to Eocene sediments’ hydrocarbon potential assessment in Central Indus Basin of Pakistan - Shazia Asim; Peimin Zhu; Shahid Nadeem Qureshi; Muhammad Tayyab Naseer (Arabian Journal of Geosciences, 2015)

A streptozotocin-induced diabetic neuropathic pain model for static or dynamic mechanical allodynia and vulvodynia: validation using topical and systemic gabapentin - Gowhar Ali; Fazal Subhan; Muzaffar Abbas; Jehan Zeb; Muhammad Shahid; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Zinc-induced modulation of some biochemical parameters in a high- and a low-zinc-accumulating genotype of Cicer arietinum L. grown under Zn-deficient condition - Shadab Naseer Siddiqui; Shahid Umar; Muhammad Iqbal (Protoplasma, 2015)

Nitrate accumulation pattern in Brassica under nitrogen treatments - Samina Mazahar; Ovais Sareer; Shahid Umar; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Growth, V uptake, and antioxidant enzymes responses of chickpea (Cicer arietinum L.) genotypes under vanadium stress - Muhammad Imtiaz; Shuxin Tu; Zhijian Xie; Dan Han; Muhammad Ashraf; Muhammad Shahid Rizwan (Plant and Soil, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Silicon-induced alleviation of NaCl toxicity in okra (Abelmoschus esculentus) is associated with enhanced photosynthesis, osmoprotectants and antioxidant metabolism - Tahira Abbas; Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Aslam Pervez; Chaudhary Muhammad Ayyub; Muhammad Anjum Aqueel; Muhammad Mansoor Javaid (Acta Physiologiae Plantarum, 2015)

Variability of aerosol optical depth over Swat in Northern Pakistan based on satellite data - Khan Alam; Rehana Khan; Shahid Ali; Muhammad Ajmal; Gulzar Khan; Wazir Muhammad; Malak Azmat Ali (Arabian Journal of Geosciences, 2015)

Mapping QTLs for Swimming Ability Related Traits in Cyprinus carpio L. - Muhammad Younis Laghari; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Naeem Tariq Narejo; Yongxin Liu; Shahid Mehboob; K. Al-Ghanim; Yan Zhang; Xiaowen Sun (Marine Biotechnology, 2014)

Comparative cytological and transcriptomic analysis of pollen development in autotetraploid and diploid rice - Jinwen Wu; Muhammad Qasim Shahid; Haibin Guo; Wei Yin; Zhixiong Chen; Lan Wang; Xiangdong Liu; Yonggen Lu (Plant Reproduction, 2014)

Luteovirus: insights into pathogenicity - Muhammad Ali; Shahid Hameed; Muhammad Tahir (Archives of Virology, 2014)

Erratum to: The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

Assessment of cadmium accumulation, toxicity, and tolerance in Brassicaceae and Fabaceae plants—implications for phytoremediation - Naser A. Anjum; Shahid Umar; Muhammad Iqbal (Environmental Science and Pollution Research, 2014)

An analysis of the resistance of Gossypium arboreum to cotton leaf curl disease by grafting - Rahim Ullah; Khalid P. Akhtar; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2014)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Mechanisms of metal-phosphates formation in the rhizosphere soils of pea and tomato: environmental and sanitary consequences - Annabelle Austruy; Muhammad Shahid; Tiantian Xiong; Maryse Castrec; Virginie Payre; Nabeel Khan Niazi; Muhammad Sabir; Camille Dumat (Journal of Soils and Sediments, 2014)

Influence of plant species and phosphorus amendments on metal speciation and bioavailability in a smelter impacted soil: a case study of food-chain contamination - Muhammad Shahid; Tiantian Xiong; Nasir Masood; Tibo Leveque; Katelle Quenea; Annabelle Austruy; Yann Foucault; Camille Dumat (Journal of Soils and Sediments, 2014)

Influence of EDTA and citric acid on lead-induced oxidative stress to Vicia faba roots - Muhammad Shahid; Camille Dumat; Bertrand Pourrut; Jérôme Silvestre; Christophe Laplanche; Eric Pinelli (Journal of Soils and Sediments, 2014)

Synthetically modified bioisosteres of salicyl alcohol and their gastroulcerogenic assessment versus aspirin: biochemical and histological correlates - Gowhar Ali; Fazal Subhan; Nazar Ul Islam; Nasir Ullah; Robert D. E. Sewell; Muhammad Shahid; Ikhtiar Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Potential of Bacillus species against Meloidogyne javanica parasitizing eggplant (Solanum melongena L.) and induced biochemical changes - Muhammad Waseem Abbasi; Naeem Ahmed; Muhammad Javed Zaki; S. Shahid Shuakat; D. Khan (Plant and Soil, 2014)

Assessment of Toxicity and Potential Risk of Butene-fipronil Using Drosophila melanogaster, in Comparison to Nine Conventional Insecticides - Muhammad Shahid Arain; Xing-Xing Hu; Guo-Qing Li (Bulletin of Environmental Contamination and Toxicology, 2014)

Large scale mass movements triggered by the Kashmir earthquake 2005, Pakistan - Muhammad Basharat; Joachim Rohn; Mirza Shahid Baig; Muhammad Rustam Khan; Markus Schleier (Journal of Mountain Science, 2014)

Characterization of a novel missense mutation in the prodomain of GDF5, which underlies brachydactyly type C and mild Grebe type chondrodysplasia in a large Pakistani family - Muhammad Farooq; Hiroyuki Nakai; Atsushi Fujimoto; Hiroki Fujikawa; Klaus Wilbrandt Kjaer; Shahid Mahmood Baig; Yutaka Shimomura (Human Genetics, 2013)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Distinctive microRNA expression signatures in proton-irradiated mice - Shahid Yar Khan; Muhammad Akram Tariq; James Patrick Perrott; Christopher Drew Brumbaugh; Hyunsung John Kim; Muhammad Imran Shabbir; Govindarajan T. Ramesh; Nader Pourmand (Molecular and Cellular Biochemistry, 2013)

Molecular characterization of a new synthetic cry2ab gene in Nicotiana tabacum - Sohail Mehmood Karimi; Muhammad Nouman Sohail; Imran Amin; Shahid Mansoor; Zahid Mukhtar (Biotechnology Letters, 2013)

Complete nucleotide sequences of two begomoviruses infecting Madagascar periwinkle (Catharanthus roseus) from Pakistan - Muhammad Ilyas; Kiran Nawaz; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid (Archives of Virology, 2013)

Biofortification and estimated human bioavailability of zinc in wheat grains as influenced by methods of zinc application - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Tariq Aziz (Plant and Soil, 2012)

Chloroplast-encoded chlB gene from Pinus thunbergii promotes root and early chlorophyll pigment development in Nicotiana tabaccum - Shahid Nazir; Muhammad Sarwar Khan (Molecular Biology Reports, 2012)

Synthesis, characterization and in vitro hydrolysis studies of ester and amide prodrugs of dexibuprofen - Zaman Ashraf; Muhammad Imran; Shahid Amin (Medicinal Chemistry Research, 2012)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Root colonization and growth promotion of sunflower (Helianthus annuus L.) by phosphate solubilizing Enterobacter sp. Fs-11 - Muhammad Shahid; Sohail Hameed; Asma Imran; Saira Ali; Jan Dirk van Elsas (World Journal of Microbiology and Biotechnology, 2012)

Development of broad-spectrum insect-resistant tobacco by expression of synthetic cry1Ac and cry2Ab genes - Muhammad Nouman Sohail; Sohail Mehmood Karimi; Shaheen Asad; Shahid Mansoor; Yusuf Zafar; Zahid Mukhtar (Biotechnology Letters, 2012)

Effect of fulvic acids on lead-induced oxidative stress to metal sensitive Vicia faba L. plant - Muhammad Shahid; Camille Dumat; Jérôme Silvestre; Eric Pinelli (Biology and Fertility of Soils, 2012)

Mineral bioavailability in grains of Pakistani bread wheat declines from old to current cultivars - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Muhammad Khawar Khan (Euphytica, 2012)

Letter to the Editor: Mastrevirus sequences in a begomovirus-infected plant - Muhammad Mubin; Shahid Mansoor; Rob W. Briddon (Virus Genes, 2012)

High-density growth and crude protein productivity of a thermotolerant Chlorella vulgaris: production kinetics and thermodynamics - Shahid Mahboob; Abdul Rauf; Muhammed Ashraf; Tayyaba Sultana; Salma Sultana; Farhat Jabeen; Muhammad Ibrahim Rajoka; H. F. Alkahem Al-Balawi; Khalid A. Al-Ghanim (Aquaculture International, 2012)

Lithological and structural control of Hattian Bala rock avalanche triggered by the Kashmir earthquake 2005, sub-Himalayas, northern Pakistan - Muhammad Basharat; Joachim Rohn; Dominik Ehret; Mirza Shahid Baig (Journal of Earth Science, 2012)

Erratum to: Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

First cloning and characterization of aspartate aminotransferase from river buffalo (Bubalus bubalis) - Muhammad Shahid Nadeem; Naeem Rashid; Muzaffar Iqbal; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Oxidative stress elevated DNA damage and homocysteine level in normal pregnant women in a segment of Pakistani population - Shazia A. Bukhari; Muhammad Ibrahim Rajoka; Z. Ibrahim; Fatima Jalal; Shahid Mahboob Rana; Saeed A. Nagra (Molecular Biology Reports, 2011)

Characterization of resistance gene analogs from Gossypium arboreum and their evolutionary relationships with homologs from tetraploid cottons - Muhammad Tehseen Azhar; Imran Amin; Aftab Bashir; Shahid Mansoor (Euphytica, 2011)

Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

Identification of a major pathogenicity determinant and suppressors of RNA silencing encoded by a South Pacific isolate of Banana bunchy top virus originating from Pakistan - Imran Amin; Muhammad Ilyas; Javaria Qazi; Rohina Bashir; Jitender S. Yadav; Shahid Mansoor; Claude M. Fauquet; Rob W. Briddon (Virus Genes, 2011)

Abnormal PMC microtubule distribution pattern and chromosome behavior resulted in low pollen fertility of an intersubspecific autotetraploid rice hybrid - Jin-Hua He; Muhammad Qasim Shahid; Zhi-Xiong Chen; Xing-An Chen; Xiang-Dong Liu; Yong-Gen Lu (Plant Systematics and Evolution, 2011)

Synthesis of a New Tri-Branched PEG-IFNα2 and Its Impact on Anti Viral Bioactivity - Muhammad Farooq Sabar; Mustansara Yaqub; Mohsin Ahmad Khan; Nadeem Ahmad; Muhammad Usman Ghani; Mariam Shahid (International Journal of Peptide Research and Therapeutics, 2010)

Both malvaceous and non-malvaceous betasatellites are associated with two wild cotton species grown under field conditions in Pakistan - Muhammad Tehseen Azhar; Imran Amin; Zahid Iqbal Anjum; Muhammad Arshad; Rob W. Briddon; Shahid Mansoor (Virus Genes, 2010)

Erratum to: Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Detection of Mycobacterium avium subsp. paratuberculosis in tissue samples of cattle and buffaloes - Farhan Anwar Khan; Zafar Iqbal Chaudhry; Muhammad Ijaz Ali; Shahid Khan; Naima Mumtaz; Ijaz Ahmad (Tropical Animal Health and Production, 2010)

Molecular characterisation of Banana bunchy top virus (BBTV) from Pakistan - Imran Amin; Javaria Qazi; Shahid Mansoor; Muhammad Ilyas; Rob W. Briddon (Virus Genes, 2008)

Studies on the chemical constituents of Phyllanthus emblica - Habib-ur-Rehman; Khawaja Ansar Yasin; Muhammad Aziz Choudhary; Naeem Khaliq; Atta-ur-Rahman; Muhammad Iqbal Choudhary; Shahid Malik (Natural Product Research, 2007)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Assessment of genetic diversity among wheat (Triticum aestivum L.) cultivars from a range of localities across Pakistan using random amplified polymorphic DNA (RAPD) analysis - Muhammad Shahid Mukhtar; Mehboob-ur Rahmanw; Yusuf Zafar (Euphytica, 2002)